Synthetic microalgal–bacterial symbiotic system integrating oxidase-protease fusion enzyme for simultaneous removal of recalcitrant nitrogen-containing organic compounds and PET microplastics - Rui Xiao; Yushu Li; Peng Liu; Howard H. Chou (Bioresource Technology, 2027)

Endogenous 6-phospho-β-glucosidase overexpression in Lactiplantibacillus plantarum modulates selective enrichment of bioactive and volatile metabolites in black tea extract - Yao-Zeng Zhang; Zhi-Peng Cheng; Pei-Yi Feng; Xin-Xin Liu; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (Food Microbiology, 2026)

Polystyrene nanoparticles impair endometrial decidualization in early pregnant mice via oxidative stress-driven autophagy suppression and ferroptosis induction - Li-Qing Wang; Qian-Feng Qiao; Huang-Nian You; Yi-bin Zheng; Xiao-Mei Wu; Wen-Jie Yu; Zeng Liu; Wen-Juan Song; Lin-Hong Zhang; Jia-Rui Hu; Xin-Yu Mao; Yong-Jiang Zhou (Food and Chemical Toxicology, 2026)

Optimizing mass rearing and field release of Telenomus remus for effective biological control of Spodoptera litura - De-Rui Han; Guang Zou; Chao-Zhou Liu; Xia Wen; Xiao-Fei Yu; Mao-Fa Yang; Guy Smagghe; Jian-Feng Liu; Chun-Yang Huang (Crop Protection, 2026)

Safety and efficacy of recombinant botulinum toxin type A (Eveotox®) in patients with post-stroke upper limb spasticity: Results from a Phase Ib/II clinical trial - Rongrong Lu; Lingjing Jin; Jianzhong Xiong; Lixin Zhang; Yaling Liu; Leilei Xu; Rui Wu; Jianhua Tang; Liandong Zhao; Lihua Dong; Weifeng Luo; Yu Pan; et al. (Toxicon, 2026)

Insulin-like peptide 3 facilitates sheep oocytes in vitro maturation and subsequent early embryo development - Qi Yang; Rui-Feng Zhang; Zhao-Yu Jiang; Dui Sun; Rui-Hao Tang; Xiao-Yi Zhang; Yi-Tong Li; Wen-Ying Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Theriogenology, 2026)

Multiphase phosgene detection on machine learning-enhanced fluorescent sensor arrays - Rui Xiao; Kongqing Zhang; Dun Zhou; Jiaxuan Ma; Changchang Ji; Zhanhua Huang; Xiaobai Li; Yongpeng Liu; Hongwei Ma (Analytica Chimica Acta, 2026)

Microbiome dysbiosis and metabolic reprogramming in kiwifruit peel during Botrytis cinerea infection - Jingsheng Chen; Rui Ma; Yu Zhao; Yuan Sui; Zhuo Chen; Xianmei Xiao; Zhenshuo Wang; Jia Liu (Postharvest Biology and Technology, 2026)

Biodiversity and paleoenvironmental reconstruction of the Jehol Biota in the Jiufengshan Formation of eastern Inner Mongolia, northeastern China - Yan Xue; Zhenhua Jing; Xiao Teng; Xin Zhang; Peihan Liu; Siyu Song; Rui Fang; Gang Li; Daran Zheng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Bi-based electrocatalysts for acidic CO2-to-formate electrolysis: Dynamic interfacial microenvironment regulation and industrial perspectives - Xiao Liu; Wei Cai; Xuanwen Liu; Rui Guo (Journal of Environmental Chemical Engineering, 2026)

Co-inoculation of lactic acid bacteria improves silage quality and mitigates antibiotic resistance gene transmission by restructuring the microbial community in hybrid Pennisetum silage - Duoting Wu; Wan Zhong; Zhisheng Wang; Xinyan Tao; Liyuan Shi; Peng Dai; Fali Wu; Yahui Jiang; Quanhui Peng; Jianxin Xiao; Yiping Tang; Huawei Zou; et al. (Journal of Environmental Chemical Engineering, 2026)

CTAB-assisted synthesis of HoY2Ox composite oxide catalyst with highly exposed specific (211) plane for cyclohexene epoxidation - Yingjie Wang; Fang Wang; Yuting Luo; Rui Wang; Xiao Fan; Meng Xu; Junhua Liu (Journal of Environmental Chemical Engineering, 2026)

Temperature-responsive topology regulation for fire-safe, high-strength polyamide 66 via a low-barrier phosphonate spacer - Qin Zhang; Guo-Rui Zhu; Xiang-Xin Xiao; Ya-Dong Wang; Li Chen; Bo-Wen Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2026)

Waste akebiae trifoliata-derived WO3 hierarchical tubes efficient detection of ppb-level triethylamine gas at low temperature and application in food freshness detection - Wen-Xiao Li; Jia-Wang Wang; Rui-Long Li; Qiu-Yue Zheng; Bao-Yu Song; Bo-Ya Liu; Li-Xia Zhao; Ying Fu; Ying-Ming Xu (Chemical Engineering Journal, 2026)

A review of atmospheric black carbon research progress in China - Qi Zhou; Shunyao Wang; Shujun Bie; Junjie Cai; Yingjun Chen; Yuan Cheng; Xiang Ding; Jianwei Gu; Jie Li; Weijun Li; Dantong Liu; Jiaying Liu; et al. (Atmospheric Environment, 2026)

Schisandra chinensis polysaccharide attenuates diabetic islet cell injury by promoting autophagy via suppression of the PI3K/AKT/mTOR signaling cascade - Xiao-Ying Zhou; Guang-Hui Zhou; Wen-Chong Li; Jun-Feng Zhang; Ming-Kui Lin; Zi-Cong Liang; Rui-Ke Liu (Journal of Molecular Histology, 2026)

Intracellular imaging and therapeutic application of liver fibrosis via a microRNA-on self-stacking amplification circuit - Xiao-Meng Sun; Yin-Xiang Chen; Lin-Ru Xu; Rui Bai; Li-Zeng Zhu; Gaoxiang Ma; Lian-Wen Qi; Yu Gu; Qun Liu (Analytica Chimica Acta, 2026)

Inside-out conversion of open pores into closed nanopores enables high-plateau hard carbon anodes for sodium-ion batteries - Zhuo Xiong; Rui Li; Ping Liu; Shuang Lin; Chaoshu Zhao; Wenyuan Fu; Jiale Shen; Lili Xiao; Xuedan Chen; Jianping Long; Xianguang Zeng; Anjun Hu; et al. (Chemical Engineering Journal, 2026)

Modulating local structural disorder in layered cathodes with alternating edge- and face-sharing octahedra for enhanced high-rate performance - Chengjun Fan; Xiaoxia Yang; Lingling Yao; Qin Wang; Xiao Ouyang; Leidang Zhou; Zhiwen Gao; Rui Jia; Xibang Chen; Jing Chen; Hao Liu; Bin Liao; et al. (Chemical Engineering Journal, 2026)

A pH-responsive sequential-releasing hydrogel breaks the infection-inflammation-oxidative stress cycle to promote vascularized healing in refractory anal fistula - Qiuqun Xiao; Kailan Liu; Manzhen Zhou; Ruyi Peng; Luyang Dai; Rui Zhang; Lin Luo; Yong Xue; Yunrui Hu (Chemical Engineering Journal, 2026)

Ecological risk assessment of 1,4-thioxane and its remediation by a synthetic microbiome based on a sulfur transformation system: From multi-omics to water application - Xu Yang; Ai-de Peng; Yong-han Huang; Jia-hao Cheng; Hao-tian Zhong; Hai-tang Zhou; Pei-qi Liu; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Xue-gang Luo (Water Research, 2026)

Prevalence and risk factors of bovine tuberculosis in dairy cattle, 2020–2025: A systematic review and meta-analysis of available literature - Qi Wang; Xiao-Nan Wang; Xiao-Qun Liu; Long-Ge Zhao; Zi-Tong Jing; Tian Tian; Jia-Ting Zhang; Yi-Xing Zhao; Jian-Ming Li; Nai-Chao Diao; Kun Shi; Rui Du (Preventive Veterinary Medicine, 2026)

Early Cretaceous Jehol Biota in the Qinling Orogenic Belt: palaeobiogeographical and palaeoecological implications - Siyu Song; Xin Zhang; Xiao Teng; Ting Li; Tingting Yu; Jiahao Li; Yan Xue; Peihan Liu; Rui Fang; Xiangdong Zhao; Daran Zheng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Interfacial electron redistribution stabilizes Cu-centered redox cycling for efficient Fenton-like catalysis - Xiao-Ying Li; Ruo-Lan Xu; Ren Zhu; Ting-Yu Zhang; Wen-Rui Wang; Wu-Jun Liu; Hong Jiang (Journal of Cleaner Production, 2026)

Machine learning-based geographical origin discrimination of Smilax china - Boyuan Xu; Haotian Zhong; Yan Wang; Rui Liu; Xiao Huang; Heming Wu; Lei Wang; Aiping Deng; Yong Xiao; Kun Yu (Journal of Applied Research on Medicinal and Aromatic Plants, 2026)

Triterpenoid saponin variation in cultivated and mountain-cultivated ginseng aqueous extracts is associated with distinct myocardial multi-omics and intestinal microbial–metabolic response patterns - Yanxu Zhang; Runlai Lu; Rui Liu; Ye Qiu; Yifei Wang; Jialin Wei; Qiang Chen; Chunping Xiao; Zhidong Qiu (Food Research International, 2026)

Evolution of cracks in red-bed mudstone under the coupling of drying-wetting cycle and temperature: From microscopic mechanism to a kinetic model - Guodong Zhang; Sixiang Ling; Chengjun Xiao; Hongwei Liu; Xiaoning Li; Rui Deng; Xiyong Wu (Engineering Geology, 2026)

Coexistence of urban decay and crime? Exploring the association of physical disorder and streetscape perceptions with crime density - Rongyi Sun; Linggui Liu; Jin Rui; Xiao Rong; Yuheng Tu (Applied Geography, 2026)

Kit Ligand enhances in vitro oocyte maturation and early embryonic development in sheep - Qi Yang; Dui Sun; Zhao-Yu Jiang; Rui-Hao Tang; Rui-Feng Zhang; Xiao-Yi Zhang; Wen-Ying Li; Yi-Tong Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Animal Reproduction Science, 2026)

Botany, extraction methods, chemical constituents, pharmacological activities, and food applications of Stauntonia chinensis - Chen-Yu Chang; Xiao-Yun Wang; Ke-Jia Liu; Qi Li; Shu-Yan Lu; Qin-Ge Ma; Rong-Rui Wei (Natural Product Research, 2026)

PTPσ mediates the integration of grafted neuronal tissueoids with host neural pathways after complete spinal cord injury - Rui Mao; Yuan-Huan Ma; Jin-Yuan Xiao; Qing-Shuai Wei; Yin-Chun Zhao; Qi-Xing Hu; Hou-Ge Li; Ke-Jun Zhang; Lai-Jian Wang; Hui-Juan Shi; Li-Zhi Peng; Jun-Hua Wang; et al. (Science China Life Sciences, 2026)

Delta-Band Dynamics of CaMKI-Positive Preoptic Neurons Encode Thermal Homeostatic Information - Dian-Dian Wang; Run-Zhou Yang; Song-Tang Sun; Ya-Lun Sun; Rui-Yu Wang; Xiao-Yan Meng; Sen-Miao Li; Jia-Kang Li; Pei-Pei Liu; Shu-Ang Li; Jian-Sheng Kang (Neuroscience Bulletin, 2026)

A legacy pollutant deciphered by multiomics toxicology and targeted remediation by a synthetic microbial consortium: a case study of 2-chloroacetophenone from abandoned chemical weapons - Xu Yang; Ai-De Peng; Jia-Hao Cheng; Yong-Han Huang; Hao-Tian Zhong; Hai-Tang Zhou; Pei-Qi Liu; Xiao-Hui Ji; Chen Li; Sheng-Rui Zhang; Jin-Long Lai; Xue-Gang Luo; et al. (Water Research, 2026)

A novel AGTPBP1-ERK/MYLK network mediates pancreatic cancer progression - Zhe-yu Yang; Qian Zhang; Jing-rui Yang; Xiao-dong Zhang; Chang-le Liu; Jia-yu Huang; Rui Xiao; Jian-jun Ren (Tissue and Cell, 2026)

Tuning the Cu/Zn ratio in copper-zinc phosphate catalysts: Mechanistic insights into activity and stability of anisole acetylation - Yuting Luo; Yingjie Wang; Rui Wang; Xiao Fan; Meng Xu; Junhua Liu; Fang Wang (Fuel, 2026)

Advancing PCOS drug development: multi-omics discovery of key targets and repurposable compounds - Zhiyong Xiao; Xin Zhang; Yuxin Zhang; Jiajia Liu; Xiaoyan Zheng; Rui Lai; Han Yang; Jie Wu; Jie Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Cross-species comparative transcriptomic analysis of spermatozoa reveals species-specific regulatory networks linked to fertilization-associated genes in cattle, sheep and goats - Yue Zhao; Linfeng Bai; Qiqi Jiang; Hao Xiao; Fangyuan Liu; Bilige Wuyun; Rihan Wu; Chunxia Hao; Rui Ding; Peng Yuan; Lizhi Wang; Ying Lu; et al. (Science China Life Sciences, 2026)

Integrative multi-omics reveals NQO1-mediated airway epithelial injury as a key mechanism of bisphenol A–induced COPD - Rui Li; Shaobo Ge; Jin Liu; Yuer Li; Shiyuan Yao; Shuhan Ma; Yuanliang Sun; Xiao Li; Xia Yang; Jie Zhang; Ming Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Preparation and characterisation of two new malonylated rare ginsenosides by acid hydrolysis and their anti-hepatoma activities - Ya-Qian Lu; Xiao-Man Jin; Fu-Rui Zhang; Mei-Hui Li; Wen-Wen Li; Wei Li; Chun-Su Yuan; Zhi Liu (Natural Product Research, 2026)

Unraveling antibiotic fate in a highly urbanized estuary: Spatiotemporal patterns, multi-media partitioning, and contaminant prioritization - Nian-Nian Wu; Shan Liu; Ru Xu; Qian-Yi Huang; Yun-Feng Pan; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu; Xiao-Ping Huang (Marine Pollution Bulletin, 2026)

Os79, a UDP‐Glycosyltransferase, negatively regulates cadmium tolerance and accumulation in rice - Rui Guo; Hao Yu Wang; Chong Wei Zhong; Rong Rong Ma; Jiu Huang; Jin Chen; Xian Jiao Guan; Lu Zheng; Ren Fang Shen; Ming Qing Liu; Xiao Fang Zhu (Journal of Hazardous Materials, 2026)

A new pathway to enhance the oceanic carbon sink: inorganic carbonate precipitation driven by calcium–alkali coupling - Shan Shan Liu; Jin Ming Song; Xue Gang Li; Hua Mao Yuan; Li Qin Duan; Jun Lei Li; Bao Xiao Qu; Qi Dong Wang; Jun Ma; Jian Wei Xing; Zhi Bo Wang; Rui Wang; et al. (Journal of Environmental Management, 2026)

Tuning the fate of radical intermediates: The pivotal role of catalyst acidity and texture in steering lignin pyrolysis pathways - Yuyang Fan; Chao Liu; Zhengxue Zhang; Shiliang Wu; Anqing Zheng; Zhaojuan Zheng; Jia Ouyang; Rui Xiao (Fuel, 2026)

Reprogrammable actuation in shape memory hydrogels with soft and hard magnetic particles - Ye Tian; Yuanyuan Bian; Zike Chen; Chang Zhao; Chengqian Zhang; Yi Song; Ye Qiu; Aiping Liu; Rui Xiao; Lu Dai; Huaping Wu (Chemical Engineering Journal, 2026)

Molecular characterization of a novel partitivirus isolated from Fusarium solani, the causal agent of tobacco root rot - Xiao Wu; Ying Wang; Rui Guo; Ya Rong Wang; Si Jun Li; Xiang Ping Zhou; Jie Zhong; Yan Song Xiao; Tian Bo Liu (Archives of Virology, 2026)

Self-supported cube-like Cu nanoparticles with in-situ growth for efficient CO2 electroreduction to hydrocarbons - Peijun Li; Weicong Xu; Xing Wang; Chao Liu; Anze Ning; Qingwen Chen; WulejiasiI Aerxin; Tao Li; Haowei Huang; Rui Xiao (Journal of Environmental Chemical Engineering, 2026)

Pt decorated core-shell ZnS:Cu doped epoxy composites: Achieving enhanced breakdown strength and defect visualization - Zhi-Hao Xing; Ming-Xiao Zhu; Jian-Yi Xue; Jia Cheng; Guang Li; Bing Xia; Chongzi Cao; Yanbing Ji; Rui Liu (Chemical Engineering Journal, 2026)

Hydrogen-bonding guided isoreticular supramolecular frameworks with self-recovery for efficient natural gas purification - Zhou-Rui Yan; Xiao-Han Li; Shi-Kai Zheng; Ze-Jiu Diao; Fan Li; Jin-Peng Liu; Guoliang Liu; Lin-Bing Sun (Chemical Engineering Journal, 2026)

Comparative Proteomic Insights into Low Molecular Weight Chitosan-Induced Drought Tolerance in Sugarcane - Gui Zhou; Xiao-Xia Liu; Li-Hang Qiu; Cheng-Lin Zou; Yang-Rui Li (Sugar Tech, 2026)

Development and validation of a Mn/MOF-808 based colorimetric platform for rapid and reliable on-site monitoring of iodide in marine environments - Yi-Ting Chen; Xiao-Jun Dai; Xi- Qing Xu; Pei Liu; Wen-Ge Zhang; Wen-Rui Zhang; Shu-Xuan Li; Peng Wang; Chun-Hui Gong; Yi Yang (Analytica Chimica Acta, 2026)

Prevalence and Molecular Characterization of Entamoeba spp. in Pigs in Shanxi Province, North China - Ze-Dong Zhang; Han-Dan Xiao; Dong-Yang Wang; Zi-Rui Wang; Xun-Zhi Liu; Nan Su; Xing-Quan Zhu; Qing Liu; Wen-Wei Gao (Acta Parasitologica, 2026)

New 14,15-dinor- neo -clerodane and neo -clerodane diterpenoids from Ajuga macrosperma Wall. ex benth - Yi-huan Li; Yi-hang Ba; Jian-fen Xiao; Shuai Chen; Tian-qing Zhu; Kai-xiang Liu; Hong-ping He; Hua-yi Jiang; Rui Yang (Natural Product Research, 2026)

Cooling energy demand for maintaining frozen wall thickness in artificial ground freezing - Xu Li; Rui-ming Li; Xiao-kang Li; Shuang Liu; Zheng Yang (Tunnelling and Underground Space Technology, 2026)

Do gender differences affect the sustainable intensification of cultivated land use among farming households?--evidence from Shenyang, China - Xiao Lyu; Yuan Liu; Wenlong Peng; Rui Yu (Journal of Rural Studies, 2026)

Impact of habitat biotic factors on selective food hoarding in Brandt's voles - Shan-shan Sun; Tao Liu; Hai-rui Yang; Zhi-liang Zhang; Ya-nan Li; Ming Ming; Hao-ting Zhang; Hai-wen Yan; Xin Li; Lin-lin Li; Na Zhu; Xiao-dong Wu; et al. (Journal of Arid Environments, 2026)

Bioactive edestin peptides from hemp (Cannabis sativa L.) seeds improve exercise performance under hypobaric hypoxia - Rui Zhang; Jie Liu; Liang-Liang Chen; Jia-Qi Liu; Xiao-Qian Jin; Zi-Xian Fu; Jun-Bin Xiong; Bin Jia; Jun-Ling Shi; Da-Chuan Yin (Food Research International, 2026)

Release kinetics and environmental risks of TCPP from polyurethane foam microplastics: Insights from artificial seawater to natural estuarine water - Shan-Shan Yao; Yu-Han Xie; Zhi-Yan Wang; Shan Liu; Rui Hou; Lang Lin; Yu Zhong; Xiao-Ping Huang; Heng-Xiang Li; Xiang-Rong Xu (Environmental Pollution, 2026)

Erratum to “Evidence of shallow subsurface ice at Tianwen-1 landing site” [Earth and Planetary Science Letters 678 (2026)/EPSL 119832] - Xindong Meng; Ling Zhang; Yi Xu; Iraklis Giannakis; Roberto Bugiolacchi; Jiannan Zhao; Xiaoping Zhang; Qiquan Yang; Rui Chen; Renrui Liu; Xiaoting Xu; Huaqing Cao; et al. (Earth and Planetary Science Letters, 2026)

Biochar-driven cycling of Fe(II)/Fe(III) and Co(II)/Co(III) in cobalt ferrite for efficient norfloxacin degradation via Fenton-like pathway - Rui Gan; Fanguang Kong; Xiao Zhao; Daoqing Liu; Shuo Zhang; Wen Liu; Si Li; Weiling Sun (Chemical Engineering Journal, 2026)

Two-level energy storage semi-interpenetrating hydrated salt gel for battery cooling and thermal runaway propagation mitigation - Rui Wei; Yuhan Xiao; Jianfeng Wang; Fuqiang Wang; Di-Lin Chen; Bowei Chen; Zipeng Su; Yongkai Jia; Ruixuan Qiu; Yiqun Liu; Quanqing Yu; Fen Liu (Chemical Engineering Journal, 2026)

The light side of the microbiome in trauma: Mechanism and applications - Han-Yue Luo; Lei-Ming Cao; Kan Zhou; Yi-Fu Yu; Yao Xiao; Guang-Rui Wang; Bing Liu; Qiu-Ji Wu; Xiao-Long Wang; Zhi-Yong Song; Lin-Lin Bu (Chemical Engineering Journal, 2026)

Data-driven discovery of high-performance surface passivators for efficient and stable perovskite solar cells - Feiyi Zhou; Zeyu Wang; Shangshang Zhao; Xu Zhang; Qingyue Guo; Runze Dai; Fanxiang Meng; Huajie Lyu; Jun Wan; Yi Dong; Zhe Jin; Shanqing Yu; et al. (Chemical Engineering Journal, 2026)

5-HMF-driven microporous N, O-dual doped carbon materials based on chitosan for syngas purification and CO2 capture - Jinpeng Zhai; Chao Liu; Lijuan Sun; Beichen Xue; Yongxin Wu; Rui Xiao (Carbohydrate Polymers, 2026)

Metabolomic changes following PMSG-induced estrus synchronization in Qianbei Ma goats - Feng-Xin Qiao; Yong-Hong Ju; Xiao-Dong Wang; Peng-Cheng An; Quan Ji; Rui-Yang Li; Ting-Ji Zeng; Qing Liu; Dai-Yue Zhang; Zu-Han Feng; Mao-Sheng Cao; Xiang Chen (Animal Reproduction Science, 2026)

Integrated metabolomics and transcriptomics analyses provide insights into flavor and color regulation during tomato postharvest ripening - Xian-Kang Xiao; Wei-Xin Liu; Xiao Lu; Cai-Rui Chen; Xin-Yi Zhang; Xiao-Jun Pu; Feng Wang (Postharvest Biology and Technology, 2026)

Changes of intracellular and extracellular organic matter in Microcystis colonies after ultrasonic stress and during recovery cultivation - Jia Liang; Zhipeng Duan; Lei Liu; Chao Xing; Xiao Tan; Jun Sun; Yangxue Xu; Rui Zhu (Journal of Environmental Management, 2026)

AI-Facilitated selenium-enriched peptides: Synthesis, bioactivity, virtual screening, and food industry potential, and future prospects - Zhi-Rui Ding; Jun-Wei Chen; Lin-Jie Xiao; Meng-Yu Gao; Jayani Chandrapala; Long Pan; Yang Lin; Hui-Rong Wang; Na Liu; Kang-Yi Zhang; Ai-Mei Liao (Food Bioscience, 2026)

A COF-spaced Plasmon-enhanced fluorescent nanocomposite for ultrasensitive and on-site dual-modality lateral flow immunoassay - Han Han; Junhua Su; Zhenzhen Liu; Zijin Tong; Lei Wu; Shihui Zhu; Wentao Zhao; Baohua Zhao; Rui Xiao (Chemical Engineering Journal, 2026)

Electronic structure engineered Fe-ZnO@au-DTNB nanotags for ultrasensitive SERS-based lateral flow immunoassay - Renjie Xiong; Junhua Su; Shizhe Wang; Zijin Tong; Renlong Zhu; Yufei Liu; Rui Xiao (Chemical Engineering Journal, 2026)

Effects of short-term grazing prohibition on methane, nitrous oxide and nitric oxide fluxes from alpine meadows on eastern Tibetan Plateau - Xiao Chen; Rui Wang; Lei Ma; Han Zhang; Zhisheng Yao; Kai Wang; Wei Zhang; Siqi Li; Shenghui Han; Chunyan Liu; Yong Li; Xunhua Zheng (Agriculture, Ecosystems & Environment, 2026)

The climate threshold for locally absent rings in Siberian larch exhibits significant variation with altitude - Xiao-xia Gou; Tong-wen Zhang; Hua-ming Shang; Shu-long Yu; Dong Guo; Rui-bo Zhang; Li Qin; Sheng-xia Jiang; Yu-ting Fan; Ke-xiang Liu; He-li Zhang; Kai-long Guo; et al. (Agricultural and Forest Meteorology, 2026)

Spatial Distribution Characteristics of Secondary PM2.5 in Beijing-Tianjin-Hebei Region Based on Time Series Decomposition - Qing Yao; Jing Ding; Zi-rui Liu; Xu Yang; Ying-xiao Tang; Zi-yin Cai; Su-qin Han (Aerosol Science and Engineering, 2026)

Who is the best allogeneic hematopoietic stem cell transplant donor for severe aplastic anemia? Data from the Chinese Bone Marrow Transplantation Registry Group (CBMTRG) - Zheng-Li Xu; Lan-Ping Xu; Shun-Qing Wang; De-Pei Wu; Xi Zhang; Su-Jun Gao; Ling-Hui Xia; Rui Xi; Jian-Min Yang; Qi-Fa Liu; Ming Jiang; Xiao-Sheng Fang; et al. (Science Bulletin, 2026)

Oxidized- and hydroxylated-pennogenin saponins from the rhizomes of Paris fargesii and their hemostatic activity - Ling-Ling Yu; Lijin Jiao; Yan-Xi Li; Xu-Hong Li; Shan-Shan Ling; Long-Gao Xiao; Rui-Qi Liu; Wei Ni; Huan Yan; Yunheng Ji; Hai-Yang Liu (Phytochemistry, 2026)

Improving multi-step water demand forecasting performance: Static, past, future, and periodic feature importance - Rui Yuan; Yacan Man; Kuizu Su; Xiao Zhou; Shuming Liu (Journal of Water Process Engineering, 2026)

Macro-micro scales insights into the effect of enrofloxacin on the Fe-C-Anammox system: Performance enhancement, metabolic optimization, and ARGs reduction - Rui Zhong; Jiaqi Lu; Liping Xie; Xiao-Ming Ji; Qi Zhang; Xiao Ma; Wenru Liu; Ying Wang (Journal of Water Process Engineering, 2026)

Effect of enzyme-induced carbonate precipitation on nitrogen loss from sheet erosion on purple soil slopes in the Three Gorges Reservoir area - Hai Xiao; Jiejie Hou; Lun Zhang; Rui Xiang; Deyu Liu; Feng Gao; Yu Ding; Zhenyao Xia (Journal of Water Process Engineering, 2026)

Encoding intrinsic rare-earth dissolution selectivity into deep eutectic solvents via coordination-active functional group design - Zhihan Zhang; Guobiao Li; Zhi Wang; Wanhai Xiao; Yong Lin; Shuping Cheng; Rui Min; Jian Wu; Mingqing Liu; Dong Wang (Journal of Cleaner Production, 2026)

Construction and application of controlled-release preservation pads based on Zein/sodium caseinate-stabilized oregano essential oil Pickering emulsions - Liu Yang; Wenwen Chen; Xinyu Zhang; Rui Xiao; Xue Ding; Zhipeng Jing; Hongyuan Zhang (Food Hydrocolloids, 2026)

Evidence of shallow subsurface ice at Tianwen-1 landing site - Xindong Meng; Ling Zhang; Yi Xu; Giannakis Iraklis; Roberto Bugiolacchi; Jiannan Zhao; Xiaoping Zhang; Qiquan Yang; Rui Chen; Renrui Liu; Xiaoting Xu; Huaqing Cao; et al. (Earth and Planetary Science Letters, 2026)

Monodisperse lutetium-177-labeled poly(lactic acid) microspheres for radioembolization therapy of hepatocellular carcinoma - Qing-Rong Jiang; Ping He; Ling-Yun Guo; Qi-Yi Mo; Xing-Long Zhou; Wei Wang; Zhuang Liu; Rui Xie; Da-Wei Pan; Wen-Jie Zhang; Xiao-Jie Ju; Liang-Yin Chu (Chemical Engineering Journal, 2026)

Multi-Target Water Demand Forecasting with Graph Neural Networks: A Comparative Study - Yacan Man; Xiao Zhou; Rui Yuan; Kuizu Su; Shuming Liu (Water Resources Management, 2026)

Coupled effects of straw return practices on soil microbial functional potential and agricultural productivity in Semi-Arid Region - Rui-Zhi Liu; Xiao-Ya Zhao; Li-Jie Wang; Xing Zhang; Shu‑Ping Hu; Ju‑Lin Gao; Xiao‑Fang Yu; Qinggeer Borjigin (Plant and Soil, 2026)

Zinc finger protein ZNF638 in brown fat deteriorates type 1 diabetes via retinol binding protein 4 - Meiyao Meng; Shuang Liu; Yinzhao Zhong; Jingyi Hu; Lijun Zhu; Jin Qiu; Rui Wang; Yuan Luo; Yingwen Wang; Wenhao Zhou; Guangyu Shan; Zhenyu Du; et al. (Science Bulletin, 2026)

Molecular insight into the structure and formation mechanism of fluid phase in the classical coking theory - Bo Gong; Jie-Ping Wang; Hao-Dong Liu; Rui Guo; Jin-Xiao Dou; Guang-Yue Li; Ying-Hua Liang (Fuel, 2026)

Structural characterization and prebiotic activity of oligosaccharides derived from sesame meal produced by different oil extraction methods - Hui-Fang Duan; Xiao-Rong Chen; Ran Zhang; Yuan-Qing Luo; Chang-Yong Lu; Ke-Qing Liu; Rui-Fu Cui; Run-Yang Zhang; Hua-Min Liu (Food Research International, 2026)

Strain-dependent immunomodulatory activities of lipoteichoic acids from probiotics: From interspecies to intraspecies variation - Yini Liu; Rui Xiao; Min Guo; Jingyu Lu; Jianxin Zhao; Ruojie Zhang; Hao Zhang; Gang Wang; Zipei Zhang (Food Bioscience, 2026)

Using encapsulated essential oils to control food spoilage: encapsulation techniques, release methods, and preservation strategies-A comprehensive review - Rui Xiao; Yin Feng; Xinyu Zhang; Zhipeng Jiang; Wenwen Chen; Xue Ding; Gang Yang; Liu Yang (Food Control, 2026)

Interfacial proton transfer in MOF-functionalized aerogel enabling for selective heavy metal adsorption - Jun-Heng Fu; Baihang Cai; Yeshuang Zhong; Xinru Gong; Shuangfeng Fang; Fei Wang; Yufeng Yan; Rui Dai; Puyuan Liu; Jianye Gao; Ruihan Wang; Ying Cao; et al. (Desalination, 2026)

Structural characterization and anti-hepatic fibrosis effects of a novel polysaccharide from Astragalus complanatus seeds - Zhi-Fan Zhu; Shu-Yao Wang; Xiao-Feng Liu; Na Liu; Dian-Chao Dong; Yan-Chun Qi; Na Li; Nan Wang; Jin Tan; Chang Jia; Rui-Qing Cai; Xiao-Qiang Li; et al. (Carbohydrate Polymers, 2026)

Tree of life and conservation of gymnosperms in China - Chang-Wang Ma; Dan Xie; Hong Du; Kai-Yuan Huang; Yuan-Yuan Feng; Zhou-Rui Wei; Xin-Quan Liu; Cheng-Ru Li; Jing-Jing Sun; Xiao-Xin Wei; Zhi-Heng Wang; Wei-Hua Xu; et al. (Science China Life Sciences, 2026)

Brominated organic compounds in leachate across China: Occurrence and molecular variations - Jing Zheng; Ji-Tao Lv; Yue Sun; Qing-Yu Liu; Qiu-Rui Zhang; Zi-Meng Wang; Xiao-Song He (Water Research, 2026)

Gastrin releasing peptide receptor antagonism in the paraventricular nucleus exerts antihypertensive effects in 2K1C rats - Xiao-Min Wang; Jin-Jun Liu; Yi-Pu Wang; Chao Bai; Abdoulaye Issotina Zibrila; Wen-Jie Xia; Rui-Na Yang; Yu-Ming Kang; Xiao-Jing Yu (Toxicology and Applied Pharmacology, 2026)

Deciphering the effects of cascade reservoirs on phytoplankton communities in a karst river: Importance of super-large reservoirs - Jiang Wu; Xiao-Nan Wu; Xiao-Hui Zhao; Xu Han; En-Hang Liang; Rui An; Jia-Ju Liu; Wei-Ling Sun; Nan Xu; Ting Wang (Journal of Environmental Management, 2026)

Recent progress on Cu-based MOF electrocatalysts for CO2 reduction - Heng-fei Cui; Xiao-jing Liu; Cong Liu; Hao-wen Zhu; Ming-yang Liu; Rui-tang Guo (Fuel, 2026)

Malt endogenous amylase-hydrolyzed nanostarch for anthocyanin encapsulation by nanoprecipitation: Fabrication, characterization and evaluation - Shucheng Liu; Yanyun Lin; Xiaoyan Fu; Qiuyu Xia; Naiyong Xiao; Yang Liu; Rui Hai Liu; Wen Xia (Food Chemistry, 2026)

Synergistic surface plasmon resonance effect of Ag and S-scheme heterojunction in Ag/AgBr/Bi24O31Cl10 towards enhanced enrofloxacin removal: Performance, degradation pathways and synergistic mechanism - Xiao-Ju Wen; Qian Zhan; Hongyu Ye; Jing Xu; Binbin Qian; Rui Luo; Xiankun Wu; Zongtang Liu; Zhenghao Fei; Hai Guo (Environmental Research, 2026)

Efficient bioconversion of corn stover hydrolysates into phenazine-1-carboxylic acid by engineered Pseudomonas chlororaphis for sustainable biopesticide production - Sheng-Jie Yue; Yu-Xuan Li; Kai-Quan Liu; Sheng-Xiao Zhang; Peng Huang; Wei Wang; Xue-Hong Zhang; Xiang-Rui Hao; Lian Jiang; Hong-Bo Hu (Bioresource Technology, 2026)

Release kinetics and bioaccessibility of heavy metal from antifouling paint particles in simulated digestive fluids: An emerging threat to marine biota - Zhen-Liang Li; Ting-Ting Xu; Shan-Shan Yao; Heng-Xiang Li; Shan Liu; Rui Hou; Lang Lin; Zhi-Xin Ni; Qun Xie; Xiao-Ping Huang; Xiang-Rong Xu (Marine Pollution Bulletin, 2025)

Corylifol A ameliorates pancreatic cancer-associated cachexia by targeting TAOK3 in pancreatic cancer cells and targeting TAOK1 in skeletal muscle cells - Ke Yu; Rui-Qin Zhang; Nan Li; Qiong-Sen Wang; Jia Gu; Sai-Yue He; Ying-Qian Wang; Guo-Guo Wang; Xiong-Wen Zhang; Xiao-Dong Guo; Xuan Liu (Toxicology and Applied Pharmacology, 2025)

Mitigation performance and mechanism of the EICP for the erosion resistance of purple soil to concentrated flow in the Three Gorges Reservoir area - Deyu Liu; Ruidong Yang; Lun Zhang; Zhenyao Xia; Zhiyong Zhang; Rui Xiang; Feng Gao; Wenqi Zhang; Yu Ding; Hongqiang Shi; Hai Xiao (Soil and Tillage Research, 2025)

Value decomposition reinforcement learning-based formation control for multi-USVs with incomplete information - Rui Xiao; Chun Liu; Hongtian Chen; Liang Xu; Youmin Zhang (Ocean Engineering, 2025)

Whole-genome resequencing unveils the phylogeographic coevolution of Oncomelania hupensis with Yangtze River dynamics in China - Lei Duan; Fang Luo; Qin Liu; Shen Chen; Xia Tian; Wen-Wen Lv; Lu He; Zi-Rui Ren; Jing Xu; Xiao-Nong Zhou; Shi-Zhu Li; Shan Lv; et al. (Molecular Phylogenetics and Evolution, 2025)

Tailored SO2 capture in multivariate UiO-66(Zr) MOFs: Experimental insights and theoretical mechanisms - Zai-Dong Shao; Peng Wu; Fang Liu; Qi-Jun Zhang; Chao-Yang Guo; Rui-Sang Liu; Jiang Lu; Xiao-Meng Ren; Yu-Ming Zheng (Journal of Environmental Chemical Engineering, 2025)

Multi-task deep learning utilizing VOCs detected by HS-GC-IMS for geographical origin tracing and adulteration detection of turmeric powder - Xiao Han; Tong Wu; Shixin Cen; Jie Yong; Xinrang Tian; Xinyi Li; Rui Sun; Minghui Liu; Heshui Yu; Zheng Li (Food Control, 2025)

Quantifying nitrogen loss responses to seasonal deluges and droughts: A modeling study in a subtropical agro-forest catchment, upper Yangtze River - Wei Zhang; Xunhua Zheng; Siqi Li; Chunyan Liu; Zhisheng Yao; Shenghui Han; Rui Wang; Kai Wang; Bo Zhu; Minghua Zhou; Xiao Chen; Yong Li (Ecohydrology & Hydrobiology, 2025)

Dual-mechanism defect engineering of multi-enzyme embedded ZIF-8 for efficient anthocyanin extraction from black rice - Mengyuan Cao; Bicong Wang; Yuchao Deng; Da-Wei Pan; Xiao-Jie Ju; Rui Xie; Zhuang Liu; Xing-Long Zhou; Mao-Jie Zhang; Wei Wang; Liang-Yin Chu (Chemical Engineering Journal, 2025)

Multiomics integration unveils rapeseed adaptative responses to potassium deprivation: a synergy of morpho-physiological, transcriptomic, and metabolic reprogramming - Rui Cui; Si-si Sun; Min-nan Pei; Ying Liu; Yu-shan Xiao; Ying-na Feng; Ting Zhou; Ying-peng Hua (Plant and Soil, 2025)

IFNGR1, IRF8 genetic polymorphisms modulate the susceptibility of non-tuberculous mycobacteria pulmonary disease and influence the patients’ treatment outcomes and immune status - Li-ping Cheng; Zhi-bin Liu; Lei Wang; Jie Cao; Qing-rong Qu; Hai Lou; Xiao-na Shen; Juan Yang; Yuanyuan Yu; Rui Juan Zheng; Wei Sha; Qin Sun (Inflammation Research, 2025)

Metformin suppresses gammadelta T17 cell differentiation alleviating DSS-induced colitis - Mingzhong Sun; Hongli Liu; Huixiang Ju; Hongmei Chen; Rui Yang; Dongmei Yan; Langping Shen; Aiting Cai; Yaru Zhi; Lihua Xiao; Qinfang Tang; Yungang Wang (Immunologic Research, 2025)

Integrated multi-omics analysis of UL16-binding protein 2 as a prognostic and immunotherapy biomarker for colorectal cancer - Xin-Yang Qu; Yong Xu; Rui-Min Wu; Gao-Chun Xiao; Ping-Feng Wang; Jin Xie; Xu-Sheng Liu (Functional & Integrative Genomics, 2025)

Zircon U-Pb Ages and Sr-Nd-Hf Isotopes Geochemistry of I-Type Granites in the Jiangda-Weixi Region, Eastern Tibet: Implications for the Tectonic Evolution of the Paleo-Tethyan Orogen - Rui Gao; Tao Wu; Andrew C. Kerr; Han Liu; Long Xiao; Wan Huang (Journal of Earth Science, 2025)

The endogenous fungus Colletotrichum endophyticum from Korean epimedium Nakai promoted the growth of the model plant Arabidopsis thaliana - Jiang Rui; Zou Mingxuan; Liu Yucui; Zhuang Xin; Qi Xiaoting; Shi Fang; Liu Hanning; Xiao Jinglei (Archives of Microbiology, 2025)

Application of ambient noise tomography to coastal granite islands: A case study of Wuzhizhou Island in Hainan, China - Cheng Huang; Sheng Liu; Jun-Qiao Long; Chang-Rong Zhang; Bo Xiao; Da-Cheng Wang; Cheng-Long Wei; Rui Wang; Li Yan; Xuan Hu; Zhuo Xin; Xiu-Ji Meng; et al. (Applied Geophysics, 2025)

Sediment amplifies organic matter cycling and nutrients feedback in eutrophic lake zones - Junfeng Xing; Yuping Zhou; Ding He; Fen Guo; Penghui Li; Yuan Zhang; Rui Lv; Runze Xue; Changqing Liu; Yihua Xiao (Water Research, 2025)

The correlation between temperature change and lung cancer risk altered by air particulate pollutants: Nationwide analysis - Shenxuan Zhou; Yanchi Wang; Zhenyu Li; Yiran Liu; Rui Zhu; Bo Liu; Jiacan Yuan; Mingna Wu; Jing Xiao; Hanpeng Lai; Anhui Ning; Yan Zhang; et al. (Journal of Cleaner Production, 2025)

Morphology and nutrient content of bamboo rhizomes: Responses to enclosure succession in a Phyllostachys edulis forest in Wuyi Mountains, China - Xing Cai; Rui Cheng; Zhenhua Chen; Jiannan Lin; Min Wu; Jiaying Liu; Jihong Xiao; Yuchen Lin; Lingyan Chen; Yirong Zhang; Jundong Rong; Tianyou He; et al. (Forest Ecology and Management, 2025)

Hierarchically structured Fe-Cu-Ni-O@Al2O3-ZrO2 monolithic oxygen carrier for efficient chemical looping hydrogen production - Zixiang Gao; Tao Li; Suxia Ma; Haiyu Liu; Rui Xiao (Chemical Engineering Journal, 2025)

An electrochemically switchable “Cu−S” coordination of copper(II)-doped conjugated polymer for electrochromic energy-saving smart windows - Xue-Song Liu; Rui-An Liu; Baige Yang; Yuxin Qu; Weiran Zhang; Sean Xiao-An Zhang; Yu-Mo Zhang (Chemical Engineering Journal, 2025)

Phytosphingosine suppresses gastric cancer through SFRP4/β-catenin axis-mediated Wnt signaling pathway inhibition - Yanchen Liu; Rui Guo; Chi Xue; Xinwei Zhang; Fanghao Xiao; Xiangxuan Zhao; Zhi Zhu; Kai Li (Chemico-Biological Interactions, 2025)

Vitamin E alleviates ammonia‑nitrogen and hypoxia co-exposure-induced intestinal damage in grass carp (Ctenopharyngodon idella) by modulating mitochondrial function, cellular autophagy and apoptosis - Rui Su; Ke Yao; Xiao-Qiu Zhou; Lin Feng; Wei-Dan Jiang; Yang Liu; Yao-Bin Ma; Hong-Mei Ren; Xiao-Wan Jin; Pei Wu (Aquaculture, 2025)

Synergistic quorum quenching to the diffusible signal factor and AHLs mediated quorum sensing in Thiothrix controlling filamentous sludge bulking - Rui Liu; Lin Feng; Jie Li; Zhuo-Li Yan; Jian-Hong He; Yue Zhi; Xiao-Wei Xu; Peng Yan; You-Peng Chen (Journal of Environmental Chemical Engineering, 2025)

Adaptive responses and molecular mechanisms of Lactiplantibacillus plantarum to citric acid stress - Han Xie; Wei Zhang; Cong-Rong Shi; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

Impact of amplicon length on the identification of edible oils based on real-time PCR - Kai Chen; Bin Xiao; JianZhi Luo; XueWei Yuan; Juan Zhang; Songxue Wang; Rui Zhang; Nan Wang; LiQiang Liu; AiKe Li; Ailiang Chen (Food Control, 2025)

Halogen-sulfur synergy in benzodithiophene-benzodithienedione conjugated polymers: Molecular design of high-performance photoelectrodes for metal anti-corrosion - Rui Ding; Jin-ying Li; Yi-wen Zhang; Hao-han Cao; Xiao Liu; Yu-han Wang; Ming-di Lei; Yu-lin Zhang; An-lan Ji; Yu-chen Zhang; Jie Liu; Tai-jiang Gui; et al. (Chemical Engineering Journal, 2025)

Differences in the home-field effects of litter decomposition modulate changes in soil microbial nutrient limitations: insights from eco-enzyme stoichiometry - Yongxia Meng; Peng Li; Lie Xiao; Jialiang Liu; Chaoya Zhang; Shutong Yang; Xiaoming Zhang; Yunqi Wang; Tian Wang; Rui Wang (CATENA, 2025)

Interactions and feedback mechanisms in oasis wetland hydrology–soil–vegetation systems, northwestern China - Bing Liu; Ying Zhao; Arash Malekian; Xiao Wang; Wenzhi Zhao; Maliheh Behrang Manesh; Bin Wang; Changkun Yang; Weihao Sun; Wen Li; Pouyan Dehghan Rahimabadi; Yangyang Meng; et al. (CATENA, 2025)

HMGA2 Attenuates Tendon Stem/Progenitor Cell Senescence Via PI3K/AKT-Mediated Mitophagy Activation and SASP Suppression - Hao Wang; Guang-Chun Dai; Yu-Cheng Gao; Xiao-Yu Liu; Pan-Pan Lu; Mu-Min Cao; Ren-Wang Sheng; Liu Shi; Zhang Cheng; Ying-Juan Li; Yun-Feng Rui (Stem Cell Reviews and Reports, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

Silicon supplementation via carriers to enhance diatom competition with cyanobacterial blooms and remediate eutrophic waters - Rui Zhou; Bang Xiao; Li Zhao; Yangyang Tang; Wei Yang; Huazu Liu; Xiangdong Zhang; Chaowei Yuan; Xinqi Wang; Xizi Long; Qiang He; Wei Li (Water Research, 2025)

Cellulose nanocrystals for functional food packaging: Enhancing performance and enabling intelligence - Xinxin Yan; Ziwen Li; Wenhui Cheng; Rui Chen; Jun Liu; Junlong Song; Huining Xiao; Haishun Du; Jiaqi Guo (Trends in Food Science & Technology, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Development and characterization of a high-resolution, high-sensitivity collinear resonance ionization spectroscopy system - Han-Rui Hu; Yang-Fan Guo; Xiao-Fei Yang; Zhou Yan; Wen-Cong Mei; Shao-Jie Chen; Yin-Shen Liu; Peng Zhang; Shi-Wei Bai; Dong-Yang Chen; Yong-Chao Liu; Shu-Jing Wang; et al. (Science Bulletin, 2025)

Quaternary sedimentary evolution and source apportionment in the northwestern South China Sea: Evidence from geochemical and zircon U-Pb data - Peng-Fei Xiong; Shu Jiang; Cong Cheng; Kai Zhang; Xiao-Yu Fang; Tao Jiang; Jia-Le Fu; Hong-Ji Liu; Xin-Rui Zhou; Xu-Shen Li (Quaternary Science Reviews, 2025)

Cyclic organic matter accumulation in a plateau salinized lacustrine basin: Major controls and hydrocarbon significance - Peng Pang; Di Xiao; Kunyu Wu; Songtao Wu; Haoting Xing; Ying Xiong; Rui Liu; Xiucheng Tan (Marine and Petroleum Geology, 2025)

Associations Between Pre- and Post-Diagnosis Dietary Inflammatory Patterns and Ovarian Cancer Survival: Results From the Ovarian Cancer Follow-Up Study - Jia-Xin Liu; Rui-Han Bao; Meng Luan; Chuan Liu; Lang Wu; Fang-Hua Liu; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Qian Xiao; Dong-Hui Huang; Xiao-Ying Li; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Electrocatalytic removal of nitrate by non-noble Fe3C/Cu: Property, mechanism, and practical water treatment performance - Yang Guo; Hao Chen; Houfen Li; Jiming Liu; Xiao Zhang; Aijuan Zhou; Xiuping Yue; Rui Li; Jindong Wang; Pengxiao Liu; Hongtao Yu; Xu Zhao (Journal of Hazardous Materials, 2025)

Genome-wide association and epidemiological evidence linking air pollution to aging mechanisms - Xiao-Yu Liu; Dong Peng; Xu-Rui Liu; Yuan-Hui Sheng; Jun-Nan Zhao; Rong-Bin Xu; Dan Zhang; Bo Chen (Journal of Hazardous Materials, 2025)

Recovery of rare earth elements from sediments affected by mining activities - De-Xiang Xu; Xuan-Pu Cheng; Cui-Ling Huang; Xiao-Rui Liu; Can-Die Xie; Rong-Liang Qiu; Chang Liu; Mei-Na Guo; Jean-Louis Morel; Wen-Shen Liu; Ye-Tao Tang (Journal of Hazardous Materials, 2025)

Targeted and non-targeted analyses reveal trophic biomagnification of rubber-derived chemicals in an estuarine food web near China's largest rubber production region - Yuan Liu; Jia-Ming Zhou; Nian-Nian Wu; Shan Liu; Xiao-Liang Liao; Haijiang Wu; Lin Zhu; Heng-Xiang Li; Lang Lin; Rui Hou; Zhi-Hua Li; Xiang-Rong Xu; et al. (Journal of Hazardous Materials, 2025)

Unlocking the bioremediation potential of adapted Desulfovibrio desulfuricans in acidic low-temperature U-contaminated groundwater - Lei Zhou; Nan Bai; Rui Xiao; Zhendong Yang; Guoping Jiang; Huaqun Yin; Yujie Wang; Liangzhi Li; Delong Meng; Zhenghua Liu (Journal of Environmental Sciences, 2025)

Computer-aided precise hapten design strategy for the monospecific detection of altrenogest: Experimental validation and analysis of the molecular recognition mechanism - Hongfei Yang; Hao Wen; Yu Si; Mingyue Ding; Yiting Liu; Ziyan Yu; Linwei Zhang; Jiacan Wang; Xiaoming Pan; Shiyun Han; Yiting Wang; Shixiang Wu; et al. (Food Chemistry, 2025)

Multilevel surface enhancement of primary and secondary particles in cobalt-free high-nickel cathode material through Mo and W staged doping - Dandan Sun; Jiyuan Jian; Xin Zhang; Shuang Lin; Yixuan Qiao; Tao Wu; Xianhui Zhao; Rui Xiao; Ziwei Liu; Hua Huo; Pengjian Zuo; Yulin Ma; et al. (Chemical Engineering Journal, 2025)

Gradient distribution of trap states in polymer dielectrics induced by electric field for enhanced insulation properties - Bing Xia; Ming-Xiao Zhu; Zhi-Hao Xing; Rui Liu; Jie-Rui Ren; Xue-Kai Xu (Chemical Engineering Journal, 2025)

Development of a new onset of film boiling model within the fouling layer - Xiaowen Wang; Maolong Liu; Rui Zhang; Tenglong Cong; Yao Xiao; Hanyang Gu (Annals of Nuclear Energy, 2025)

Enhancing the anti-inflammatory efficacy of polysaccharides through processing techniques: a case study on Atractylodes macrocephala - Hong-Da Xuan; Sheng-Nan Shen; Chun-Jin Fu; Jie Zhou; Rui-Xing Chen; Jun-Zhe Zhang; Xiao-Xia Liu; Feng-Qin Li; Yi-Fan Zhao; Dong Zhang; Hai-Ning Lyu; Fang Wang (Natural Product Research, 2025)

Maximizing membrane antifouling potential: The impact of fluoride positioning in multifunctional designs - Caihong Liu; Rui Gao; Xiao Wang; Andreia F. Faria; Liu Yang; Bin Zhang; Qiang He (Water Research, 2025)

A green approach to CO2 capture using fly ash-based catalysts: Performance and mechanistic insights - Rui Zhang; Lianghong Zhou; Ting Li; Yingjie Niu; Haonan Liu; Ruqi Xiao; Chao’en Li; Francesco Barzagli (Fuel, 2025)

l-theanine alleviates ulcerative colitis by repairing the intestinal barrier through regulating the gut microbiota and associated short-chain fatty acids - Aoxiang Liu; Bin Wang; Minming Wang; Rui Tang; Wei Xu; Wenjun Xiao (Food and Chemical Toxicology, 2025)

Modelling forest-atmosphere exchanges of carbon and water using an improved hydro-biogeochemical model in subtropical and temperate monsoon climates - Wei Zhang; Xunhua Zheng; Siqi Li; Shenghui Han; Chunyan Liu; Zhisheng Yao; Rui Wang; Kai Wang; Xiao Chen; Guirui Yu; Zhi Chen; Jiabing Wu; et al. (Ecological Modelling, 2025)

A stable all-solid-state lithium metal battery achieved by optimizing the cathode-electrolyte interface through perovskite-coating-stabilized single crystal LiNi0.9Co0.05Mn0.05O2 cathode - Cheng Liu; Wenjin Li; Kaiyuan Deng; Puxi An; Rui Wang; Beisen Chen; Qingmei Xiao; Jiatao Wu; Lei Yao; Guangliang Gary Liu (Chemical Engineering Journal, 2025)

Recyclable flame retardant, luminescent, and transparent thermoplastic polyurethanes: applications in light conversion films for flexible solar cells - Li-Wei Su; Ming-Hao Liu; Yang Jing; Peng-Yu Huang; Bo Jiang; Rui-Guang Xing; Xin Ge; Ya-Hui Li; Jin-Xiao Bao; Gao-Fei Pan (Chemical Engineering Journal, 2025)

Electroacupuncture may alleviate inflammatory pain by downregulating the expression of P2Y14 receptor in the primary somatosensory cortex - Shuai Hou; Cui-Yuan Chen; Rui-Zhu Zhou; Liu-Xuan He; Xiao-Xiao Zhao; Sha-Sha Chen; Sha Yang; Hai-Yan Yin; Shu-Guang Yu (Purinergic Signalling, 2025)

Submersion deteriorates the mechanical properties of Cynodon dactylon root and alters its failure type - Deyu Liu; Zhubao Chen; Lun Zhang; Zhenyao Xia; Rui Xiang; Feng Gao; Qianheng Zhang; Ruidong Yang; Yu Ding; Yueshu Yang; Hai Xiao (Plant and Soil, 2025)

Droplet-vitrification for cassava shoot tip cryopreservation: protocol optimization and histological observation for rapid shoot tip recovery - Min-Rui Wang; Xiu-Qing Miao; Yun-Liu Fu; Lang-Xin Chen; Xiao-Bing Wang; Qing-Quan Yang; Li Xu; Zhiying Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Upregulation of circRNA_0002286 protects against brain ischemia/reperfusion injury after remote ischemic postconditioning via microRNA-124-3p/VLCAD axis - Chun-Yan Li; Wei Ma; Jin-Wei Yang; Wei Liu; Kuang-Pin Liu; Xiao-Hua Weng; Shou-Rui Niu; Shen Li; Jian-Hui Guo; Li-Yan Li (Journal of Molecular Histology, 2025)

From farm to table: application and challenges of yeast in the growth, preservation and fermentation of fruit - Xiaohua Ma; Guangyi Yang; Liangfu Zhou; Rui Xiao; Yanlin Liu; Xixi Zhao (Trends in Food Science & Technology, 2025)

Sesquiterpenoids isolated from the root bark of Lycium chinense - Xiao-xia Wang; Qian Liu; Ning Wang; Rui-li Zhang; Xiao Li; Peng-yu Zhuang; Hang Liu; Liang-dan Sun; Yang Jin (Phytochemistry, 2025)

Evolution and functional characterization of a biosynthetic gene cluster for saponin biosynthesis in Sapindaceae - Yingxiao Mai; Huimin Hu; Wenjuan Ji; Yaxuan Xiao; Hong Zhou; Zaohai Zeng; Wenshu Lv; Xingling Su; Jiakun Zheng; Jing Xu; Yanwei Hao; Zhenhua Liu; et al. (Molecular Plant, 2025)

Flow behavior and retarding mechanism of LNAPL pollutants in capillary zone - Rui Zuo; Chenxi Huang; Kexue Han; Donghui Xu; Xiao Zhao; Jiawei Liu; Ziyi Wu; Jinsheng Wang (Journal of Hydrology, 2025)

Not for nothing, microplastics can (potentially) reduce the risk of mosquito-to-human transmission of arboviruses - Jian-hang Li; Xiao-hui Liu; He-ting Gao; Guo-rui Liang; Teng Zhao; Chun-xiao Li (Journal of Hazardous Materials, 2025)

Bioactives derived from egg by-products: Preparation, health benefits, and high-value-added applications - Yue Huang; Rui Chuang; Mengzhuo Liu; Huajiang Zhang; Hanyu Li; Lina Xu; Ning Xia; Chaogeng Xiao; Ahmed M. Rayan; Mohamed Ghamry (Food Chemistry, 2025)

Mechanistic applications of low-temperature plasma in starch-based biopolymer film: A review - Yanli Guo; Mengzhuo Liu; Rui Chuang; Huajiang Zhang; Hanyu Li; Lina Xu; Ning Xia; Chaogeng Xiao; Ahmed M. Rayan; Mohamed Ghamry (Food Chemistry, 2025)

Single and joint associations of exposure to polycyclic aromatic hydrocarbons with hypertensive disorders of pregnancy: A nested case-control study - Rui Yu; Cheng Chen; Mingyu Deng; Nian Wu; Yanling Xiao; Songlin An; Lin Tao; Xingting Zheng; Jing Yang; Zhongmei Hu; Pei Xu; Xingyan Liu; et al. (Environmental Pollution, 2025)

Rising disparities in grain self-sufficiency across China: Provincial divergence amidst overall national improvement - Xiaoyu Yu; Rui Xiao; Zhonghao Zhang; Feng Zhou; Fei Mo; Zhenci Xu; Feng Tian; Zhi Gao; Yansheng Li; Peng Zhu; Kailiang Yu; Lumeng Liu; et al. (Environmental Impact Assessment Review, 2025)

Spatiotemporal prediction of ionospheric TEC based on denoising wavelet transform convolution - Rui Zhou; Yanxiong Wu; Jianxian Cai; Haijun Liu; Huijun Le; Jian Xiao; Yan Ma (GPS Solutions, 2025)

Suppression of NRF2 by photodynamic action to enhance bortezomib-triggered DNA damage for synergistic colorectal cancer therapy - Liu-Gen Li; Hao Chen; Ting-Ting Yu; Rui-Lin Liu; Cunqing Kong; Fan Leng; Rong-Cheng Xiao; Yao-Hua Lu; Ning Han; Jun Hu; Yuan-Jian Hui; Tong-Fei Li (Journal of Photochemistry and Photobiology B: Biology, 2025)

The alleviating effects of tryptophan metabolite indole-3-propionic acid on glycolipid metabolism disorders and cognitive dysfunction in obese mice - Chen Ding; Ying He; Zhitong Wang; Xiao Xiao; Yihang Zhao; Yuhao Wang; Xia Chen; Rui Guo; Yongbo She; Bin Wang; Zhigang Liu (Food Bioscience, 2025)

Construction of linear causal-regulated and autocatalysis-driven DNA circuits for highly sensitive and specific detection of Salmonella Typhimurium - Xinru Ren; Weiqing Sun; Bowen Li; Yijing Xiao; Xudong Yue; Meili Yang; Qing-ao Pang; Rui Zhu; Zhiqiang Guo; Haiping Zhang; Yu Wang; Su Liu; et al. (Food Control, 2025)

Laboratory investigation of sandstone joints and strata on TBM performance using a tunnelling test platform - Wei-Qiang Xie; Xiao-Li Liu; Shao-Hui Tang; Qi Zhang; Da-Rui Ren; Qing Ma (Engineering Geology, 2025)

Highly selective and reversible adsorption of trace gaseous ammonia by a stable nanoporous carboxylic acid-functionalized silica aerogel - Zai-Dong Shao; Ting-Ting Hu; J. Paul Chen; Qi-Jun Zhang; Peng Wu; Rui-Sang Liu; Jiang Lu; Xiao-Meng Ren; Yu-Ming Zheng (Chemical Engineering Journal, 2025)

Injectable dual-network hydrogel for phototherapy and immunomodulation in the treatment of MRSA-infected and diabetic wound - Shengfei Bao; Aodi Jiang; Li Peng; Fuying Liao; Ga Liu; Li Chen; Peng Zhou; Zhen Zhu; Rui L. Reis; Subhas C. Kundu; Lian Duan; Bo Xiao; et al. (Chemical Engineering Journal, 2025)

Ensemble framework for multistep carbon emission prediction: an improved Bi-LSTM model based on the Bayesian optimization algorithm and two-stage decomposition - Qi Song; Yu-Long Bai; Rui Wang; Xiao-Xin Yue; Wen-Hui Liu (Stochastic Environmental Research and Risk Assessment, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Ecological security and structural optimization of land space in the Pearl River Delta Urban Agglomeration: an approach based on the footprint family - Cong Huang; Jun Liu; Hanyu Yin; Zhonghao Zhang; Wei Cao; Wenfang Tan; Xufeng Fei; Chen Xu; Lumeng Liu; Jiali Chen; Kai Li; Rui Xiao (Environment, Development and Sustainability, 2025)

Study on seeding delay time and lag distance of automatic section control system for maize seeder - Lin Ling; Hanqing Li; Yuejin Xiao; Weiqiang Fu; Jianjun Dong; Liwei Li; Rui Liu; Xinguang Huang; Guangwei Wu; Zhijun Meng; Bingxin Yan (Computers and Electronics in Agriculture, 2025)

Flood complexity and rising exposure risk in High Mountain Asia under climate change - Yuanyuan Bai; Dongfeng Li; Sonam Wangchuk; Albert Kettner; Yi Zhao; Rui Deng; Yong Liu; Cunde Xiao; Jinren Ni; Peng Cui (Science Bulletin, 2025)

Biochar-algae microspheres based on sodium alginate for the highly efficient adsorption of malachite green dye: Kinetics, isotherms, and mechanism of adsorption - Wei-Zhe Wu; Rui Li; Zhi-Qian-Li Ma; Chun-Xiao Liu; Wen-Ting Zhao (Journal of Contaminant Hydrology, 2025)

Glucose-driven synthesis of N-doped porous carbon from sludge for CO2 removal in biomass syngas - Jinpeng Zhai; Zhenjiang Wang; Jia Ouyang; Beichen Xue; Chao Liu; Rui Xiao (Chemical Engineering Journal, 2025)

Process modeling guided start-up and stable operation of a pilot-scale mainstream partial denitrification-anammox system - Min Xu; Wenbo Chai; Wanlu Zhu; Yuyan Zhang; Rui Xiao; Changzhi Wang; Wenlong Liu; Huijie Lu (Chemical Engineering Journal, 2025)

Preparation and bioactivities of low-molecular weight fucoidans and fuco-oligosaccharides: A review - Hai-Di Liu; Dong-Yue Ma; Shan-Rui Shi; Shi-Lin Song; Wen-Lan Li; Xiao-Hui Qi; Shou-Dong Guo (Carbohydrate Polymers, 2025)

Energy Release Efficiency and Mechanisms of Mining-Induced High-Energy Earthquakes in China - Zi-Bo Wang; Rui-Feng Liu; Ting-Ting Wang; Yi-Xiao Zhang; Xiao Ren (Rock Mechanics and Rock Engineering, 2025)

Root exudates drive root avoidance of maize in response to neighboring wheat - Xiao-Tong Yin; Fang-Fang Zhang; Rui-Peng Yu; Na Liu; Wei-Ping Zhang; Dario Fornara; Liesje Mommer; Xue-Xian Li; Long Li (Plant and Soil, 2025)

Effects of earthworms on the performance of Lolium multiflorum, soil properties and microbial communities in its root-zone soil under cadmium stress - Xiao-Gai Wang; Bing-Nan Zhao; Zi-Yang Xie; Zhi-Huan Chen; Zhi-Hang Liu; Xiao Chen; Bo-Yang Lu; Jia-Ning Liu; Rui Zhang; Chao Si (Plant and Soil, 2025)

3D DNA walkers integrated with self-reporting MOFs: Pioneering ratiometric electrochemical sensing for Staphylococcus aureus - Xianzhu Meng; Rui Ma; Xiao Luo; Yang Liu; Xiaoli Yin; Huiwen Gu; Ying Chen (Analytica Chimica Acta, 2025)

CORBES: Radiation belt survey with international small satellite constellation - Ji Wu; Li Deng; Jaan Praks; Marius Anger; Philipp Oleynik; Wojciech Hajdas; Jin-Dong Wang; Shen-Yi Zhang; Bin Zhou; Li Zeng; Jinbin Cao; David Fischer; et al. (Advances in Space Research, 2025)

Petrogenesis of Early Permian within-plate-type gabbros in the Western Qiangtang Terrane, Tibet: partial melting of lithospheric mantle metasomatized by subducted oceanic sediments on the northern margin of the Gondwana - Xiao-Rui Fan; Yun-Chuan Zeng; Ji-Feng Xu; Feng Huang; Ming-Jian Li; Xi-Jun Liu; Hong-Xia Yu; Jing Hu (International Geology Review, 2025)

Effect and mechanism of the moisture content on the kinetic retardation of LNAPL pollutant migration by the capillary zone - Kexue Han; Rui Zuo; Ronggao Qin; Donghui Xu; Xiao Zhao; Minghao Pan; Jiawei Liu; Yunxiang Xu; Jinsheng Wang (Journal of Hazardous Materials, 2025)

Enhanced removal of lead complexes using phosphide-modified nanoscale zero-valent iron: The boosting impact of the iron cycle - Rui Li; Xinya Liu; Xiao Ge; Xiaozhi Wang (Journal of Cleaner Production, 2025)

Lactic acid bacteria-mediated transformation of black tea extract: Insights into metabolite profile and sensory characteristics - Zhi-Peng Cheng; Yao-Zeng Zhang; Zhong-Zheng Guan; Rui-shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (Food Bioscience, 2025)

Urinary concentrations of phthalate metabolites and the survival of high-grade serous ovarian cancer with advanced stage - Wen-Rui Zheng; Yi-Zi Li; Jin Xu; Ke-Xin Liu; Fang-Hua Liu; Wei-Yi Xing; Jia-Xin Liu; Lang Wu; Xiao-Ying Li; Dong-Hui Huang; Ting-Ting Gong; Qi-Jun Wu (Environmental Pollution, 2025)

Extending PANI molecular chains into pores of hierarchical MIL-101 as flexible electrodes for supercapacitor applications - Jinyao Chi; Shiyu Gu; Rui Shi; Runze Zhao; Xufei Liu; Qi Zhang; Qingliang Lv; Zhenyu Xiao; Lei Wang (Chemical Engineering Journal, 2025)

Metal-organic coordinated self-assembled nanomedicine for enhanced cuproptosis-mediated chemo-photo-chemodynamic synergistic therapy of non-small cell lung cancer - Ru-Gui Liu; Rui-Rui Zhao; Zi-Wei Yu; Feng-Juan Liu; Chun-Zhao Liu; Xiao Wu (Chemical Engineering Journal, 2025)

Dynamic characterization of the changes in intestinal fungi and fecal metabolites during the reproductive cycle of sows - Jin-Wen Su; Xin-Wen Hou; Shuo Liu; Yu Chen; Ji-Xin Zhao; Xiao-Xuan Zhang; Hong-Bo Ni; He Ma; Rui Liu (Veterinary Research Communications, 2025)

Establishment of cell suspension culture and genetic transformation systems for production of bioactive metabolites of medicinal plant Artemisia argyi Lévl. et Vant - Yukun Li; Sainan Peng; Jingyi Zhang; Chuang Xiao; Rui Zhao; Yuhuan Miao; Dahui Liu (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Swertiamarin relieves radiation-induced intestinal injury by limiting DNA damage - Zhe Zhao; Dan He; Jinyu Wang; Yu Xiao; Lixin Gong; Can Tang; Haibo Peng; Xuemei Qiu; Rui Liu; Tao Zhang; Jingyi Li (Molecular and Cellular Biochemistry, 2025)

The truncated AXIN1 isoform promotes hepatocellular carcinoma metastasis through SRSF9-mediated exon 9 skipping - Qian-qian Zhang; Ying-shuang Miao; Jun-yi Hu; Rui-xuan Liu; Yue-xiao Hu; Feng Wang (Molecular and Cellular Biochemistry, 2025)

Sand Production and Critical Rate in Stress-Sensitive Unconsolidated Sandstone: An Experimental Study - Xiao-Hua Tan; Rui Wang; Xiao-Jun Zhou; Yao Zhu; Cai-Shen Li; Bo Cao; Zhi Yang; Hao Chen; Bao-Quan Wen; Liu Tang; Huan-Yu Ran (Geotechnical and Geological Engineering, 2025)

Bacillus safensis M01 reversed the inflammatory injury of mice jejunum caused by enterotoxigenic Escherichia coli K88 - Xin-Wen Hou; Jinxin Meng; Xiao-Tong Chen; Ji-Xin Zhao; Kai-Meng Shang; Yong-Jie Wei; Rui Liu (Archives of Microbiology, 2025)

Research progress of non-coding RNA regulating the role of PANoptosis in diabetes mellitus and its complications - Guangyu Han; Kaibo Hu; Tianfeng Luo; Wenting Wang; Deju Zhang; Liu Ouyang; Xiao Liu; Jianping Liu; Yuting Wu; Jianqi Liang; Jitao Ling; Yixuan Chen; et al. (Apoptosis, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Characterization of the gut microbiota in drug abuse: prediction, prevention, and personalized medicine to benefit affected populations - Xin Wang; Ya-Jie Yu; Cai Liao; Xiao-Ru Liu; Rui Yu; Yun Wang (EPMA Journal, 2025)

Combined uranium-series and trace elements analysis in cold seep bivalves: possibility in hundred-year-scale reconstruction of deep-sea temperature and acidification - Chaofeng Cai; Jing-Chun Feng; Guozhong Wu; Rui Hou; Xiao Chen; Jinyi Liu; Xiaochun Zhang; Si Zhang (Frontiers in Marine Science, 2025)
Despite the pivotal role of deep-sea in the global climate system, effective technology is still limited for reconstructing the key parameters of deep-sea environment such as temperature and acidification, especially at the hundred-year scale. In this study, we assessed the robustness and reliability of using bivalve shells in reconstructing cold seep environments. A significant heterogeneous distribution of trace elements was observed in the shells of clams and mussels from Formosa and Haima cold seeps even if they were collected from the same site, which was caused mainly by the environmental variables rather than physiological characters. The results of the principal component analysis revealed different trace elements ratios in the shell were associated with seepage. In particular, Sr/Ca was identified as a reliable proxy for temperature reconstruction, which performed better than oxygen isotopes. Na/Ca and U/Ca are potential proxies for cold seep acidification, but further validation is needed before their practical application. The age bias using the U-series dating method resulted from high 232 Th and low initial 230 Th/ 232 Th rather than from alpha-recoil processes. The median ages assigned to mussels from the F and Haima cold seeps were 229.5 and 323.5 years, respectively. The lifespan of clams from the Haima cold seep was too short to date accurately. We proposed to conduct feasibility verification and error correction to enhance the method performance in reconstructing the hundred-year evolution of cold seep environment in the South China Sea.

IFN-mediated lncRNA-ISL promotes SVV infection through G1P3 - Chen Wang; Yijun Yang; Xiwang Yang; Qiyue Yang; Rui Liu; Wenting Li; Xiao Liu (Veterinary Microbiology, 2025)

Centrifuge test study on the influence mechanism of anchor cable installation on the seismic response of pile‒anchor structures - Yu Wang; Tong Zheng; Rui Sun; Qiangqiang Sun; Xiao Long; Hongshuai Liu; Wenhao Qi (Soil Dynamics and Earthquake Engineering, 2025)

Pre-industrial Common Era temperature fluctuations in South China inferred based upon bacterial tetraether lipids from Lake Poyang - Rui Miao; Hong Yang; Qin Leng; Yuwei Chen; Shangbin Xiao; Xiaoke Qiang; Xiangzhong Li; Yuan Yao; Zenghao Zhao; Hongxuan Lu; Zhonghui Liu; Huanye Wang; et al. (Quaternary Science Reviews, 2025)

Numerical and experimental studies on the hydrodynamic performance of a composite cylindrical perforated-wall caisson breakwater - Zi-bo Xia; Xin-yu Wang; Xiao Liu; Rui-jia Jin; Bao-lei Geng; Yong Liu (Ocean Engineering, 2025)

A small RNA effector conserved in herbivore insects suppresses host plant defense by cross-kingdom gene silencing - Wen-Hao Han; Shun-Xia Ji; Feng-Bin Zhang; Hong-Da Song; Jun-Xia Wang; Xiao-Ping Fan; Rui Xie; Shu-Sheng Liu; Xiao-Wei Wang (Molecular Plant, 2025)

Co-exposure to polystyrene nanoplastics and F-53B induces vascular endothelial cell pyroptosis through the NF-κB/NLRP3 pathway - Junli Lv; Zhenzhen Tan; Ziwen An; Rui Xu; Huaxing Zhang; Mingmei Guo; Fang Xiao; Mengwei Zhao; Yi Guo; Yi Liu; Xuehui Liu; Jingtao Ma; et al. (Journal of Hazardous Materials, 2025)

Sulfur dioxide increases testosterone biosynthesis by activating ERK1/2 pathway and disrupting autophagy in Leydig cells - Xiang Li; Yan Shi; Sha Liu; Zhiyuan Feng; Haoran Xiao; Rui Li; Zirou Li; Xinyue Zhang; Yongli Han; Jundong Wang; Chen Liang; Jian Bai; et al. (Journal of Hazardous Materials, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Strong magnetism and geochemical characteristics of sediment in Challenger Deep and their indications for sources - KaiWei Wang; YongHong Wang; QiuYu Yue; XiaoHua Zhang; JiWen Liu; Chunhui Xiao; Toshiya Kanamatsu; Michael Strasser; Rui Bao (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Equol promotes the in vitro maturation of porcine oocytes by activating the NRF2/KEAP1 signaling pathway - Sai Xiao; Ke Peng; Rui Chen; Xinxin Liu; Benliang Zhou; Rijing He; Yujun Yan; Runtian Wan; Ye-Shi Yin; Shengsheng Lu; Xingwei Liang (Theriogenology, 2025)

A ferroptosis-targeting detachable dissolvable microneedle as a combined therapeutic strategy for radiation-induced oral mucositis - Yanxuan Xiao; Caiyong Song; Hongping Ye; Dan Li; Jiayi Shi; Xiaoke Huang; Qianming Chen; Rui Liu (Chemical Engineering Journal, 2025)

Differential responses of soil CO2 dynamics along soil depth to rainfall patterns in the Chinese Loess Plateau - Xiao Yang; Rui Wang; Mengdi Yang; Quanfeng Liu; Wenju Zhang; Shengli Guo (Agriculture, Ecosystems & Environment, 2025)

Microfluidic Approach for Enhanced Paeoniflorin Transdermal Delivery: A Comparative Study on Different Chips and Mixing Dynamics - Qifei Gu; Wuqing Xiao; Yingyin Zhu; Wanling Zhong; Xue Sui; Yongchao Liu; Jie Zhang; Huichao Wu; Rui Zhou (AAPS PharmSciTech, 2025)
Paeoniflorin is a natural pharmaceutical ingredient with a widely biological activity. However, as a hydrophilic drug, the problem of low transdermal rate limits its clinical application. To overcome this shortage, LUVs were used as biocompatible carriers of paeoniflorin in this study. We prepared paeoniflorin-loaded large unilamellar vesicles (LUVs) with W/O/W structure by microfluidics. We used four kinds of chips to prepare paeoniflorin LUVs and explored the effects of the chip structures on LUVs properties applying both experiments and numerical simulations. The difference of fluid mixing mechanisms was analyzed among four different channels, including straight and curved structures. Then we evaluated the differences in skin permeability among the three groups, paeoniflorin aqueous solution group, drug-loaded liposome group and blank liposome & drug mixture group, using the abdominal skin of male mice. The results showed that the structure of the microfluidic channel was a key factor affecting the flow rate and mixing efficiency. The mixing efficiency further affected the liposome size. The mixing efficiency of curved channel was not better than that of a straight channel due to the low flow rate and long mixing time. By the results of transdermal experiments, LUVs could reduce the transdermal time and increase the total transdermal amount. LUVs effectively improved the transdermal absorption efficiency of paeoniflorin. In conclusion, paeoniflorin LUVs with highly efficient transdermal were successfully prepared by using microfluidics. We explored the underlying fluid dynamics that lead to variations in the preparation with different chip structures. The transdermal effect of the LUVs was verified. Graphical Abstract

Nitrogen@Carbon Quantum Dots for Fluorescence Detection of L-alanine, L-methionine and L-cysteine - Xin Chen; Qing-wan Wang; Tong-ling Zhan; Yue Sun; Xiao-rui Zhang; Kun Liu; Xiao-wu Liu (Journal of Fluorescence, 2025)

Acoustic leak localization for water distribution network through time-delay-based deep learning approach - Rongsheng Liu; Tarek Zayed; Rui Xiao (Water Research, 2025)

To kill or to piggyback: Switching of viral lysis-lysogeny strategies depending on host dynamics - Chen Hu; Xiaowei Chen; Wei Wei; Douglas Wallace; Jihua Liu; Yao Zhang; Lianbao Zhang; Dapeng Xu; John Batt; Xilin Xiao; Qiang Shi; Qiang Zheng; et al. (Science of The Total Environment, 2025)

Microbial mechanisms of sulfate reduction for low-temperature bioremediation of acid-mined uranium sandstone groundwater - Rui Xiao; Zhenghua Liu; Min Xu; Guoping Jiang; Yang Peng; Cunzeng Li; Jie Wang; Huaqun Yin; Lechang Xu (Journal of Water Process Engineering, 2025)

Grazing increases the complexity of networks and ecological stochastic processes of mycorrhizal fungi - Jiqiong Zhou; Pengsen Wang; Li Wei; Jianguo Zhang; Xuxu Li; Nan Huang; Gang Liu; Kun Zou; Rui Fan; Lin Liu; Xiao Ma; Ting Huang; et al. (Journal of Environmental Management, 2025)

Exploring the immunomodulatory mechanisms of Osmunda japonica Thunb polysaccharides: Activation of MAPK and NF-κB signaling pathways - Xiaochen Liu; Rui Xu; Yuting Miao; Yining Zang; Yuxin Huang; Yuying Zheng; Fengwei Li; Ming Wei; Rui Xiao; Xiaohong Yu (Food Bioscience, 2025)

Development of a Novel TBM Tunnelling Test Platform and Its Application in Rock–Machine Interaction Analysis - Wei-Qiang Xie; Xiao-Li Liu; Rui-Peng Qian; Jian Chen; En-Zhi Wang; Wei Hong (Rock Mechanics and Rock Engineering, 2025)

Influence of land-use type on earthworm diversity and distribution in Yunnan: Insights from soil properties - Chang-E Liu; Qing-Rui Luo; Yan-Lan Xiao; Hong-Yang Li; Hong-Juan Dong; Chang-Qun Duan (Applied Soil Ecology, 2025)

Nanozymes featuring a mesoporous silica shell for rapid enrichment and ultrasensitive lateral flow immunoassay of influenza A - Jing Liang; Xiaoxian Liu; Zhenzhen Liu; Xuanming Xu; Yinuo Sun; Yuan Chen; Rui Xiao; Yajie Wang (Analytica Chimica Acta, 2025)

Molecular intersections of traumatic brain injury and Alzheimer’s disease: the role of ADMSC-derived exosomes and hub genes in microglial polarization - Pengtao Li; Liguo Ye; Sishuai Sun; Yue Wang; Yihao Chen; Jianbo Chang; Rui Yin; Xiaoyu Liu; Wei Zuo; Houshi Xu; Xiao Zhang; Robert Chunhua Zhao; et al. (Metabolic Brain Disease, 2024)

Spatial and temporal evolution and factors influencing soil aggregate stability in the riparian zone during exposure: A case study of the water-level fluctuation zone of the Three Gorges Reservoir, China - Yuanzhen Ni; Zhenyao Xia; Yueshu Yang; Deyu Liu; Rui Xiang; Yu Ding; Huan Hong; Di Wang; Hai Xiao (Science of The Total Environment, 2024)

Associations between volatile organic compounds exposure and multiple oxidative damage biomarkers: Method development, human exposure, and application for e-waste pollution prediction - Jia-Rong Wang; Hong-Xuan Kuang; Ye Liu; Xin-Yi Li; Tian-Hong Chen; Xiao-Hui Zhu; Rui-Fang Fan; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

β-Caryophyllene oxide inhibits lysine acetylation of histones in Fusarium proliferatum to block ribosomal biosynthesis and function - Hong-Xin Liao; Jing Yang; Jin-Rui Wen; Hong-Yan Nie; Jun Zhao; Fu-Rong Xu; Xiao-Yun Liu; Xian Dong (Pesticide Biochemistry and Physiology, 2024)

Mechanisms of manganese-tolerant Bacillus brevis MM2 mediated oxytetracycline biodegradation process - Zhiyan Li; Jin Wang; Rui Deng; Liu Azuan; Mingzhu Chen; Xiao He; Zhengbo Yue (Environmental Pollution, 2024)

Muscone inhibits angiotensin II–induced cardiac hypertrophy through the STAT3, MAPK and TGF-β/SMAD signaling pathways - Yi-jiang Liu; Jia-jia Xu; Cui Yang; Yan-lin Li; Min-wei Chen; Shi-xiao Liu; Xiang-hui Zheng; Ping Luo; Rui Li; Di Xiao; Zhong-gui Shan (Molecular Biology Reports, 2024)
Background Muscone is a chemical monomer derived from musk. Although many studies have confirmed the cardioprotective effects of muscone, the effects of muscone on cardiac hypertrophy and its potential mechanisms are unclear.The aim of the present study was to investigate the effect of muscone on angiotensin (Ang) II-induced cardiac hypertrophy. Methods and results In the present study, we found for the first time that muscone exerted inhibitory effects on Ang II-induced cardiac hypertrophy and cardiac injury in mice. Cardiac function was analyzed by echocardiography measurement, and the degree of cardiac fibrosis was determined by the quantitative real-time polymerase chain reaction (qRT-PCR), Masson trichrome staining and western blot assay. Secondly, qRT-PCR experiment showed that muscone attenuated cardiac injury by reducing the secretion of pro-inflammatory cytokines and promoting the secretion of anti-inflammatory cytokines. Moreover, western blot analysis found that muscone exerted cardio-protective effects by inhibiting phosphorylation of key proteins in the STAT3, MAPK and TGF-β/SMAD pathways. In addition, CCK-8 and determination of serum biochemical indexes showed that no significant toxicity or side effects of muscone on normal cells and organs. Conclusions Muscone could attenuate Ang II-induced cardiac hypertrophy, in part, by inhibiting the STAT3, MAPK, and TGF-β/SMAD signaling pathways.

Lymph nodes in oral squamous cell carcinoma: a comprehensive anatomical perspective - Guang-Rui Wang; Nian-Nian Zhong; Lei-Ming Cao; Xuan-Hao Liu; Zi-Zhan Li; Yao Xiao; Kan Zhou; Yi-Fu Yu; Bing Liu; Lin-Lin Bu (Clinical & Experimental Metastasis, 2024)

Sirtuin 7 ameliorates cuproptosis, myocardial remodeling and heart dysfunction in hypertension through the modulation of YAP/ATP7A signaling - Yu-Fei Chen; Rui-Qiang Qi; Jia-Wei Song; Si-Yuan Wang; Zhao-Jie Dong; Yi-Hang Chen; Ying Liu; Xin-Yu Zhou; Jing Li; Xiao-Yan Liu; Jiu-Chang Zhong (Apoptosis, 2024)

Phylogenomic analyses and comparative genomic studies of Thermus strains isolated from Tengchong and Tibet Hot Springs, China - Inam Ullah Khan; Muhammad Saqib; Arshia Amin; Sadia Manzoor; Iftikhar Ahmed; Rui-Rui Liu; Jian-Yu Jiao; Xiao-Yang Zhi; Wen-Jun Li (Antonie van Leeuwenhoek, 2024)

A multimodal classification method: Cow behavior pattern classification with improved EdgeNeXt using an inertial measurement unit - Yingqi Peng; Yingxi Chen; Yuxiang Yang; Meiqi Liu; Rui Hu; Huawei Zou; Jianxin Xiao; Yahui Jiang; Zhisheng Wang; Lijia Xu (Computers and Electronics in Agriculture, 2024)

Optimal operation of CCHP system with duality operation strategy considering hydrogen trading and carbon capture - Zhi-Feng Liu; Ya-He Huang; Qing Kang; Ze-Qi Li; Jing Lu; Rui-Zheng Gu; Xing-Fu Luo; Xiao-Rui Chen; You-Yuan Liu; Yu Tang; Liang Guo (Sustainable Cities and Society, 2024)

Orbital and suborbital climate cycles recorded in terrestrial strata from the late Paleocene-early Eocene in the Subei Basin, East China - Juan Liu; Yanzhen Li; Liangcheng Tan; Rui Zhang; Xingxing Liu; Ze Zhang; Anguo Xiao; David B. Kemp; Chunju Huang (Global and Planetary Change, 2024)

Astronomical forcing of terrestrial organic carbon burial in East Asia during the Eocene - Juan Liu; Juye Shi; Yongchao Lu; Xiaojie Fan; Ze Zhang; Rui Zhang; Zhixiang Wang; Ke Xu; Anguo Xiao; David B. Kemp; Chunju Huang (Earth and Planetary Science Letters, 2024)

Formate-facilitated recovery of wastewater anammox granular sludge from oxygen inhibition: Effects and mechanisms - Min Xu; Rui Xiao; Fengqian Xu; Wenbo Chai; Wenlong Liu; Huijie Lu (Chemical Engineering Journal, 2024)

Inflammatory microenvironment activation-targeted self-delivery nanomedicine for effective rheumatoid arthritis treatment - Xinrui Dong; Haibao Liu; Rui Sun; Shuwen Tan; Gaoyang Li; Xuerou Jin; Xiaoqin Zhang; Zhiyi Xiao; Dingxiang Li; Jun-Li Cao; Xiaoran Deng (Chemical Engineering Journal, 2024)

Tuning local charge polarization of covalent organic frameworks for enhanced photocatalytic uranium (VI) reduction - Xiao-Xing Wang; Cheng-Rong Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Hao-Xuan He; Rui Zhang; An-Min Song; Jia-Xin Qi; Xiao-Juan Chen; Xin Liu; Yuan-Jun Cai; Ru-Ping Liang; et al. (Chemical Engineering Journal, 2024)

Mechanism of o-cresol polymerization and its carbon recovery from aqueous solution by a cathode/Fe2+/H2O2 process - Sui-Qin Yang; Yu-Hong Cui; Wei-Jun Xue; Zheng-Qian Liu; Rui Hu; Xiao-Qian Ye (Chemical Engineering Journal, 2024)

Molecularly tailored bifunctional nano-overlayers for efficient and stable inverted perovskite solar cells - Lu-Lu Jiang; Shao-Jie Li; Qi Li; Shuai-Ke Guo; Zhen-Rong Song; Ying-Zhuo Shen; Xiao-Nan Zhang; Dong-Sheng Zheng; Xiao-Dan Tang; Hai-Rui Liu (Chemical Engineering Journal, 2024)

“Four-in-One” multifunctional nanohybrids integrated magnetic colorimetric catalytic SERS-driven lateral flow immunoassay for ultrasensitive detection of MPXV - Xiaoxian Liu; Xingsheng Yang; Zongzheng Zhao; Xiao Li; Jing Liang; Yinuo Sun; Rui Xiao; Guanghui Wang (Chemical Engineering Journal, 2024)

MSC-mediated mitochondrial transfer restores mitochondrial DNA and function in neural progenitor cells of Leber’s hereditary optic neuropathy - Rui Wang; Feixiang Bao; Manjiao Lu; Xiaoyun Jia; Jiahui Xiao; Yi Wu; Qingjiong Zhang; Xingguo Liu (Science China Life Sciences, 2024)

Effects of replacing fish meal with biofloc meal on growth performance, nutrients metabolism, immune response and intestinal microbiota of common carp (Cyprinus carpio) - Xiao-Fang Wei; Si-Tong Meng; Yin-Tao Wang; Liang Li; Rui Zhu; Deng-Lai Li; Si-Ying Liu; Li-Fang Wu (Aquaculture, 2024)

A global urban heat island intensity dataset: Generation, comparison, and analysis - Qiquan Yang; Yi Xu; TC Chakraborty; Meng Du; Ting Hu; Ling Zhang; Yue Liu; Rui Yao; Jie Yang; Shurui Chen; Changjiang Xiao; Renrui Liu; et al. (Remote Sensing of Environment, 2024)

Complete genome sequence of the 4-hydroxybenzoate-degrading bacterium Gymnodinialimonas sp. 57CJ19, a potential novel species from intertidal sediments - Dong-Hui Li; Ning Zheng; Zhen-Hai Liu; Xiao-Rui Dong; Chen Zhao; Shi-Gan Yan; Bin-Bin Xie (Marine Genomics, 2024)

Reaction mechanism for NH3-SCR of NOx over CrMn1.5O4 catalyst - Zheng-nan Yuan; Rui-tang Guo; Xiao-jing Liu; Yi-feng Xu; Lu Liu; Wei-guo Pan (Fuel, 2024)

Myo-inositol: A potential game-changer in preventing gill cell death and alleviating “gill rot” in grass carp (Ctenopharyngodon idellus) - Jie Chen; Wei-Dan Jiang; Lin Feng; Pei Wu; Yang Liu; Xiao-Wan Jin; Hong-Mei Ren; Jia-Yong Tang; Rui-Nan Zhang; Xiao-Qiu Zhou (Fish & Shellfish Immunology, 2024)

High-throughput generation of monodisperse double emulsions via controllable symmetric splitting in Y-shaped microchannels - Lin-Ling Fan; Wei Wang; Xiao-Jie Ju; Zhuang Liu; Rui Xie; Jianhong Xu; Guangsheng Luo; Da-Wei Pan; Liang-Yin Chu (Chemical Engineering Journal, 2024)

Dialdehyde starch cross-linked aminated gelatin sponges with excellent hemostatic performance and biocompatibility - Yu-He Zhu; Chen-Yu Zhou; Xu Peng; Wei Wang; Zhuang Liu; Rui Xie; Da-Wei Pan; Xiao-Jie Ju; Liang-Yin Chu (Carbohydrate Polymers, 2024)

A Cysteinyl-tRNA Synthetase Mutation Causes Novel Autosomal-Dominant Inheritance of a Parkinsonism/Spinocerebellar-Ataxia Complex - Han-Kui Liu; Hong-Lin Hao; Hui You; Feng Feng; Xiu-Hong Qi; Xiao-Yan Huang; Bo Hou; Chang-Geng Tian; Han Wang; Huan-Ming Yang; Jian Wang; Rui Wu; et al. (Neuroscience Bulletin, 2024)
This study aimed to identify possible pathogenic genes in a 90-member family with a rare combination of multiple neurodegenerative disease phenotypes, which has not been depicted by the known neurodegenerative disease. We performed physical and neurological examinations with International Rating Scales to assess signs of ataxia, Parkinsonism, and cognitive function, as well as brain magnetic resonance imaging scans with seven sequences. We searched for co-segregations of abnormal repeat-expansion loci, pathogenic variants in known spinocerebellar ataxia-related genes, and novel rare mutations via whole-genome sequencing and linkage analysis. A rare co-segregating missense mutation in the CARS gene was validated by Sanger sequencing and the aminoacylation activity of mutant CARS was measured by spectrophotometric assay. This pedigree presented novel late-onset core characteristics including cerebellar ataxia, Parkinsonism, and pyramidal signs in all nine affected members. Brain magnetic resonance imaging showed cerebellar/pons atrophy, pontine-midline linear hyperintensity, decreased rCBF in the bilateral basal ganglia and cerebellar dentate nucleus, and hypo-intensities of the cerebellar dentate nuclei, basal ganglia, mesencephalic red nuclei, and substantia nigra, all of which suggested neurodegeneration. Whole-genome sequencing identified a novel pathogenic heterozygous mutation (E795V) in the CARS gene, meanwhile, exhibited none of the known repeat-expansions or point mutations in pathogenic genes. Remarkably, this CARS mutation causes a 20% decrease in aminoacylation activity to charge tRNA Cys with L-cysteine in protein synthesis compared with that of the wild type. All family members carrying a heterozygous mutation CARS (E795V) had the same clinical manifestations and neuropathological changes of Parkinsonism and spinocerebellar-ataxia. These findings identify novel pathogenesis of Parkinsonism-spinocerebellar ataxia and provide insights into its genetic architecture.

WNT2B high‑expressed fibroblasts induce the fibrosis of IBD by promoting NK cells secreting IL-33 - Yanling Cheng; Shuzhe Xiao; Lin Lan; Danqiong Liu; Rui Tang; Jianbiao Gu; Li Ma; Zhihua He; Xirong Chen; Lanlan Geng; Peiyu Chen; Huiwen Li; et al. (Journal of Molecular Medicine, 2024)

RIP3 regulates doxorubicin-induced intestinal mucositis via FUT2-mediated α-1,2-fucosylation - Wei Wen; Xiaomin Hu; Jialin Liu; Fanxin Zeng; Yihua Xu; Ye Yuan; Chunyan Gao; Xueting Sun; Bo Cheng; Jue Wang; Xinli Hu; Rui-Ping Xiao; et al. (Inflammation Research, 2024)

High-altitude exposure leads to increased modularity of brain functional network with the increased occupation of attention resources in early processing of visual working memory - Jing Zhou; Nian-Nian Wang; Xiao-Yan Huang; Rui Su; Hao Li; Hai-Lin Ma; Ming Liu; De-Long Zhang (Cognitive Neurodynamics, 2024)

The role of male hormones in bacterial infections: enhancing Staphylococcus aureus virulence through testosterone-induced Agr activation - Zhaoxia Luo; Huimin Xi; Wei Huang; Mei-fang Liu; Lei Yuan; Qiang Chen; Yanghua Xiao; Qing Zhu; Rui Zhao; Yi-yun Sheng (Archives of Microbiology, 2024)

Tropical cyclone tracking from geostationary infrared satellite images using deep learning techniques - Chang-Jiang Zhang; Liu Zhang; Chen-Miao Rui; Lei-Ming Ma; Xiao-Qin Lu (International Journal of Remote Sensing, 2024)

The role of pantothenic acid in alleviating hypoxia-induced liver injury of sub-adult grass carp (Ctenopharyngodon idellus): Possible mechanisms and implication - Yan Xia; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Jia-Yong Tang; Rui-Nan Zhang; Lu Zhang; Hai-Feng Mi; Lin Feng (Aquaculture, 2024)

Megastigmane glycosides from the traditional Uighur medicine Cydonia oblonga Mill. - Shan-Shan Jiao; Rui-Feng Ding; Xin Yuan; Xiao-Ping He; Yan Liu; Kai Guo; Sheng-Hong Li (Phytochemistry, 2024)

Directional synthesis and application of long-chain ethers from biomass-derived carbonyls - Yuan Liu; Fang Liu; Li Yang; Feiqiang Guo; Shiliang Wu; Rui Xiao (Fuel, 2024)

A Janus textile mimics leaf stoma for dynamic thermal regulation through a shape memory coating - Yuanxiang Xiao; Rui Cai; Shuangfei Xiang; Shujun Zhao; Feiya Fu; Hongyan Diao; Xiangdong Liu (Chemical Engineering Journal, 2024)

Phosphorylation of RasGRP1 by Shc3 prevents RasGRP1 degradation and contributes to Ras/c-Jun activation in hepatocellular carcinoma - Xinran Zhang; Yun Liu; Rui Yang; Yuanyuan Guo; Meiling Yan; Ying Xiao; Yunzhuo Dong; Ruixia Zhang; Yinpeng Qin; Yishan Bu; Yi Zhang; Huier Gao (Molecular and Cellular Biochemistry, 2024)

Jianpi Huayu Prescription Prevents Atherosclerosis by Improving Inflammation and Reshaping the Intestinal Microbiota in ApoE−/− Mice - Hao-Ran Zhao; Qin-Chi Xian; Xuan-Ming Zhang; Xiao-Yu Ma; Fu-Qiao Wang; Rui-Si Wang; Zhi-Jie Liu; Zhi-Gang Zhang (Cell Biochemistry and Biophysics, 2024)
This study established an LPS-induced RAW264.7 macrophage inflammatory injury model and an AS mouse vulnerable plaque model to observe the effect of JPHYP on macrophage inflammation, plaque formation, blood lipids, inflammation levels, intestinal flora and the influence of TLR4/MyD88/MAPK pathway, and explore the anti-AS effect and molecular mechanism of JPHYP, and detected 16S rRNA of mice intestinal microbes. The difference of intestinal flora in different groups of mice was compared to further explore the intervention effect of JPHYP and clarify the molecular biological mechanism of JPHYP in preventing and treating AS by regulating TLR4/MyD88/MAPK inflammatory signaling pathway and improving intestinal flora.

Improving effect of N-acetylcysteine on growth and intestinal health in juvenile Cyprinus carpio involve the Nrf2/MAPK/NF-κB pathways - Rui Zhu; Deng-Lai Li; Bao-Yuan Zhang; Liang Li; Guo-Jun Shang; Hao-Tong Wang; Zhi-Yong Yang; Xiao-fang Wei; Si-Tong Meng; Si-Ying Liu; Yin-Tao Wang; Li-Fang Wu; et al. (Aquaculture, 2024)

Spatio-temporal patterns and population exposure risks of urban heat island in megacity Shanghai, China - Dan Liu; Rui Zhou; Qun Ma; Tianxing He; Xuening Fang; Lishan Xiao; Yina Hu; Jie Li; Lin Shao; Jun Gao (Sustainable Cities and Society, 2024)

Exploring the relationship between land use change patterns and variation in environmental factors within urban agglomeration - Rui Xiao; Hanyu Yin; Ruoxin Liu; Zhonghao Zhang; Sukhbaatar Chinzorig; Kun Qin; Wenfang Tan; Yi Wan; Zhi Gao; Chen Xu; Lumeng Liu; Tao Jia (Sustainable Cities and Society, 2024)

First complete Niobe yangtzeensis Lu, 1975 (Asaphidae, Trilobita) from the Middle Ordovician of South China, and its systematic and palaeogeographic implications - Xiao-Qi Du; Yi-Long Liu; Rui-Wen Zong (Palaeoworld, 2024)

The effects and mechanisms of heat stress on mammalian oocyte and embryo development - L.I. Lang; Zhen-zhen Wang; Bin Liu; S.H.E.N. Chang-qing; T.U. Jing-yi; W.A.N.G. Shi-cheng; L.E.I. Rui-ling; P.E.N.G. Si-qi; X.I.A.O. Xiong; Z.H.A.O. Yong-ju; Xiao-yan Qiu (Journal of Thermal Biology, 2024)

Enhanced photocatalytic U(VI) reduction via double internal electric field in CoWO4/covalent organic frameworks p-n heterojunction - Rui-Xiang Bi; Zhi-Hai Peng; Lan Lei; Xiao-Xing Wang; Xin Liu; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2024)

Silica's silent threat: Contributing to skin fibrosis in systemic sclerosis by targeting the HDAC4/Smad2/3 pathway - Bingsi Tang; Yaqian Shi; Zhuotong Zeng; Xinglan He; Jiangfan Yu; Ke Chai; Jiani Liu; Licong Liu; Yi Zhan; Xiangning Qiu; Rui Tang; Yangfan Xiao; et al. (Environmental Pollution, 2024)

The protective effect and mechanism of piperazine ferulate in rats with 5/6 nephrectomy-caused chronic kidney disease - Xiu-Meng Zhang; Xin-Ran Min; Dan Li; Bo Li; Yi-Xin rui; Hong-Xiao Xie; Rong Liu; Nan Zeng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Ile-Pro-Pro attenuates sympathetic activity and hypertension - Jun-Liu Chen; Rui Ge; Xiu-Zhen Li; Yue Zhang; Wen-Yuan Hao; Na Li; Zhi-Qin Xu; Qi Chen; Yue-Hua Li; Guo-Qing Zhu; Xiao Tan (Journal of Physiology and Biochemistry, 2024)

Distribution, risk evaluation, and source allocation of cesium and strontium in surface soil in a mining city - Jia-li Li; Chun-dan Gan; Xin-yue Du; Xue-ying Yuan; Wen-lin Zhong; Meng-qi Yang; Rui Liu; Xiao-yu Li; Hao Wang; Yu-liang Liao; Zheng Wang; Mu-cheng Xu; et al. (Environmental Geochemistry and Health, 2024)

An “off-on-enhanced on” electrochemiluminescence biosensor based on resonance energy transfer and surface plasmon coupled 3D DNA walker for ultra-sensitive detection of microRNA-21 - Meng-Li Li; Ming-Yu Zhong; Jia Zhang; Yi-Jia Zhang; Yu-Qi Zhang; Yan Liu; Xiang-Kai Li; Shu-Tian Gan; Gong-Rui Meng; Li Mi; Yong-Hong Hu; Fang Zhang; et al. (Analytica Chimica Acta, 2024)

Targeting gut microbiota for immunotherapy of diseases - Ya-Jie Yu; Xiao-Dong Liu; Cai Liao; Rui Yu; Xin Wang; Ming Li; Yun Wang (Archives of Toxicology, 2024)

C-Phycocyanin improves the quality of goat oocytes after in vitro maturation and vitrification - Xing-Yue Wang; Yang Gao; Hao-Ran Liu; Teng Wang; Meng-Lei Feng; Fang-Rui Xue; Kang Ding; Qi Yang; Zhao-Yu Jiang; Dui Sun; Chun-Ru Song; Xiao-Jie Zhang; et al. (Theriogenology, 2024)

Per- and polyfluoroalkyl substances and human health outcomes: An umbrella review of systematic reviews with meta-analyses of observational studies - Wei-Yi Xing; Jia-Nan Sun; Fang-Hua Liu; Li-Shen Shan; Jia-Li Yin; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Jia-Xin Liu; Wen-Rui Zheng; Ying-Ying Zhang; Xin-Jian Song; et al. (Journal of Hazardous Materials, 2024)

Phyllanthus emblica Linn: A comprehensive review of botany, traditional uses, phytonutrients, health benefits, quality markers, and applications - Qin-Ge Ma; Lei Wang; Rong-Hua Liu; Jin-Bin Yuan; Hui Xiao; Zhang-Yang Shen; Jia-Xin Li; Jia-Zeng Guo; Lan Cao; Hui-Lian Huang; Rong-Rui Wei (Food Chemistry, 2024)

Hemorrhagic Shock and Resuscitation Causes Excessive Dopaminergic Signaling in the mPFC and Cognitive Dysfunction - Rong-Xin Song; Hui-Tao Miao; Shi-Yan Jia; Wen-Guang Li; Ji-Zhen Liu; Wei Zhang; Bao-Rui Xing; Jian-Yong Zhao; Li-Min Zhang; Xiao-Ming Li (Molecular Neurobiology, 2024)

Whole exome sequencing analyses reveal novel genes in telomere length and their biomedical implications - Wei-Shi Liu; Bang-Sheng Wu; Liu Yang; Shi-Dong Chen; Ya-Ru Zhang; Yue-Ting Deng; Xin-Rui Wu; Xiao-Yu He; Jing Yang; Jian-Feng Feng; Wei Cheng; Yu-Ming Xu; et al. (GeroScience, 2024)

Spatiotemporal coda Q variations in the northeastern margin of the Qinghai–Tibet Plateau, China - Zhaocheng Liang; Xiao Guo; Rui Zou; Xuzhou Liu; Manzhong Qin; Shaohua Li (Journal of Earth System Science, 2024)

Organic-mineral colloids regulate the migration and fractionation of rare earth elements in groundwater systems impacted by ion-adsorption deposits mining in South China - Xiao-Rui Liu; Wen-Shen Liu; Miaoyue Zhang; Chao Jin; Keng-Bo Ding; Alan J.M. Baker; Rong-Liang Qiu; Ye-Tao Tang; Shi-Zhong Wang (Water Research, 2024)

Celastrol induced the autophagy of spermatogonia cells contributed to tripterygium glycosides-related testicular injury - Dong-Xiao Cui; Ze-Chen Niu; Xi Tang; Chun-Zhou Cai; Ding-Qiao Xu; Rui-Jia Fu; Wen-Juan Liu; Yu-Wei Wang; Yu-Ping Tang (Reproductive Toxicology, 2024)

Critical factors in soil organic carbon mineralization induced by drying, wetting and wet-dry cycles in a typical watershed of Loess Plateau - Yi Zhang; Xiaojun Liu; Peng Li; Lie Xiao; Shixuan Zhou; Xing Wang; Rui Wang (Journal of Environmental Management, 2024)

Purification, characterisation and visualisation of soybean protein hydrolysis by aspergillopepsin I from mangrove Aspergillus tubingensis - Hongli Yao; Shuangping Liu; Rui Chang; Tiantian Liu; Dongna Ma; Xiao Han; Congyu Lin; Zhilei Zhou; Jian Mao (International Biodeterioration & Biodegradation, 2024)

Synergistic multifactor influence and management of commercial vanadium-based catalyst lifetimes - Yi-feng Xu; Xiao-jing Liu; Rui-tang Guo; Tong Wu; Hong-lei Ding; Dong Ye; Wei-guo Pan (Fuel, 2024)

Photoactive cationic conjugated microporous polymers containing pyrimidine with an ‘adsorption-kill’ antibacterial strategy for infected wound healing - Ga Liu; Shengfei Bao; Jiahao Shi; Chunyu Xie; Fuying Liao; Lingshuang Wang; Fan Zheng; Rui L. Reis; Subhas C. Kundu; Bo Xiao; Xiao Yang; Lian Duan (Chemical Engineering Journal, 2024)

Adaptive strategies of high and low nucleic acid prokaryotes in response to declining resource availability and selective grazing by protozoa - Chen Hu; Liuqian Yu; Xiaowei Chen; Jihua Liu; Yao Zhang; John Batt; Xilin Xiao; Qiang Shi; Rui Zhang; Tingwei Luo; Nianzhi Jiao; Dapeng Xu (Science China Earth Sciences, 2024)
Prokaryotes play a fundamental role in global ocean biogeochemical cycles. However, how the abundance and metabolic activity of ecologically distinct subgroups (i.e., high nucleic acid (HNA) and low nucleic acid (LNA) cells), and their regulating factors, change in response to changing marine environmental conditions remains poorly understood. Here, we delved into the time-evolving dynamic responses of the HNA and LNA prokaryotic subgroups to declining resource availability and selective grazing by protozoa by conducting a 73-day incubation experiment in a large-volume (117,000 L) macrocosm that facilitates community-level exploration. We found that the metabolic activity of the HNA subgroup was higher than that of the LNA subgroup when the macrocosm was resource replete but that the HNA subgroup declined more rapidly than the LNA subgroup as the resources became increasingly scarce, leading to a steadily increasing contribution of LNA cells to prokaryotic activity. Meanwhile, as resources in the macrocosm became limited, protozoan grazing preference shifted from the HNA to the LNA subgroup and the contributions of the LNA subgroup to the carbon flow within the macrocosm increased. The findings highlight the resilience of LNA cells in resource-limited environments, illuminate the critical role of selective grazing by protozoa in balancing distinct prokaryotic subgroups under changing resource conditions, and demonstrate the complex and adaptive interactions between protozoa and prokaryotes across diverse environmental contexts.

Two new sesterterpenoids from Atractylodes japonica Koidz. ex Kitam - Yuan-Yuan Zhou; Zhao Sun; Yan Liu; Zhen-Xing Fang; Hui-Rui Gao; Ning-Yu Liu; Xiao-Juan Zhang; Bing-You Yang; Hai-Xue Kuang (Journal of Natural Medicines, 2024)

Genome-wide identification and expression-pattern analysis of sulfate transporter (SULTR) gene family in cotton under multiple abiotic stresses and fiber development - Yu Chen; Xianghui Xiao; Rui Yang; Zhihao Sun; Shuhan Yang; Haibo Zhang; Baoguang Xing; Yanfang Li; Qiankun Liu; Quanwei Lu; Yuzhen Shi; Youlu Yuan; et al. (Functional & Integrative Genomics, 2024)

Evaluating the fracture resistance and drainage difficulty of coal reservoirs using log data - Zhi-di Liu; Bin-rui Yang; Xiao-yan Tang; Wei Wang; Liang Ji; Zhi-hao Jiang (Applied Geophysics, 2024)

A newly defined latest Carboniferous-Permian ridge subduction in the southern Altaids: Insights from adakitic, S-type, and I-type granitoids in the northern East Junggar (NW China) - Jingmin Gan; Wenjiao Xiao; Qigui Mao; Hao Wang; He Yang; Miao Sang; Xiaoliang Jia; Yin Liu; Zhiyong Zhang; Zhou Tan; Rui Li (International Geology Review, 2024)

New sight in arginine-improved flesh quality: Role of MRFs, cyclins, and WNT signaling in grass carp (Ctenopharyngodon idellus) - Yu-Long Ma; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Hong-Mei Ren; Rui-Nan Zhang; Shu-Wei Li; Ling Tang; Lin Feng (Aquaculture, 2024)

Advanced acoustic leak detection in water distribution networks using integrated generative model - Rongsheng Liu; Tarek Zayed; Rui Xiao (Water Research, 2024)

Covalent organic framework-sodium alginate-Ca2+-polyacrylic acid composite beads for convenient dispersive solid-phase extraction of neonicotinoid insecticides in fruit and vegetables - Ling-Zhi Liu; Rui Zhou; Yong-Li Li; Yue-Hong Pang; Xiao-Fang Shen; Jun Liu (Food Chemistry, 2024)

Development of an analytic method for organosulfur compounds in Welsh onion and its use for nutritional quality analysis of five typical varieties in China - Pingxiang Liu; Peng Wu; Jingxiu Bi; Yuying Jiang; Rui Gao; Lei Gao; Yonghua Li; Tong Zhao; Xiao Zhang; Chao Zhang; Yutao Wang (Food Chemistry, 2024)

Evaluating the influence of Cynodon dactylon on the wave force and wave erosion in the water-level fluctuation zone of the Three Gorges Reservoir Area - Hai Xiao; Deyu Liu; Feng Gao; Rui Xiang; Wenqi Zhang; Zirui Liu; Chaohuan Ye; Lun Zhang; Zhenyao Xia (Ecological Engineering, 2024)

Mechanistic insights into the stepwise lithium-mediated electrochemical nitrogen reduction for enhanced ammonia synthesis - Peng Yang; Feng Gong; Chaozhen Liu; Shenglin Liu; Enkang Fu; Yuhang Jing; Junjie Feng; Wenbo Tang; Rui Xiao (Chemical Engineering Journal, 2024)

Evaluation of benefits and risks of immunosuppressive drugs in biomaterial-based neural progenitor cell transplantation for spinal cord injury repair - Bo Guo; Xinhao Zhao; Yunlong Zou; Xiaokang Cheng; Zheng Sun; Xiaoyu Xue; Man Yin; Chen Jin; Zhenni Chen; Rui Quan; Wenbin Liu; Bin Chen; et al. (Chemical Engineering Journal, 2024)

CircRNA: a rising therapeutic strategy for lung injury induced by pulmonary toxicants - Cai Liao; Zhen-Wei He; Rui Yu; Ya-Jie Yu; Xiao-Ru Liu; De-Lei Kong; Yun Wang (Archives of Toxicology, 2024)

Two new monoterpene esters from Illigera paviflora Dunn roots - Meng-Yuan Jiang; Xiao-Yun Pu; Wen-Ting Li; Juan Liu; Xiao-Li Zeng; Hong-Rui Li; Xi-Shan Bai; Lin Hu; Xiang-Zhong Huang (Natural Product Research, 2024)

Two microbes assisting Miscanthus floridulus in remediating multi-metal(loid)s-contaminated soil - Yunhua Xiao; Jingjing Ma; Rui Chen; Sha Xiang; Bo Yang; Liang Chen; Jun Fang; Shuming Liu (Environmental Science and Pollution Research, 2024)

Viologen-based ionic conjugated mesoporous polymer as the electron conveyer for efficient polysulfide trapping and conversion - Hai-Yang Li; Zhong-Shan Li; Gang-Hao Qiu; Rou-Rou Zhang; Ya-Rui Wang; Feng Wang; Ren-Wu Huang; Xiao-Fei Liu; Shuang-Quan Zang (Science Bulletin, 2024)

Asymmetric response of transition metal cationic orbitals to applied electric field - Xinmin Liu; Wanglin Chen; Ying Tang; Shuang Xiao; Qinyi Li; Wuquan Ding; Laosheng Wu; Rui Tian; Rui Li; Hang Li (Journal of Hazardous Materials, 2024)

Application of iron tailings in the coagulation of landfill leachate by bipolar membrane electrodialysis - Yanchao Jin; Guodong Wang; Zheng Li; Chun-Yan Lin; Li-Ping Li; Xiao Chen; Rui Ding; Jianxi Liu; Riyao Chen (Journal of Cleaner Production, 2024)

Differentiated impacts of environmental contexts on residents' environmental attitudes towards ecological restoration programs of China's drylands - Tianjing Wu; Yanxu Liu; Xutong Wu; Zhifeng Liu; Rui Xiao (Journal of Environmental Management, 2024)

Non-fitting functional representation for the equilibrium constant subject to reaction between H2S and CO2 - Chao-Wen Wang; Ji Li; Lie-Hui Zhang; Qun-Chao Ding; Guan-Hong Liu; Gao Li; Rui Jiang; Xiao-Long Peng; Lin-Sheng Wei; Hong-Ming Tang; Jian-Yi Liu; Chun-Sheng Jia (Fuel, 2024)

Self-enhanced nanohydrogel electrochemiluminescence biosensor based on CRISPR/Cas12a and gold platinum nanoparticles modification for high-sensitivity detection of Burkholderia pseudomallei - Yuexin Wang; Bo Shen; Nini Luo; Cai Li; Haiping Wu; Yanshuang Wang; Shen Tian; Xuemiao Li; Rui Liu; Xinmin Li; Junman Chen; Wei Cheng; et al. (Chemical Engineering Journal, 2024)

A renal-targeted gene delivery system derived from spermidine for arginase-2 silencing and synergistic attenuation of drug-induced acute kidney injury - Xu-Rui Gu; Kun Liu; Yi-Xuan Deng; Bi-Xiao Xiang; Ling-Yun Zhou; Wen-Jun Yin; Jia-Xin Huang; Ying-Cai Meng; Dian-Ke Li; Rui-Man Que; Zhi-Yao Tang; Guang-Liang Zhou; et al. (Chemical Engineering Journal, 2024)

Core-shell MOF@COF photocatalysts for synergistic enhanced U(VI) and tetracycline cleanup through space and carrier separation - Rui-Xiang Bi; Xin Liu; Lan Lei; Zhi-Hai Peng; Xiao-Xing Wang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Andesitic arc magmas derived from two contrasting mélange origins: Evidence from central Tibetan dioritic porphyries - Lu-Lu Hao; Qiang Wang; Andrew C. Kerr; Fang Huang; Ming Xiao; Xiao-Long Ma; Wan-Feng Zhang; Wen-Yu Wang; Mao-Rui Liu (Chemical Geology, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

The SIDT2/MDA5/IFN axis contributes to virus resistance in teleost fish - Yaoguo Li; Hao Tang; Mingxue Sun; Qiaolin Liu; Yijing Liao; Hong Luo; Rui Li; Ronghua Wang; Hong Yang; Hongquan Wang; Jun Zou; Tiaoyi Xiao (Aquaculture, 2024)

Microplastics affect mosquito from aquatic to terrestrial lifestyles and are transferred to mammals through mosquito bites - Jian-hang Li; Xiao-hui Liu; Guo-rui Liang; He-ting Gao; Si-han Guo; Xin-yu Zhou; Dan Xing; Teng Zhao; Chun-xiao Li (Science of The Total Environment, 2024)

Controlling airborne pathogen within Fangcang shelter hospitals: Aerodynamic analysis of bioaerosols released from various locations through experiment and simulation - Chuan Jiang; Zhijian Liu; Xia Xiao; Haiyang Liu; Junzhou He; Rui Rong; Jingwei Liu; Zhenzhe Huang; Yongxin Wang (Building and Environment, 2024)

Portable fluorescent lateral flow assay for ultrasensitive point-of-care analysis of acute myocardial infarction related microRNA - Junnan Zhao; Han Han; Zhenzhen Liu; Jin Chen; Xiaoxian Liu; Yinuo Sun; Bingwei Wang; Baohua Zhao; Yuanfeng Pang; Rui Xiao (Analytica Chimica Acta, 2024)

The residues and health risk assessment of polychlorinated biphenyls (PCBs) in Pheretima (an earthworm-derived traditional medicine) from southeastern China - Yun-Jing Zhang; Jing Sun; Xiao-Jiang Chen; Rui Cheng; Zhi-Tong Liu; Ling Cao; You-Long Feng (Environmental Science and Pollution Research, 2024)

Nickel isotope fractionation during intense weathering of basalt: Implications for Ni output from continental weathering - Sheng-Sheng Sun; Teng-Hao-Bo Deng; Ming Ao; Wen-Jun Yang; Xiao-Rui Liu; Ting Liu; Jian-Ming Zhu; Jean Louis Morel; Ye-Tao Tang; Rong-Liang Qiu (Geochimica et Cosmochimica Acta, 2024)

α-Glucan derivatives as selective blockers of aldolase A: Computer-aided structure optimization and the effects on HCC - Qian-Han Xiao; Ze-Zhi Li; Li Ren; Shu-Yao Wang; Xiao-Qiang Li; Hong-Xin Bai; Rui-Zhi Qiao; Na Tang; Wen-Juan Liu; Jing-Mei Wang; Guang-Yuan Ma; Dian-Chao Dong; et al. (Carbohydrate Polymers, 2024)

Potential protective effects of sodium butyrate on glycinin-induced oxidative stress, inflammatory response, and growth inhibition in Cyprinus carpio - Deng-Lai Li; Si-Ying Liu; Rui Zhu; Si-Tong Meng; Yin-Tao Wang; Zhi-Yong Yang; Liang Li; Xiao-Fang Wei; Guo-Jun Shang; Hao-Tong Wang; Zi-Hui Qu; Ya-Nan Quan; et al. (Fish Physiology and Biochemistry, 2024)

New 4',5'-methylenedioxyflavone derivatives from the whole plant of sarcandra glabra - Ya-Qiu Qin; Wei Liu; Rui Yin; Ping-Ting Xiao; Zi-Yuan Wang; Tian-Qing Huang; E-Hu Liu (Natural Product Research, 2024)

Development and evaluation of a bivalent vaccine based on recombinant newcastle disease virus expressing infectious bursal disease virus VP2L-CH3-CH4 in SPF chickens - Wen Ying Sun; Xiao Lin Cao; Yi Xuan Wang; Xiao Chen Guo; Jin Miao Liu; Zhi Qiang Xue; Hui Juan Li; Wei Wang; Ting Ting Zhang; Qianhui Li; Rui Han Qin; Yu Han Jin; et al. (Veterinary Microbiology, 2024)

Degradation profile of environmental pollutant 17β-estradiol by human intestinal fungus Aspergillus niger RG13B1 and characterization of genes involved in its degradation - Qi-Meng Zhu; Chao Wang; Jing-Wen Liu; Rui Zhang; Xiu-Lan Xin; Juan Zhang; Cheng-Peng Sun; Xiao-Chi Ma (Journal of Hazardous Materials, 2024)

Identification, characterization and hypolipidemic effect of novel peptides in protein hydrolysate from Protaetia brevitarsis larvae - Zong-Qi Zhang; Xin-Rui Ren; Jin Geng; Si-Cong Chen; Qing-Lei Wang; Chun-Qin Liu; Jin-Hua Xiao; Da-Wei Huang (Food Research International, 2024)

Unlocking the potential of N-acetylcysteine: Improving hepatopancreas inflammation, antioxidant capacity and health in common carp (Cyprinus carpio) via the MAPK/NF-κB/Nrf2 signalling pathway - Rui Zhu; Guo-Jun Shang; Bao-Yuan Zhang; Hao-Tong Wang; Liang Li; Xiao-fang Wei; Deng-Lai Li; Zhi-Yong Yang; Zi-Hui Qu; Ya-Nan Quan; Si-Ying Liu; Yin-Tao Wang; et al. (Fish & Shellfish Immunology, 2024)

Effects of UHPC shear key on strengthening shear performances of wet joint in prefabricated composite beams - Hao Wang; Ning Wang; Xiao-gang Liu; Qing-rui Yue; Jing-liang Yan; Yu Zhang (Engineering Structures, 2024)

Novel insights into mass transfer-controlled radical-mediated co-pyrolysis of lignin with typical plastics - Yuyang Fan; Chao Liu; Zhengxue Zhang; Jia Ouyang; Fuli Deng; Ruixue Zhao; Huiyan Zhang; Rui Xiao (Chemical Engineering Journal, 2024)

Urea-boosted gas-exfoliation synthesis of lignin-derived porous carbon for zinc ion hybrid supercapacitors - Beichen Xue; Chaozhen Liu; Xiaofeng Wang; Yi Feng; Jiahuan Xu; Feng Gong; Rui Xiao (Chemical Engineering Journal, 2024)

Facile synthesis of bead-chain structured MWCNTs@CeO2 with oxygen vacancies-rich for promoting electrochemical energy storage - Xiao-Man Cao; Jia-Qi Chen; Xin-Rui Zhao; Hao Ge; Daliang Liu; Qiong Wu; Zhi-Jia Sun; Qingguo Zhang (Chemical Engineering Journal, 2024)

Mechanism of Antidepressant Action of (2R,6R)-6-Hydroxynorketamine (HNK) and Its Compounds: Insights from Proteomic Analysis - Chaohui Zhen; Chong Wang; Yanjun Ma; Yuli Pang; Feiyue Cai; Jiali Meng; Yuefei He; Ping Xiao; Jianxi Liu; Xi Mei; Shupeng Li; Guanzheng Wu; et al. (Molecular Neurobiology, 2024)

Human activity and climate change accelerate the extinction risk to non‐human primates in China - Wen‐Bo Li; Yang Teng; Ming‐Yi Zhang; Ying Shen; Jia‐Wen Liu; Ji‐Wei Qi; Xiao‐Chen Wang; Rui‐Feng Wu; Jin‐Hua Li; Paul A. Garber; Ming Li (Global Change Biology, 2024)
Human activity and climate change affect biodiversity and cause species range shifts, contractions, and expansions. Globally, human activities and climate change have emerged as persistent threats to biodiversity, leading to approximately 68% of the ~522 primate species being threatened with extinction. Here, we used habitat suitability models and integrated data on human population density, gross domestic product (GDP), road construction, the normalized difference vegetation index (NDVI), the location of protected areas (PAs), and climate change to predict potential changes in the distributional range and richness of 26 China's primate species. Our results indicate that both PAs and NDVI have a positive impact on primate distributions. With increasing anthropogenic pressure, species' ranges were restricted to areas of high vegetation cover and in PAs surrounded by buffer zones of 2.7–4.5 km and a core area of PAs at least 0.1–0.5 km from the closest edge of the PA. Areas with a GDP below the Chinese national average of 100,000 yuan were found to be ecologically vulnerable, and this had a negative impact on primate distributions. Changes in temperature and precipitation were also significant contributors to a reduction in the range of primate species. Under the expected influence of climate change over the next 30–50 years, we found that highly suitable habitat for primates will continue to decrease and species will be restricted to smaller and more peripheral parts of their current range. Areas of high primate diversity are expected to lose from 3 to 7 species. We recommend that immediate action be taken, including expanding China's National Park Program, the Ecological Conservation Redline Program, and the Natural Forest Protection Program, along with a stronger national policy promoting alternative/sustainable livelihoods for people in the local communities adjacent to primate ranges, to offset the detrimental effects of anthropogenic activities and climate change on primate survivorship.

Improvement of flesh quality, muscle growth and protein deposition in adult grass carp (Ctenopharyngodon idella): The role of tryptophan - Lu-Qiao Xiao; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Ling Tang; Shu-Wei Li; Cheng-Bo Zhong; Rui-Nan Zhang; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2023)

Microwave assisted synthesis of PQ-GDY@NH2-UIO-66(Zr) for improved photocatalytic removal of NO under visible light - Qingyu Yang; Shuangjun Li; Rui Liang; Lei Gao; Shao Zhang; Junfen Jia; Yiran Liu; Rundong Lyv; Guisheng Li; Shengxiong Xiao; Dieqing Zhang (Journal of Environmental Sciences, 2023)

Highly-efficient hydrogen production from ammonia decomposition over Co-doped graphdiyne under moderate temperature - Lishan Liu; Feng Gong; Yunlong Xie; Sijun Wang; Yu Qiu; Zhihua Wang; Rui Xiao (Fuel, 2023)

Anti-freezing hydrogel thermocells with confined microcrystallization for enhanced low-grade heat harvest - Ping-Fan Li; Ting-Yuan Hu; Tao Luo; Zhuang Liu; Xiao-Jie Ju; Rui Xie; Da-Wei Pan; Wei Wang; Liang-Yin Chu (Chemical Engineering Journal, 2023)

Development characteristics and failure modes of reactivated ancient landslides in the Sichuan–Tibet transportation corridor, China - Rui-an Wu; Yong-shuang Zhang; Chang-bao Guo; San-shao Ren; Xin Yao; Xiao-yi Liu; Zhi-hua Yang; Guo-liang Du (Journal of Mountain Science, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

The development of ecological civilization in China based on the economic–social–natural complex system - Rui Xiao; Haiguang Hao; Huiyuan Zhang; Yujie Liu; Mengxiao Liu (Ambio, 2023)

A Pre-Procession Module for Point-Based Deep Learning in Dense Point Clouds in the Ship Engineering Field - Shilin Huo; Yujun Liu; Ji Wang; Rui Li; Xiao Liu; Jiawei Shi (Journal of Marine Science and Engineering, 2023)
Recently, point cloud technology has been applied in the ship engineering field. However, the dense point cloud acquired by terrestrial laser scanning (TLS) technology in ship engineering applications brings an obstacle to some powerful and advanced point-based deep learning point cloud processing methods. This paper presents a deep learning pre-procession module to ensure the feasibility of processing dense point clouds on commonly available computer devices. The pre-procession module is designed according to the traditional point cloud processing methods and the PointNet++ paradigm, and is evaluated on two ship structure datasets and two popular point cloud datasets. Experimental results illustrate that (i) the proposed module improves the performance of point-based deep learning semantic segmentation networks, and (ii) the proposed module empowers the existing point-based deep learning networks with the capability to process dense input point clouds. The proposed module may provide a useful semantic segmentation tool for realistic dense point clouds in various industrial applications.

Monitoring the evolution process of karst desertification and quantifying its drivers in the karst area of Southwest China - Wenli Liu; Liangliang Jiang; Bing Liu; Rui Liu; Zuolin Xiao (Environmental Science and Pollution Research, 2023)

New perspective into possible mechanism in growth promotion of potassium diformate (KDF) on the juvenile grass carp (Ctenopharyngodon idella) - Xue Xue; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Rui-Nan Zhang; Lin Feng (Aquaculture, 2023)

Subchronic exposure to di-(2-ethylhexyl) phthalate (DEHP) elicits blood–brain barrier dysfunction and neuroinflammation in male C57BL/6J mice - Wen-qiang Ren; Nuo Liu; Yan Shen; Xian-yan Wang; Qiong Zhou; Chen Rui; Xiao-han Yang; Sheng-long Cao; Ling-yu Li; Yán Wāng; Qu-nan Wang (Toxicology, 2023)

TBtools-II: A “one for all, all for one” bioinformatics platform for biological big-data mining - Chengjie Chen; Ya Wu; Jiawei Li; Xiao Wang; Zaohai Zeng; Jing Xu; Yuanlong Liu; Junting Feng; Hao Chen; Yehua He; Rui Xia (Molecular Plant, 2023)

Surface reconstruction of copper foil via electrochemical etching to proliferate CH4 production from CO2 electroreduction - Weicong Xu; Chao Liu; Peijun Li; Hongyun Zeng; Xianjun Lu; Xinyu Li; Tao Li; Rui Xiao (Journal of Cleaner Production, 2023)

Influence of urban extent discrepancy on the estimation of surface urban heat island intensity: A global-scale assessment in 892 cities - Qiquan Yang; Yi Xu; Xiaohua Tong; Ting Hu; Yue Liu; T.C. Chakraborty; Rui Yao; Changjiang Xiao; Shurui Chen; Zonghan Ma (Journal of Cleaner Production, 2023)

Speciation and gas-liquid equilibrium study of CO2 absorption in aqueous MEA-DEEA blends - Rui Zhang; Haonan Liu; Ruixi Liu; Yingjie Niu; Luning Yang; Francesco Barzagli; Chao'en Li; Min Xiao (Gas Science and Engineering, 2023)

Inactivation of Alicyclobacillus spp. in apple juice by pulsed light and the analysis of its mechanisms - Yali Ma; Qi Wang; Wanyu Shen; Yingying Liu; Lige Qi; Jiandong Xiao; Rui Cai; Tianli Yue; Zhouli Wang (Food Control, 2023)

Enzymatic DNA repairing amplification-powered construction of an Au nanoparticle-based nanosensor for single-molecule monitoring of cytosine deaminase activity in cancer cells - Wen-jing Liu; Rui Song; Xiao-ran Zou; Dong-ling Li; Qinfeng Xu; Chun-yang Zhang (Analytica Chimica Acta, 2023)

Application of enzymatically treated Artemisia annua L. on adult grass carp (Ctenopharyngodon idella): Improved growth performance, intestinal antioxidant capacity and apical junctional complex - Qin-Qin Dai; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; He-Qun Shi; Lu Zhang; Hai-Feng Mi; Jia-Yong Tang; Rui-Nan Zhang; Lin Feng (Aquaculture, 2023)

Diversity and function of mountain and polar supraglacial DNA viruses - Yongqin Liu; Nianzhi Jiao; Kevin Xu Zhong; Lin Zang; Rui Zhang; Xiang Xiao; Yi Shi; Zhihao Zhang; Ye Tao; Liping Bai; Bianli Gao; Yunlan Yang; et al. (Science Bulletin, 2023)

Transmission to green economic development and the dependence on natural resources in China - Rui Ma; Xiao qin Xie; Bin Liu; Fengjiao Zhou; Mohamad Shaharudin bin Samsurijan (Resources Policy, 2023)

Dynamic modeling and switching analysis of all-attitude multimode underwater vehicle for multidimensional data acquisition - Rui Lin; Junjun Cao; Jialuan Xiao; Caoyang Yu; Chunhu Liu; Baoheng Yao; Lian Lian (Ocean Engineering, 2023)

Association between urinary neonicotinoid insecticide levels and dyslipidemia risk: A cross-sectional study in Chinese community-dwelling elderly - Jian Sun; Pei He; Rui Wang; Zhong-Yuan Zhang; Yu-Qing Dai; Xiao-Yu Li; Si-Yu Duan; Cai-Ping Liu; Hao Hu; Guang-Jun Wang; Yan-Ping Zhang; Fei Xu; et al. (Journal of Hazardous Materials, 2023)

Multiple stages of Au mobilization in the Changshagou Au deposit, Eastern Tianshan, NW China: Insights from mineral chemistry and fluid inclusions - Yi-Hao Liu; Yun Zhao; Chun-Ji Xue; Rui Wang; Hai-Xia Chu; Xiao-Bo Zhao; Matthew J. Brzozowski; Reimar Seltmann; Jun Chen; Jun-Bao Gao (Journal of Asian Earth Sciences, 2023)

Exploring the repairing mechanisms of reduced graphene oxide (rGo) on the dysregulation of Xenopus Laevis larva hypothalamus-pituitary-thyroid (HPT) axis caused by chiral triazole fungicide metconazole - Yue Deng; Meiling Zheng; Rui Liu; Haixia Zeng; Jingling Diao; Ran Xiao; Xiaoxuan Su (Pesticide Biochemistry and Physiology, 2023)

Biotrophic interactions between plant and endophytic bacteria in removal of PAHs and Cd from contaminated soils enhanced by graphene oxide - Lingmei Li; Rui Liu; Jianjun Chen; Peidong Tai; Xiaoyi Bi; Ping Zou; Yajie Wang; Yao Xiao (Journal of Cleaner Production, 2023)

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

Controllable micro cross-linking towards multifunctional flame-retardant aliphatic polyamide - Qin Zhang; Guo-Rui Zhu; Xiang-Xin Xiao; Qing-Song Liu; Min Jiang; De-Ming Guo; Hai-Bo Zhao; Wen-Da Li; Li Chen; Bo-Wen Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2023)

Remarkable bioactivity, bio-tribological, antibacterial, and anti-corrosion properties in a Ti-6Al-4V-xCu alloy by laser powder bed fusion for superior biomedical implant applications - Jiang Ju; Rui Zan; Zhao Shen; Chenchen Wang; Peng Peng; Jun Wang; Baode Sun; Bo Xiao; Qian Li; Shaofei Liu; Tao Yang (Chemical Engineering Journal, 2023)

Direct numerical simulation of acoustic wave propagation in ocean waveguides using a parallel finite volume solver - Rui Xia; Xiao-Wei Guo; Chao Li; Jie Liu (Ocean Engineering, 2023)

Efficient lipid synthesis of Chlorella pyrenoidosa promoted under heavy metals from electric arc furnace slag - Qing Yu; Tian-Ji Liu; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Yu-Ran Wang; Le-Le Kang; Rui Ji; Fu-Ping Wang; Xiao-Man Wang; Bao Liu; Shuang Cai; et al. (Journal of Cleaner Production, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Molecular insights into the dissolved organic matter of leather wastewater in leather industrial park wastewater treatment plant - Xiao-Xu Gao; Yun-Wen Wang; Ye-Chen An; Rui-Yun Ren; Yao-Hui Lin; Ning Wang; Yi-Fan Wang; Jing-Long Han; Zhi-Neng Hao; Jing-Fu Liu; Ai-Jie Wang; Nan-Qi Ren (Science of The Total Environment, 2023)

Opportunities for the use of selenium nanoparticles in agriculture - Jiangyun Song; Sujuan Yu; Rui Yang; Junping Xiao; Jingfu Liu (NanoImpact, 2023)

Paleozoic remelting of carbonatite in Bayan Obo (China): Further insights into the formation of a giant REE deposit - Hai-Dong She; Hong-Rui Fan; M. Santosh; Xiao-Chun Li; Kui-Feng Yang; Qi-Wei Wang; Wei Wei; Yan-Jiang Liu; Shang Liu; Shuang-Liang Liu (Gondwana Research, 2023)

Intraspecific variations of adaptive strategies of native and invasive plant species along an elevational gradient - Hasigerili; Kun Guo; Miao-Miao Zheng; Rui-Ling Liu; Yan-Yan Wang; Yuan Gao; Li Shu; Xiao-Ran Wang; Jian Zhang; Wen-Yong Guo (Flora, 2023)

Genetic and Phenotypic Spectrum of Amyotrophic Lateral Sclerosis Patients with CCNF Variants from a Large Chinese Cohort - Bi Zhao; Qirui Jiang; Junyu Lin; Qianqian Wei; Chunyu Li; Yanbing Hou; Bei Cao; Lingyu Zhang; Ruwei Ou; Kuncheng Liu; Tianmi Yang; Yi Xiao; et al. (Molecular Neurobiology, 2023)
Cyclin F (CCNF) variants have been found to be associated with amyotrophic lateral sclerosis (ALS)/frontotemporal dementia (FTD). However, the genetic and clinical characteristics of ALS patients who carry CCNF variants are largely unknown. Genetic analysis was performed for 1587 Chinese ALS patients, and missense variants were predicted by software analyses. Additionally, we searched PubMed, Embase, and Web of Science for relevant literature and conducted a meta-analysis of the frequency of variants. In our ALS cohort, we identified 29 nonsynonymous variants in 41 ALS patients. Among these ALS patients, 18 (1.1%) were carriers of 15 rare missense variants that were considered probably pathogenic variants, and 11 of 15 variants were novel. Seven relevant studies were identified, and a total of 43 CCNF variants in 59 ALS patients with a frequency of 0.8% were reported. The ratio of males to females in our cohort (10/8) was similar to that in Caucasian populations (4/7) and significantly higher than that in Asian populations (10/1). The proportion of bulbar onset in Caucasian CCNF carriers was similar to our cohort (25.0 vs. 27.8%); however, bulbar onset had never been reported in previous Asian studies (0/11). FTD was not found in CCNF carriers in previous Asian studies and our cohort, but it has been reported in a FALS cohort (1/75) of Caucasian individuals. There were some differences in the clinical characteristics among different ethnic ALS populations. More basic scientific studies are needed to elucidate the pathogenic mechanisms and genotype-phenotype associations of CCNF variants.

Composition, metabolism and postharvest function and regulation of fruit cuticle: A review - Gang-Shuai Liu; Hong-Li Li; Zhen-Zhen Peng; Rui-Ling Liu; Yan-Chao Han; Yun-Xiang Wang; Xiao-Dan Zhao; Da-Qi Fu (Food Chemistry, 2023)

CO2 absorption in blended amine solvent: Speciation, equilibrium solubility and excessive property - Rui Zhang; Ruixi Liu; Francesco Barzagli; Meher Geetika Sanku; Chao'en Li; Min Xiao (Chemical Engineering Journal, 2023)

Study on of structural style of fault zone and reservoir characteristics in the northern slope of Tazhong Uplift, Tarim Basin, China - Rui Zhao; Yuan Kang; Jun Han; Xiuxiang Zhu; Teng Zhao; Yuqing Liu; Chongyang Xiao; Shang Deng; Zhixing Ru; Yingtao Li (Carbonates and Evaporites, 2023)

Experimental study on flow and heat transfer of supercritical carbon dioxide in zigzag channels with bending angle 30° for advanced nuclear systems - Sheng-hui Liu; Rui-long Liu; Yan-ping Huang; Xiao-liang Zhu; Liu Yang; Jia Tang; Bin Han; Tian-yang Xing; Xue-bin Zhao (Annals of Nuclear Energy, 2023)

Visualizing the intellectual structure and evolution of carbon neutrality research: a bibliometric analysis - Qi Zhang; Yiman Xiao; Yuting Liu; Tingqin Deng; Zhenghao Li; Rui Li (Environmental Science and Pollution Research, 2023)

Ciprofloxacin degradation performances and mechanisms by the heterogeneous electro-Fenton with flocculated fermentation biochar - Yanchao Jin; Peiwen Huang; Xiongjian Chen; Li-Ping Li; Chun-Yan Lin; Xiao Chen; Rui Ding; Jianxi Liu; Riyao Chen (Environmental Pollution, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Impact of clayey sediment compaction on pore water evolution and the release of iron - Yanjun Liu; Teng Ma; Juan Chen; Ziqi Peng; Cong Xiao; Wenkai Qiu; Rui Liu; Yao Du (Applied Geochemistry, 2023)

Regulating the reaction pathway of nZVI to improve the decontamination performance through magnetic spatial confinement effect - Hai-Yuan Chi; Xiao-Xia Zhou; Min-Rong Wu; Wan-yu Shan; Jing-fu Liu; Jin-quan Wan; Bing Yan; Rui Liu (Journal of Hazardous Materials, 2023)

Amorphous nanophosphates of dual-metal (Co and Ni) for the decomposition of ozone under humid conditions - Qian Zhang; Jifei Liao; Guangzhi Du; Yu Lin; Xiaoqiong Liu; Rui Wang; Lingyu Huang; Wenyan Xiao; Jiahao Chen; Yan Fu (Journal of Environmental Chemical Engineering, 2023)

Activating α7nAChR helps post-myocardial infarction healing by regulating macrophage polarization via the STAT3 signaling pathway - Xiao-Hui Niu; Rong-Hua Liu; Xiao Lv; Rui-Lin He; Fang-Zhou Lv; Shu-Jie Wu; Xu-Qing Li; Lei Li; Jia-Feng Lin (Inflammation Research, 2023)

Full genome sequence of a novel iflavirus from the aster leafhopper Macrosteles fascifrons - Jiajing Xiao; Kai Zhu; Rui Ma; Chunmin Zhang; Keliang Lv; Danfeng Ge; Renyi Liu (Virus Genes, 2023)

Diffusion simulation and risk assessment model establishment of chlorine gas leakage based on terrain conditions - Xiao-ting Ren; Xiao-ling Ma; Jiang-zheng Liu; Rui Liu; Chen-qian Zhao; Hao Wu; Zhao Wang; Chun-xu Hai; Xiao-di Zhang (Environmental Science and Pollution Research, 2023)

Abnormal fatty acid metabolism and ceramide expression may discriminate myocardial infarction from strangulation death: A pilot study - Song-Jun Wang; Bing-Rui Liu; Fu Zhang; Ya-Ping Li; Xiao-Rui Su; Chen-Teng Yang; Bin Cong; Zhi-Hua Zhang (Tissue and Cell, 2023)

Ultrasensitive hydrogel grating detector for real-time continuous-flow detection of trace threat Pb2+ - Xiao-Yu Tian; Meng-Wei Sun; Guo-Yu Wen; Min Cao; Da-Wei Pan; Rui Xie; Xiao-Jie Ju; Zhuang Liu; Wei Wang; Liang-Yin Chu (Journal of Hazardous Materials, 2023)

Associations of co-exposure to polycyclic aromatic hydrocarbons and metals with hyperuricemia risk in Chinese coke oven workers: Mediating roles of oxidative damage - Chaofan Guo; Xin Liu; Xiaojing Liao; Haimei Wu; Zhaorui Zhang; Dehua Wu; Rui Ma; Yongshun Huang; Na Zhao; Yongmei Xiao; Qifei Deng (Environmental Pollution, 2023)

Longitudinal shear behavior and design method of UHPC connection for prefabricated slabs in composite beams - Hao Wang; Xiao-gang Liu; Qing-rui Yue; Ning Wang; Ming-zhao Zheng (Engineering Structures, 2023)

Insight of key parameters in freeze-thaw damage on the performance of cement-based materials: A comparative study with rapid-freeze method - Siyuan Chen; Rui Liu; Huigang Xiao; Wei Wang (Cold Regions Science and Technology, 2023)

Kingella pumchi sp. nov., an organism isolated from human vertebral puncture tissue - Meng Xiao; Ruina Liu; Juan Du; Rui Liu; Lei Zhai; He Wang; Su Yao; Ying-Chun Xu (Antonie van Leeuwenhoek, 2023)

Unique bacterial communities and lifestyles in deep ocean blue holes: Insights from the Yongle Blue Hole (South China Sea) - Shun Zhou; Jiwen Liu; Peng Yao; Liang Fu; Zuosheng Yang; Yulin Zhang; Rui Du; Chao Jia; Lin Chen; Jinchang Liang; Xiaolei Wang; Xiaochong Shi; et al. (Frontiers in Marine Science, 2023)
Deep ocean blue holes possess steep physicochemical gradients, especially low dissolved oxygen concentration, which shape the extraordinary microbial communities. However, the environmental responses of microorganisms with different lifestyles and knowledge of culturable microorganisms in the blue holes are still unknown. Here, we investigated the bacterial community structure with different lifestyles of the world’s deepest blue hole - the Yongle Blue Hole (YBH) in the South China Sea using both culture-dependent and -independent methods. YBH can be divided by oxygen content into an oxic zone, a suboxic zone and two anoxic zones. The abundance of bacteria, archaea, genes dsrB and soxB were all higher in the free-living (FL) lifestyle than in the particle-associated (PA) lifestyle, yet the diversity and richness of PA bacteria were higher than that of FL bacteria. More Gammaproteobacteria and less Alphaproteobacteria , Chloroflexi and Nitrospinae were observed within the FL fraction than within the PA fraction. The relative abundance of sulfur-oxidizing bacteria (SOB) was dominant between 100-140 m (anoxic zone I) in YBH, with a maximum of 90.0% (140 m FL fraction). The SOB in YBH were mainly colorless sulfur bacteria and purple non-sulfur bacteria, of which Thiomicrorhabdus and Sulfurimonas were the main representatives. In addition, a total of 294 bacterial strains were isolated on a variety of media and culture conditions, and 22.2% (18/81) of anaerobic strains were identified as potential novel species. Our study reveals a distinction between FL and PA bacteria in YBH. It contributes to further understanding of the bacterial community in deep ocean blue holes, and provides bacterial resources for subsequent studies on their adaptation to extreme marine environments.

Calculation method and mechanism of ultimate side resistance of screw pile - Hong-wei Ma; Li Liu; Peng Wang; Song Yuan; Qing-rui He; Xiao-li Yang (Marine Georesources & Geotechnology, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Synergistic activation of anionic redox via cosubstitution to construct high-capacity layered oxide cathode materials for sodium-ion batteries - Haocheng Ji; Wenhai Ji; Haoyu Xue; Guojie Chen; Rui Qi; Zhongyuan Huang; Hui Fang; Mihai Chu; Lele Liu; Zhewen Ma; Shenyang Xu; Jingjun Zhai; et al. (Science Bulletin, 2023)

Occurrence, sources, and risk assessment of pyrethroid insecticides in surface water and tap water from Taihu Lake, China - Rui Wang; Shengwei Zhang; Kaiyan Xiao; Minghong Cai; Hongling Liu (Journal of Environmental Management, 2023)

Balance the rapid release of insecticide microcapsules using double-layer shielding effect when the foliar application - Rui Wang; Song Liu; Feng-shou Sun; Xin Yu; Xiao Liu; Bei-xing Li; Wei Mu; Da-xia Zhang; Feng Liu (Chemical Engineering Journal, 2023)

A High-efficiency blue-LED-excitable NIR-II-emitting MgO:Cr3+,Ni2+ phosphor for future broadband light source toward multifunctional NIR spectroscopy applications - Bo-Mei Liu; Xiao-Xuan Guo; Lu-Yu Cao; Lin Huang; Rui Zou; Zhi Zhou; Jing Wang (Chemical Engineering Journal, 2023)

Microfluidic emulsification techniques for controllable emulsion production and functional microparticle synthesis - Wei Wang; Bing-Yu Li; Mao-Jie Zhang; Yao-Yao Su; Da-Wei Pan; Zhuang Liu; Xiao-Jie Ju; Rui Xie; Yousef Faraj; Liang-Yin Chu (Chemical Engineering Journal, 2023)

Interfacial modulation of organic-inorganic two-dimensional superlattices for efficient electromagnetic wave absorption - Wenjian Wang; Ke Ran; Xingwang Hou; Yilin Huang; Zidong Zhang; Dongxu He; Yuan Fang; Shuai Wang; Yu Liu; Rui Zhao; Xiao-Yu Yang; Weidong Xue (Chemical Engineering Journal, 2023)

Biological Function and Stress Response Mechanism of MYB Transcription Factor Family Genes - Rui Ma; Bowen Liu; Xi Geng; Xiao Ding; Na Yan; Xia Sun; Wenli Wang; Xianzhi Sun; Chengshu Zheng (Journal of Plant Growth Regulation, 2023)

Azospirillum Endophyticum sp. nov., an Endophyte of Paris Polyphylla Smith var. Yunnanensis - Peng-Chao Zhan; Rui-Feng Mao; Cong-Jian Li; Zhen Zhang; Jing-Ran Liu; Mei Tang; Xiao-Yang Zhi; Ling-Ling Yang (Current Microbiology, 2023)

GITRL impairs the immunosuppressive function of MDSCs via PTEN-mediated signaling pathway in experimental Sjögren syndrome - Jie Tian; Beibei Zhang; Qingfang Yuan; Xueqing Sun; Na Peng; Bo Zhu; Chang Liu; Xiaoran Wang; Man Han; Meng Cao; Fan Xiao; Shengjun Wang; et al. (Inflammation Research, 2022)

Effects of coexposure to noise and mixture of toluene, ethylbenzene, xylene, and styrene (TEXS) on hearing loss in petrochemical workers of southern China - Yan Zhang; Yan Liu; Zongxin Li; Xin Liu; Qingfei Chen; Jingyao Qin; Qilong Liao; Rui Du; Qifei Deng; Yongmei Xiao; Xiumei Xing (Environmental Science and Pollution Research, 2022)

Novel and sustainable carboxylation of terminal alkynes and CO2 to alkynyl carboxylic acids using triazolium ionic liquid-modified PMO-supported transition metal acetylacetonate as effective cooperative catalysts - Jing-Rui Li; Chen Chen; Xiao-Bing Liu; Yu-Lin Hu (Environmental Science and Pollution Research, 2022)

SLAH1 is involved in the long-distance transport of Cl− from roots into shoots in the Cl−-tolerant xerophyte Pugionium cornutum under salt stress - Yan-Nong Cui; Xiao-Yu Li; Rui-Wen Liu; Zi-Hua He; Suo-Min Wang; Qing Ma (Plant and Soil, 2022)

Pharmaceutical nanoformulation strategies to spatiotemporally manipulate oxidative stress for improving cancer therapies — exemplified by polyunsaturated fatty acids and other ROS-modulating agents - Rui Xue Zhang; Franky Fuh-Ching Liu; Hoyin Lip; Junhong Liu; Qianrong Zhang; Xiao Yu Wu (Drug Delivery and Translational Research, 2022)

Meshless Surface Wind Speed Field Reconstruction Based on Machine Learning - Nian Liu; Zhongwei Yan; Xuan Tong; Jiang Jiang; Haochen Li; Jiangjiang Xia; Xiao Lou; Rui Ren; Yi Fang (Advances in Atmospheric Sciences, 2022)

Aluminum-activated Malate Transporter 12 is involved in restricting root-to-shoot Cl− transport in Arabidopsis under Cl−-salt stress - Rui-Wen Liu; Jian-Zhen Yuan; Xiao-Yu Li; Yan-Nong Cui; Mei-Mei Cai; Zi-Hua He; Qing Ma (Plant and Soil, 2022)

Monitoring glaciers in the Chenab basin with SBAS InSAR technology - Yue-kai Ding; Rui Liu; Yi-fei Fan; Ling-xiang Zhou; Qin Ji; Hong Zhang; Zuo-lin Xiao (Journal of Mountain Science, 2022)

Magnetic Resonance Imaging Markers of Cerebral Small Vessel Disease in Adults with Moyamoya Disease - Haogeng Sun; Wanjiang Li; Chao Xia; Yutao Ren; Lu Ma; Anqi Xiao; Chao You; Xiaoyu Wang; Rui Tian; Yi Liu (Translational Stroke Research, 2022)

RNAi-Based Transcriptome Suggests Candidate Genes Regulated by ZxNHX1 to Affect The Salt Tolerance of Zygophyllum xanthoxylum - Hai-Shuang Liu; Xiao-Nong Guo; Wei-Wei Chai; Rui-Xin Zhang; Pei-Qin Li; Cui-Min Ma; Qing Ma; Suo-Min Wang (Journal of Plant Growth Regulation, 2022)

The effects of dietary fermented wheat bran polysaccharides on mucosal and serum immune parameters, hepatopancreas antioxidant indicators, and immune-related gene expression of common carp (Cyprinus carpio) juveniles - Rui-Fang Wang; Yuan Wang; Jun Zhang; Mei-Qi Weng; Yu-Hui Liu; Qiu-Yan Cheng; Min Song; Yan-Ping Yang; Xiao-Ping An; Jing-Wei Qi (Aquaculture International, 2022)

Metatranscriptomic analysis of host response and vaginal microbiome of patients with severe COVID-19 - Meng Xiao; Bo Lu; Rui Ding; Xia Liu; Xian Wu; Yaqian Li; Xudong Liu; Lin Qiu; Zhibo Zhang; Jing Xie; Yu Chen; Dong Zhang; et al. (Science China Life Sciences, 2022)

Characteristics and changes of the Himalayas glacial area in China during 1990–2015 - Shu-xian Shi; Li Xing; Yue-kai Ding; Jun Dong; Rui Liu; Qin Ji; Zuo-lin Xiao; Xun Huang (Journal of Mountain Science, 2022)

Full genome sequence of a novel iflavirus from the leafhopper Recilia dorsalis - Rui Ma; Binghua Nie; Jiajia Chen; Keliang Lv; Jiajing Xiao; Renyi Liu (Archives of Virology, 2022)

Roseococcus pinisoli sp. nov., lacking pufL and pufM bacteriochlorophyll a: synthesizing genes - Lei Shen; Miao-miao An; Rui-na Liang; Peng-xiao Liu; Xiang-wei He; Guo-zhu Zhao (Archives of Microbiology, 2022)

Metagenomic analysis reveals wide distribution of phototrophic bacteria in hydrothermal vents on the ultraslow-spreading Southwest Indian Ridge - Hong Chen; Deng Hui Li; Ai Jun Jiang; Xue Gong Li; Shi Jun Wu; Jian Wei Chen; Meng Jie Qu; Xiao Qing Qi; Jie Dai; Rui Zhao; Wei-Jia Zhang; Shan Shan Liu; et al. (Marine Life Science & Technology, 2022)

Experimental study on the pore and solid structures of municipal solid waste under compression based on computed tomography (CT) scans - Han Ke; Ying Liu; Meng Meng; Jie Hu; Shi Yu Zhao; Rui Qin; Xiao Wen Wu (Environmental Science and Pollution Research, 2022)

A novel microRNA regulates cooperation between symbiont and a laterally acquired gene in the regulation of pantothenate biosynthesis within Bemisia tabaci whiteflies - Xiang Sun; Bing‐Qi Liu; Chu‐Qiao Li; Zhan‐Bo Chen; Xiao‐Rui Xu; Jun‐Bo Luan (Molecular Ecology, 2022)
Horizontally transferred genes (HTGs) play a key role in animal symbiosis, and some horizontally transferred genes or proteins are highly expressed in specialized host cells (bacteriocytes). However, it is not clear how HTGs are regulated, but microRNAs (miRNAs) are prime candidates given their previously demonstrated roles in symbiosis and impacts on the expression of host genes. A horizontally acquired PanBC that is highly expressed in whitefly bacteriocytes can cooperate with an obligate symbiont Portiera for pantothenate production, facilitating whitefly performance and Portiera titre. Here, we found that a whitefly miRNA, novel‐m0780‐5p, was up‐regulated and its target panBC was down‐regulated in Portiera ‐eliminated whiteflies. This miRNA was located in the cytoplasmic region of whitefly bacteriocytes. Injection of novel‐m0780‐5p agomir reduced the expression of PanBC in whitefly bacteriocytes, while injection of novel‐m0780‐5p antagomir enhanced PanBC expression. Agomir injection also reduced the pantothenate level, Portiera titre and whitefly performance. Supplementation with pantothenate restored Portiera titre and the fitness of agomir‐injected whiteflies. Thus, we demonstrate that a whitefly miRNA regulates panBC ‐mediated host–symbiont collaboration required for pantothenate synthesis, benefiting the whitefly– Portiera symbiosis. Both panBC and novel‐m0780‐5p are present in the genomes of six Bemisia tabaci species. The expression of a novel miRNA in multiple B . tabaci species suggests that the miRNA evolved after panBC acquisition, and allowed this gene to be more tightly regulated. Our discovery provides the first account of a HTG being regulated by a miRNA from the host genome, and suggests key roles for interactions between miRNAs and HTGs in the functioning of symbiosis.

Two new dammarane-type triterpenoids from the green walnut husks of Juglans mandshurica Maxim - Yuan-Yuan Zhou; Hui-Rui Gao; Hong-Juan Song; Dan-Da Ma; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Xiao-Li Wang; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2022)

Flavonoid glycosides from the nectar of Camellia reticulata Lindl. - Xin-Lan Chen; Xing-Rong Peng; Xue-Yang Gong; Yi-Qiu Liu; Zhuo Qing; Xiao-Xiao Ren; Rui Su; Li-Ming Fang; Ming-Hua Qiu; Kun Dong (Natural Product Research, 2022)

Rare soil species impact the rhizosphere bacterial communities and cadmium uptake by Lolium multiflorum Lam. - Chenxin Gao; Yan Zhu; Xian Xiao; Rui Liu; Xuesong Zhu; Yuan Zhao (Plant and Soil, 2022)

Petrogenesis and tectonic setting of the early-middle triassic subduction-related granite in the eastern segment of East Kunlun: evidences from petrology, geochemistry, and zircon U-Pb-Hf isotopes - Zuo-Chen Li; Xian-Zhi Pei; Paul D. Bons; Rui-Bao Li; Lei Pei; Guo-Chao Chen; You-Xin Chen; Cheng-Jun Liu; Meng Wang; Shao-Wei Zhao; Xiao-Bing Li; Feng Gao (International Geology Review, 2022)

QTL mapping and candidate gene prediction for fiber yield and quality traits in a high-generation cotton chromosome substitution line with Gossypium barbadense segments - Quanwei Lu; Pengtao Li; Rui Yang; Xianghui Xiao; Ziyin Li; Qiuyu Wu; Juwu Gong; Qun Ge; Aiying Liu; Shengli Du; Jundi Wang; Yuzhen Shi; et al. (Molecular Genetics and Genomics, 2022)

Oxygen Metabolism-induced Stress Response Underlies Heart–brain Interaction Governing Human Consciousness-breaking and Attention - Xiao-Juan Xue; Rui Su; Ze-Feng Li; Xiao-Ou Bu; Peng Dang; Si-Fang Yu; Zhi-Xin Wang; Dong-Mei Chen; Tong-Ao Zeng; Ming Liu; Hai-Lin Ma; De-Long Zhang (Neuroscience Bulletin, 2022)

Janibacter endophyticus sp. nov., an Endophytic Actinobacterium Isolated from the Root of Paris polyphylla Smith var. Yunnanensis - Zhen Zhang; En-Min Zhou; Cong-Jian Li; Xing-Wang Jiang; Rui-Feng Mao; Jing-Ran Liu; Xiao-Yang Zhi; Ling-Ling Yang (Current Microbiology, 2022)

The responses of detoxification enzyme and gene expression in western flower thrips, Frankliniella occidentalis, to new challenging hosts - Wen-Bo Yue; Jun-Rui Zhi; Li Liu; Xiao-Lin Hou; Mao Ye (Arthropod-Plant Interactions, 2022)

Neobacillus paridis sp. nov., an endophyte of Paris polyphylla Smith var. yunnanensis - Peng-Chao Zhan; Cong-Jian Li; Zhen Zhang; Rui-Feng Mao; Jing-Ran Liu; Xing-Wang Jiang; Xiao-Yang Zhi; Ling-Ling Yang (Archives of Microbiology, 2022)

Correction to: Isorhamnetin protects against cardiac hypertrophy through blocking PI3K–AKT pathway - Lu Gao; Rui Yao; Yuzhou Liu; Zheng Wang; Zhen Huang; Binbin Du; Dianhong Zhang; Leiming Wu; Lili Xiao; Yanzhou Zhang (Molecular and Cellular Biochemistry, 2022)

Kangiella shandongensis sp. nov., a novel species isolated from saltern in Yantai, China - Li-Yang Peng; Rui Yin; Shu-Kun Gao; Hui-Ning Jiang; Xiao-Xiao Liu; Yu Ma; Yan-Xia Zhou (Antonie van Leeuwenhoek, 2022)

Conservation planning on China's borders with Myanmar, Laos, and Vietnam - Lin Wang; Bin Yang; Yang Bai; Xiaoqiang Lu; Richard T. Corlett; Yunhong Tan; Xiao‐Yong Chen; Jianguo Zhu; Yan Liu; Rui‐Chang Quan (Conservation Biology, 2021)
Transboundary conservation is playing an increasingly important role in maintaining ecosystem integrity and halting biodiversity loss caused by anthropogenic activities. However, lack of information on species distributions in transboundary regions and understanding of the threats in these areas impairs conservation. We developed a spatial conservation plan for the transboundary areas between Yunnan province, southwestern China, and neighboring Myanmar, Laos, and Vietnam in the Indo‐Burma biodiversity hotspot. To identify priority areas for conservation and restoration, we determined species distribution patterns and recent land‐use changes and examined the spatiotemporal dynamics of the connected natural forest, which supports most species. We assessed connectivity with equivalent connected area (ECA), which is the amount of reachable habitat for a species. An ECA incorporates the presence of habitat in a patch and the amount of habitat in other patches within dispersal distance. We analyzed 197,845 locality records from specimen collections and monographs for 21,004 plant and vertebrate species. The region of Yunnan immediately adjacent to the international borders had the highest species richness, with 61% of recorded species and 56% of threatened vertebrates, which suggests high conservation value. Satellite imagery showed the area of natural forest in the border zone declined by 5.2% (13,255 km 2 ) from 1995 to 2018 and monoculture plantations increased 92.4%, shrubland 10.1%, and other cropland 6.2%. The resulting decline in connected natural forest reduced the amount of habitat, especially for forest specialists with limited dispersal abilities. The most severe decline in connectivity was along the Sino‐Vietnamese border. Many priority areas straddle international boundaries, indicating demand and potential for establishing transboundary protected areas. Our results illustrate the importance of bi‐ and multilateral cooperation to protect biodiversity in this region and provide guidance for future conservation planning and practice.

Late Silurian to early Devonian development of the Chingiz accretion arc, West Junggar: insights into accretion arc evolution in the Central Asia Orogenic Belt - Yichao Chen; Ji’En Zhang; Wenjiao Xiao; Renjie Zhou; Shuaihua Song; Zhiyong Zhang; Songjian Ao; Miao Sang; Qian W.L. Zhang; Rui Li; Zhen M.G. Li; Yin Liu; et al. (International Geology Review, 2021)

Chronic Exposure to Hypoxia Inhibits Myelinogenesis and Causes Motor Coordination Deficits in Adult Mice - Lin Chen; Shu-Yu Ren; Rui-Xue Li; Kun Liu; Jing-Fei Chen; Yu-Jian Yang; Yong-Bin Deng; Han-Zhi Wang; Lan Xiao; Feng Mei; Fei Wang (Neuroscience Bulletin, 2021)
Exposure to chronic hypoxia is considered to be a risk factor for deficits in brain function in adults, but the underlying mechanisms remain largely unknown. Since active myelinogenesis persists in the adult central nervous system, here we aimed to investigate the impact of chronic hypoxia on myelination and the related functional consequences in adult mice. Using a transgenic approach to label newly-generated myelin sheaths ( NG2-CreER TM ; Tau-mGFP ), we found that myelinogenesis was highly active in most brain regions, such as the motor cortex and corpus callosum. After exposure to hypoxia (10% oxygen) 12 h per day for 4 weeks, myelinogenesis was largely inhibited in the 4-month old brain and the mice displayed motor coordination deficits revealed by the beam-walking test. To determine the relationship between the inhibited myelination and functional impairment, we induced oligodendroglia-specific deletion of the transcription factor Olig2 by tamoxifen ( NG2-CreER TM ; Tau-mGFP; Olig2 fl/fl ) in adult mice to mimic the decreased myelinogenesis caused by hypoxia. The deletion of Olig2 inhibited myelinogenesis and consequently impaired motor coordination, suggesting that myelinogenesis is required for motor function in adult mice. To understand whether enhancing myelination could protect brain functions against hypoxia, we treated hypoxic mice with the myelination-enhancing drug-clemastine, which resulted in enhanced myelogenesis and improved motor coordination. Taken together, our data indicate that chronic hypoxia inhibits myelinogenesis and causes functional deficits in the brain and that enhancing myelinogenesis protects brain functions against hypoxia-related deficits.

Qingbo, a common cyprinid fish, responds diversely in behavior and locomotion to predators with different hunting modes - Cheng Fu; Lian-Chun Yi; Wen-Pei Wu; Chun-Xiao Sun; Rui-Na Liu; Shi-Jian Fu (Fish Physiology and Biochemistry, 2021)

Research progress in bioremediation of petroleum pollution - Yong Yang; Zhan-Wei Zhang; Rui-Xia Liu; Hai-Yan Ju; Xue-Ke Bian; Wan-Ze Zhang; Chuan-Bo Zhang; Ting Yang; Bing Guo; Chen-Lei Xiao; He Bai; Wen-Yu Lu (Environmental Science and Pollution Research, 2021)

Inactivation and Removal Technologies for Algal-Bloom Control: Advances and Challenges - Ming-ming Zhan; Pei-rui Liu; Xiao-ya Liu; Yu Hong; Xing Xie (Current Pollution Reports, 2021)

Dicer Deletion in Astrocytes Inhibits Oligodendroglial Differentiation and Myelination - Kun Liu; Bin Yu; Jing-Fei Chen; Rui-Xue Li; Lin Chen; Shu-Yu Ren; Fei Wang; Feng Mei; Lan Xiao (Neuroscience Bulletin, 2021)
Increasing evidence has shown that astrocytes are implicated in regulating oligodendrocyte myelination, but the underlying mechanisms remain largely unknown. To understand whether microRNAs in astrocytes function in regulating oligodendroglial differentiation and myelination in the developing and adult CNS, we generated inducible astrocyte-specific Dicer conditional knockout mice (hGFAP-CreERT; Dicer fl/fl). By using a reporter mouse line (mT/mG), we confirmed that hGFAP-CreERT drives an efficient and astrocyte-specific recombination in the developing CNS, upon tamoxifen treatment from postnatal day 3 (P3) to P7. The Dicer deletion in astrocytes resulted in inhibited oligodendroglial differentiation and myelination in the developing CNS of Dicer cKO mice at P10 and P14, and did not alter the densities of neurons or axons, indicating that Dicer in astrocytes is required for oligodendrocyte myelination. Consequently, the Dicer deletion in astrocytes at P3 resulted in impaired spatial memory and motor coordination at the age of 9 weeks. To understand whether Dicer in astrocytes is also required for remyelination, we induced Dicer deletion in 3-month-old mice and then injected lysolecithin into the corpus callosum to induce demyelination. The Dicer deletion in astrocytes blocked remyelination in the corpus callosum 14 days after induced demyelination. Together, our results indicate that Dicer in astrocytes is required for oligodendroglia myelination in both the developing and adult CNS.

Seasonal variations of water quality response to land use metrics at multi-spatial scales in the Yangtze River basin - Jiahui Xu; Rui Liu; Maofei Ni; Jing Zhang; Qin Ji; Zuolin Xiao (Environmental Science and Pollution Research, 2021)

Modeling and insights into molecular basis of low molecular weight respiratory sensitizers - Xueyan Cui; Rui Yang; Siwen Li; Juan Liu; Qiuyun Wu; Xiao Li (Molecular Diversity, 2021)

Contamination assessment, health risk evaluation, and source identification of heavy metals in the soil-rice system of typical agricultural regions on the southeast coast of China - Yanjun Ren; Meng Lin; Qingming Liu; Zhonghao Zhang; Xufeng Fei; Rui Xiao; Xiaonan Lv (Environmental Science and Pollution Research, 2021)

Impact process of the aquitard to regional arsenic accumulation of the underlying aquifer in Central Yangtze River Basin - Cong Xiao; Teng Ma; Yao Du; Yanjun Liu; Rui Liu; Dongtao Zhang; Juan Chen (Environmental Geochemistry and Health, 2021)

Arbuscular mycorrhizal colonization rate of an exotic plant, Galinsoga quadriradiata, in mountain ranges changes with altitude - Gang Liu; Rui-Ling Liu; Wen-Gang Zhang; Ying-Bo Yang; Xiao-Qiong Bi; Ming-Zhu Li; Xiao-Yan Chen; Hua Nie; Zhi-Hong Zhu (Mycorrhiza, 2021)

Small RNA Sequencing Analysis of Germinating Single-bud Seedcane Sett in Sugarcane - Kai-Chao Wu; Lin Xu; Zhi-Nian Deng; Tian Pang; Rong-Hua Zhang; Yi-Jie Li; Xiao-Yan Liu; Cheng-Feng Huang; Wen-Xian Qin; Jian-Feng Wei; Li-Ping Wei; Yang-Rui Li; et al. (Sugar Tech, 2021)

Activating transcription factor 3 is a potential target and a new biomarker for the prognosis of atherosclerosis - Weiwei Qin; Huiyu Yang; Gaizhen Liu; Rui bai; Yunfei Bian; Zhiming Yang; Chuanshi Xiao (Human Cell, 2021)

The short-term effect of PM2.5/O3 on daily mortality from 2013 to 2018 in Hefei, China - Xinmiao Sui; Junqing Zhang; Qi Zhang; Shu Sun; Ruoqian Lei; Chao Zhang; Han Cheng; Liu Ding; Rui Ding; Changchun Xiao; Xiaoru Li; Jiyu Cao (Environmental Geochemistry and Health, 2021)

Three new andrastin derivatives from the endophytic fungus Penicillium vulpinum - Yu-Yue Qin; Xi-Shan Huang; Xiao-Bo Liu; Tu-Xiang Mo; Zhao-Long Xu; Ben-Chao Li; Xiao-Ya Qin; Jun Li; Till F. Schӓberle; Rui-Yun Yang (Natural Product Research, 2020)

Neonatal curcumin treatment restores hippocampal neurogenesis and improves autism-related behaviors in a mouse model of autism - Hongyu Zhong; Rui Xiao; Ruotong Ruan; Hui Liu; Xin Li; Yun Cai; Jinghui Zhao; Xiaotang Fan (Psychopharmacology, 2020)

Elevated plasma phage load as a marker for intestinal permeability in leukemic patients - Xue-rui Yin; Ping Liu; Xi Xu; Ying Xia; Kai-zhao Huang; Qiong-dan Wang; Mei-mei Lai; Qi-gui Yu; Xiao-qun Zheng (Medical Microbiology and Immunology, 2020)

Two new anthraquinone derivatives and one new triarylbenzophenone analog from Selaginella tamariscina - Rui Liu; Hui Zou; Zhen-Xing Zou; Fei Cheng; Xia Yu; Ping-Sheng Xu; Xiao-Min Li; Dai Li; Kang-Ping Xu; Gui-Shan Tan (Natural Product Research, 2020)

High expression of long non-coding RNA Linc-A associates with poor survival in patients with colorectal cancer - Chong Zhao; Can Gan; Yang Xiao; Rui Liu; Linhao Zhang; Tian Lan; Yanting Ye; Huan Tong; Zhiyin Huang; Chengwei Tang; Jinhang Gao (Molecular Biology Reports, 2020)

Ultrafiltration and microfiltration membrane performance, cleaning, and flux recovery for microalgal harvesting - Rui Liu; Lan Wang; Li Yang; Qingling Liu; Yunxiao Gao; Jing Ye; Jingrong Xiao; Qiang Hu; Xuezhi Zhang (Journal of Applied Phycology, 2020)

Evaluating Spatial Heterogeneity of Land Surface Hydrothermal Conditions in the Heihe River Basin - Yuan Zhang; Shaomin Liu; Xiao Hu; Jianghao Wang; Xiang Li; Ziwei Xu; Yanfei Ma; Rui Liu; Tongren Xu; Xiaofan Yang (Chinese Geographical Science, 2020)

Low-frequency swell noise suppression based on U-Net - Rui-qi Zhang; Peng Song; Bao-hua Liu; Xiao-bo Zhang; Jun Tan; Zhi-hui Zou; Chuang Xie; Shao-wen Wang (Applied Geophysics, 2020)

A new phenanthropyran and a new biphenanthrene from the rhizomes of Dioscorea septemloba and their antioxidant activities - Tao He; Yi Liu; Rui-Feng Xiong; Xiao-Yu Li; Shou-Feng Wang; Chun-Ru Cheng (Natural Product Research, 2020)

Reductions in water, soil and nutrient losses and pesticide pollution in agroforestry practices: a review of evidence and processes - Xiai Zhu; Wenjie Liu; Jin Chen; L. Adrian Bruijnzeel; Zhun Mao; Xiaodong Yang; Rémi Cardinael; Fan-Rui Meng; Roy C. Sidle; Steffen Seitz; Vimala D. Nair; Kazuki Nanko; et al. (Plant and Soil, 2020)

Prefrontal Nectin3 Reduction Mediates Adolescent Stress-Induced Deficits of Social Memory, Spatial Working Memory, and Dendritic Structure in Mice - Hong-Li Wang; Ji-Tao Li; Han Wang; Ya-Xin Sun; Rui Liu; Xiao-Dong Wang; Yun-Ai Su; Tian-Mei Si (Neuroscience Bulletin, 2020)
Chronic stress may disrupt the normal neurodevelopmental trajectory of the adolescent brain (especially the prefrontal cortex) and contribute to the pathophysiology of stress-related mental illnesses, but the underlying molecular mechanisms remain unclear. Here, we investigated how synaptic cell adhesion molecules (e.g., nectin3) are involved in the effects of adolescent chronic stress on mouse medial prefrontal cortex (mPFC). Male C57BL/6N mice were subjected to chronic social instability stress from postnatal days 29 to 77. One week later, the mice exposed to chronic stress exhibited impaired social recognition and spatial working memory, simplified dendritic structure, and reduced spine density in the mPFC. Membrane localization of nectin3 was also altered, and was significantly correlated with behavioral performance. Furthermore, knocking down mPFC nectin3 expression by adeno-associated virus in adolescent mice reproduced the stress-induced changes in behavior and mPFC morphology. These results support the hypothesis that nectin3 is a potential mediator of the effects of adolescent chronic stress on prefrontal structural and functional abnormalities.

Pseudomonas Saliphila sp. nov., a Bacterium Isolated from Oil-Well Production Water in Qinghai Oilfield of China - Xiao-Juan Zhang; Hong-Can Liu; Yu-Guang Zhou; Xiao-Lei Wu; Yong Nie; Qi-Rui Li; Mei-Zhu Wang; Liang Zhao; Man Cai; Ying-Qian Kang (Current Microbiology, 2020)

α -Tetralone glycosides from the green walnut husks of Juglans mandshurica Maxim. and their cytotoxic activities - Yuan-Yuan Zhou; Shuang Guo; Ying Wang; Hong-Juan Song; Hui-Rui Gao; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2020)

Characterization of a Rapeseed Anthocyanin-More Mutant with Enhanced Resistance to Sclerotinia sclerotiorum - Rui Liu; Li-Na Ding; Ming Li; Wei Cao; Yu-Kang Wang; Wei-Jie Wang; Yan-Kun Yu; Zheng Wang; Ke-Ming Zhu; Xiao-Li Tan (Journal of Plant Growth Regulation, 2020)

Assessment of genetic diversity in Camellia oleifera Abel. accessions using inter-simple sequence repeat (ISSR) and start codon targeted (SCoT) polymorphic markers - Pu Xiao; Huhu Liu; Dongping Wang; Wenyan Tang; Hui Yang; Chong Wang; Zhilong He; Rui Wang; Xiangnan Wang; Xiangyang Lu; Yongzhong Chen; Yun Tian (Genetic Resources and Crop Evolution, 2020)

Anti-phytopathogenic Bacterial Metabolites From the Seaweed-Derived Fungus Aspergillus sp. D40 - Rui-Huan Huang; Wei Lin; Peng Zhang; Jian-Yang Liu; Dan Wang; Yi-Qiang Li; Xiao-Qiang Wang; Cheng-Sheng Zhang; Wei Li; Dong-Lin Zhao (Frontiers in Marine Science, 2020)

Tracing solute sources and carbon dynamics under various hydrological conditions in a karst river in southwestern China - Jing Liu; Bo Chen; Zhu-Yan Xu; Yuan Wei; Zhi-Hua Su; Rui Yang; Yong-Xue Ji; Xiao-Dan Wang; Li-Li Zhang; Ning An; Fei Yang (Environmental Science and Pollution Research, 2020)

Application of metagenomic next-generation sequencing for bronchoalveolar lavage diagnostics in critically ill patients - Ying Li; Bing Sun; Xiao Tang; Ya-lan Liu; Hang-yong He; Xu-yan Li; Rui Wang; Fei Guo; Zhao-hui Tong (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Risk factors and clinical characteristics of tacrolimus-induced acute nephrotoxicity in children with nephrotic syndrome: a retrospective case-control study - Ping Gao; Xin-Lei Guan; Rui Huang; Xiao-Fang Shang-guan; Jiang-Wei Luan; Mao-Chang Liu; Hua Xu; Xiao-Wen Wang (European Journal of Clinical Pharmacology, 2020)

Advances in research of the mid-deep South China Sea circulation - Dongxiao Wang; Qiang Wang; Shuqun Cai; Xiaodong Shang; Shiqiu Peng; Yeqiang Shu; Jingen Xiao; Xiaohui Xie; Zhiwei Zhang; Zhiqiang Liu; Jian Lan; Dake Chen; et al. (Science China Earth Sciences, 2019)

De novo assembly and transcriptome analysis of differentially expressed genes relevant to variegation in hawthorn flowers - Wei Ji; Wei Zhao; Rong-Chen Liu; Xiao-Bo Jiao; Kai Han; Zhong-Yi Yang; Mei-Ying Gao; Rui Ren; Xiu-Juan Fan; Ming-Xia Yang (Plant Biotechnology Reports, 2019)

Thermus caldilimi sp. nov., a thermophilic bacterium isolated from a geothermal area - Meng-Meng Li; Wen-Dong Xian; Xiao-Tong Zhang; Yi-Rui Yin; En-Min Zhou; Yi-Ping Ding; Lan Liu; Bao-Zhu Fang; Wen-Jun Li (Antonie van Leeuwenhoek, 2019)

Wind and sand control by an oasis protective system: a case from the southeastern edge of the Tengger Desert, China - Yun-hu Xie; Xiao-hong Dang; Zhong-ju Meng; Hong-tao Jiang; Xiao-jia Li; Rui-ping Zhou; Dan-dan Zhou; Xiao-xi Liu; Jing Ding; Xue-qin Wu; Yu-hao Wang; Chun-xing Hai; et al. (Journal of Mountain Science, 2019)

QTL mapping and genetic effect of chromosome segment substitution lines with excellent fiber quality from Gossypium hirsutum × Gossypium barbadense - Shao-qi Li; Ai-ying Liu; Ling-lei Kong; Ju-wu Gong; Jun-wen Li; Wan-kui Gong; Quan-wei Lu; Peng-tao Li; Qun Ge; Hai-hong Shang; Xiang-hui Xiao; Rui-xian Liu; et al. (Molecular Genetics and Genomics, 2019)

Synthesis and antitumor evaluation of novel fused heterocyclic 1,2,4-triazolo[3,4-b]-1,3,4-thiadiazole derivatives - Xiao-Jia Liu; Hai-Ying Liu; Hai-Xin Wang; Yan-Ping Shi; Rui Tang; Shuai Zhang; Bao-Quan Chen (Medicinal Chemistry Research, 2019)

Carbon Monoxide Attenuates High Salt-Induced Hypertension While Reducing Pro-inflammatory Cytokines and Oxidative Stress in the Paraventricular Nucleus - Dong-Dong Zhang; Yan-Feng Liang; Jie Qi; Kai B. Kang; Xiao-Jing Yu; Hong-Li Gao; Kai-Li Liu; Yan-Mei Chen; Xiao-Lian Shi; Guo-Rui Xin; Li-Yan Fu; Yu-Ming Kang; et al. (Cardiovascular Toxicology, 2019)

A new triterpene from the green walnut husks of Juglans mandshurica Maxim - Yuan-Yuan Zhou; Hong-Juan Song; Shuang Guo; Ying Wang; Hui-Rui Gao; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Bing-You Yang; Hai-Xue Kuang (Journal of Natural Medicines, 2019)

Physiological and biochemical responses of Dunaliella salina exposed to acrylamide - Na Ling; Hong-Xiu Li; Hong-Shi Guo; Xiu-Ming Cao; Xiao-Rui Liu (Biologia, 2019)

Two new sesquiterpenes from cultures of the higher fungus Pholiota nameko - Xiao-Yan Yang; Wan-Rong Niu; Rui-Ting Li; Xiu-Ming Cui; Ji-Kai Liu (Natural Product Research, 2019)

Impact of Seed Coating Agents on Single-Bud Seedcane Germination and Plant Growth in Commercial Sugarcane Cultivation - Yong-Jian Liang; Xiao-Qiu Zhang; Liu Yang; Xi-Hui Liu; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2019)

Effects of periodical drying and non-drying on nutrient content and desiccation tolerance of an intertidal Pyropia yezoensis strain subject to farming conditions - Wen Jun Wang; Xiao Lei Li; Teng Qing Sun; Zhou Rui Liang; Fu Li Liu; Xiu Tao Sun; Fei Jiu Wang (Journal of Applied Phycology, 2019)

Expression and characterisation of a pH and salt tolerant, thermostable and xylose tolerant recombinant GH43 β-xylosidase from Thermobifida halotolerans YIM 90462T for promoting hemicellulose degradation - Yi-Rui Yin; Wen-Dong Xian; Ming-Xian Han; En-Min Zhou; Lan Liu; Dalal Hussien M. Alkhalifah; Wael N. Hozzein; Min Xiao; Wen-Jun Li (Antonie van Leeuwenhoek, 2019)

Genomic characterization and pathogenicity of porcine deltacoronavirus strain CHN-HG-2017 from China - Meng-Jia Zhang; De-Jian Liu; Xiao-Li Liu; Xing-Yi Ge; Anan Jongkaewwattana; Qi-Gai He; Rui Luo (Archives of Virology, 2019)

Characterization and phylogenetic analysis of the complete maternal mitochondrial genome of freshwater mussel Aculamprotula scripta (Bivalvia: Unionidae: Unioninae) - Rui-Wen Wu; Sa Wang; Yi-Tong Liu; Xiong-Jun Liu; Chun-Hua Zhou; Shan Ouyang; Xiao-Ping Wu (Conservation Genetics Resources, 2018)

Acupuncture Prevents the Impairment of Hippocampal LTP Through β1-AR in Vascular Dementia Rats - Ling-Yong Xiao; Xue-Rui Wang; Jing-Wen Yang; Yang Ye; Wen Zhu; Yan Cao; Si-Ming Ma; Cun-Zhi Liu (Molecular Neurobiology, 2018)

Precipitation characteristics over the steep slope of the Himalayas in rainy season observed by TRMM PR and VIRS - Yunfei Fu; Xiao Pan; Tao Xian; Guosheng Liu; Lei Zhong; Qi Liu; Rui Li; Yu Wang; Ming Ma (Climate Dynamics, 2018)

The effects of codon usage on the formation of secondary structures of nucleocapsid protein of peste des petits ruminants virus - Xiao-xia Ma; Yi-ning Wang; Xiao-an Cao; Xue-rui Li; Yong-sheng Liu; Jian-hua Zhou; Xue-peng Cai (Genes & Genomics, 2018)

Review: Water–rock interactions and related eco-environmental effects in typical land subsidence zones of China - Teng Ma; Yao Du; Rui Ma; Cong Xiao; Yanjun Liu (Hydrogeology Journal, 2018)

Dietary exposure to cadmium of Shenzhen adult residents from a total diet study - Zhou Wang; Liubo Pan; Guihua Liu; Huimin Zhang; Jinzhou Zhang; Jie Jiang; Ying Xiao; Weibin Bai; Rui Jiao; Wei Huang (Food Additives & Contaminants: Part A, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Different behavioral, neural and neuropeptide responses of fathers to their own and to alien pups in mandarin voles - Wei Yuan; Xiang-Ping Yang; Peng Yu; Rui Jia; Fa-Dao Tai; Bin Wei; Xiao Liu; Lei-Ge Ma (Journal of Comparative Physiology A, 2018)

Periodical drying or no drying during aquaculture affects the desiccation tolerance of a sublittoral Pyropia yezoensis strain - Xiao-lei Li; Wen-jun Wang; Fu-li Liu; Zhou-rui Liang; Xiu-tao Sun; Hai-qing Yao; Fei-jiu Wang (Journal of Applied Phycology, 2018)

Phenylpropanoids from the fruits of Nicandra physaloides and their anti-inflammatory activities - Bing You Yang; Yan Liu; Hai Bing Jiang; Zhen Peng Xu; Rui Guo; Rui Wang; Xiao Mao Li; Hai Xue Kuang (Natural Product Research, 2017)

Profiling methyl jasmonate-responsive transcriptome for understanding induced systemic resistance in whitebark pine (Pinus albicaulis) - Jun-Jun Liu; Holly Williams; Xiao Rui Li; Anna W. Schoettle; Richard A. Sniezko; Michael Murray; Arezoo Zamany; Gary Roke; Hao Chen (Plant Molecular Biology, 2017)

A new biphenyl derivative from the mangrove endophytic fungus Phomopsis longicolla HL-2232 - Xiao-Bao Li; Guang-Ying Chen; Rui-Jie Liu; Cai-Juan Zheng; Xin-Ming Song; Chang-Ri Han (Natural Product Research, 2017)

Efficacy and safety of probiotic-supplemented triple therapy for eradication of Helicobacter pylori in children: a systematic review and network meta-analysis - Jue-Rong Feng; Fan Wang; Xiao Qiu; Lynne V. McFarland; Peng-Fei Chen; Rui Zhou; Jing Liu; Qiu Zhao; Jin Li (European Journal of Clinical Pharmacology, 2017)

Molecular Mechanisms of Vascular Dementia: What Can Be Learned from Animal Models of Chronic Cerebral Hypoperfusion? - Si-Qi Du; Xue-Rui Wang; Ling-Yong Xiao; Jian-Feng Tu; Wen Zhu; Tian He; Cun-Zhi Liu (Molecular Neurobiology, 2017)

Holocene activity evidence on the southeast boundary fault of Heqing basin, middle segment of Heqing-Eryuan fault zone, West Yunnan Province, China - Chang-bin Sun; De-wen Li; Xiao-ming Shen; Yan-rui Kang; Rui Liu; Ya-jiao Zhang (Journal of Mountain Science, 2017)

Erratum to: Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling‑Ling Zhang; Hu Chen; Mi Luo; Xiao‑Wei Zhang; Mei Deng; Jian Ma; Peng‑Fei Qi; Ji‑Rui Wang; Guo‑Yue Chen; Ya‑Xi Liu; Zhi‑En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling-Ling Zhang; Hu Chen; Mi Luo; Xiao-Wei Zhang; Mei Deng; Jian Ma; Peng-Fei Qi; Ji-Rui Wang; Guo-Yue Chen; Ya-Xi Liu; Zhi-En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

Isorhamnetin protects against cardiac hypertrophy through blocking PI3K–AKT pathway - Lu Gao; Rui Yao; Yuzhou Liu; Zheng Wang; Zhen Huang; Binbin Du; Dianhong Zhang; Leiming Wu; Lili Xiao; Yanzhou Zhang (Molecular and Cellular Biochemistry, 2017)

The Research on the Relationship of RAGE, LRP-1, and Aβ Accumulation in the Hippocampus, Prefrontal Lobe, and Amygdala of STZ-Induced Diabetic Rats - Lou-Yan Ma; Yu-Lang Fei; Xiao-Ye Wang; Song-Di Wu; Jun-Hui Du; Mei Zhu; Long Jin; Ming Li; Hai-Long Li; Jia-Jia Zhai; Lu-Peng Ji; Ran-Ran Ma; et al. (Journal of Molecular Neuroscience, 2017)

Phytotoxicity of CeO2 nanoparticles on radish plant (Raphanus sativus) - Xin Gui; Mengmeng Rui; Youhong Song; Yuhui Ma; Yukui Rui; Peng Zhang; Xiao He; Yuanyuan Li; Zhiyong Zhang; Liming Liu (Environmental Science and Pollution Research, 2017)

Cd Content in Sugarcane and Its Relationship with Soil Factors - Hui-Ping Ou; Liu-Qiang Zhou; Xi-Hui Liu; Jin-Sheng Huang; Yan Zeng; Ru-Lin Xie; Xiao-Hui Zhu; Hong-Wei Tan; Yang-Rui Li (Sugar Tech, 2017)

MicroRNA-146a Promotes Oligodendrogenesis in Stroke - Xian Shuang Liu; Michael Chopp; Wan Long Pan; Xin Li Wang; Bao Yan Fan; Yi Zhang; Haifa Kassis; Rui Lan Zhang; Xiao Ming Zhang; Zheng Gang Zhang (Molecular Neurobiology, 2017)

Early postnatal stress suppresses the developmental trajectory of hippocampal pyramidal neurons: the role of CRHR1 - Rui Liu; Xiao-Dun Yang; Xue-Mei Liao; Xiao-Meng Xie; Yun-Ai Su; Ji-Tao Li; Xiao-Dong Wang; Tian-Mei Si (Brain Structure and Function, 2016)

Neuroprotective Effects of a PSD-95 Inhibitor in Neonatal Hypoxic-Ischemic Brain Injury - Baofeng Xu; Ai-Jiao Xiao; Wenliang Chen; Ekaterina Turlova; Rui Liu; Andrew Barszczyk; Christopher L. F. Sun; Ling Liu; Michael Tymianski; Zhong-Ping Feng; Hong-Shuo Sun (Molecular Neurobiology, 2016)

Molecular detection and genome characterization of porcine circovirus type 2 in rats captured on commercial swine farms - Shao-Lun Zhai; Sheng-Nan Chen; Wei Liu; Xiao-Peng Li; Su-Fang Deng; Xiao-Hui Wen; Man-Lin Luo; Dian-Hong Lv; Wen-Kang Wei; Rui-Ai Chen (Archives of Virology, 2016)

New alkaloids from the leaves of Evodia rutaecarpa - Xiao Xia; Jian-Guang Luo; Rui-Huan Liu; Ming-Hua Yang; Ling-Yi Kong (Natural Product Research, 2016)

Expression Profile of MiR-128 in the Astrocytoma Patients and Cell Lines - Jingjing Xu; Yuqiong Liu; Si Guo; Shengli Ma; Lin Xiao; Na Wei; Rui Xue (Molecular Neurobiology, 2016)

Effects of light curing modes and ethanol-wet bonding on dentin bonding properties - Mu-zi Li; Jin-rui Wang; Hong Liu; Xia Wang; Kang Gan; Xiu-ju Liu; De-li Niu; Xiao-qing Song (Journal of Zhejiang University-SCIENCE B, 2016)

Emerging role of adipokines in systemic lupus erythematosus - Hong-Miao Li; Tian-Ping Zhang; Rui-Xue Leng; Xiang-Pei Li; Xiao-Mei Li; Hai-Rong Liu; Dong-Qing Ye; Hai-Feng Pan (Immunologic Research, 2016)

Dietary exposure to lead of adults in Shenzhen city, China - Liubo Pan; Zhou Wang; Zhaoqiong Peng; Guihua Liu; Huimin Zhang; Jinzhou Zhang; Jie Jiang; Nimal Pathiraja; Ying Xiao; Rui Jiao; Wei Huang (Food Additives & Contaminants: Part A, 2016)

Serum CXCL12 Levels as a Novel Predictor of Future Stroke Recurrence in Patients with Acute Ischemic Stroke - Xiao-Lin Gu; Lin Liu; Xiang-Dong Lu; Zhen-Rui Liu (Molecular Neurobiology, 2016)

A mutation in SLC22A4 encoding an organic cation transporter expressed in the cochlea strial endothelium causes human recessive non-syndromic hearing loss DFNB60 - Mariem Ben Said; M’hamed Grati; Takahiro Ishimoto; Bing Zou; Imen Chakchouk; Qi Ma; Qi Yao; Bouthaina Hammami; Denise Yan; Rahul Mittal; Noritaka Nakamichi; Abdelmonem Ghorbel; et al. (Human Genetics, 2016)

CXCL16 upregulates RANKL expression in rheumatoid arthritis synovial fibroblasts through the JAK2/STAT3 and p38/MAPK signaling pathway - Chang-hong Li; Lin-lin Xu; Jin-xia Zhao; Lin Sun; Zhong-qiang Yao; Xiao-li Deng; Rui Liu; Lin Yang; Rui Xing; Xiang-yuan Liu (Inflammation Research, 2016)

ISRM Suggested Method for In Situ Microseismic Monitoring of the Fracturing Process in Rock Masses - Ya-Xun Xiao; Xia-Ting Feng; John A. Hudson; Bing-Rui Chen; Guang-Liang Feng; Jian-Po Liu (Rock Mechanics and Rock Engineering, 2016)

The Prevention Effect of Selenium on Prevalence of Children Kaschin-Beck Disease in Active Endemic Areas in Qinghai Plateau - Qiang Li; Zhi-jun Zhao; Pei-zhen Yang; Xiao-qing Xu; Yu-fang Liu; Hui-zhen Yu; Xiao Ma; Rui Du; Lei Zhu (Biological Trace Element Research, 2016)

Effect of Dietary Selenomethionine Supplementation on Growth Performance, Tissue Se Concentration, and Blood Glutathione Peroxidase Activity in Kid Boer Goats - Yu-xuan Song; Jin-xing Hou; Lei Zhang; Jian-gang Wang; Xiao-rui Liu; Zhan-qin Zhou; Bin-yun Cao (Biological Trace Element Research, 2015)

Estimation of Permeability from NMR Logs Based on Formation Classification Method in Tight Gas Sands - Deng-Feng Wei; Xiao-Peng Liu; Xiao-Xin Hu; Rui Xu; Ling-Ling Zhu (Acta Geophysica, 2015)

Thermosensation and longevity - Rui Xiao; Jianfeng Liu; X. Z. Shawn Xu (Journal of Comparative Physiology A, 2015)

Umezawaea endophytica sp. nov., isolated from tobacco root samples - Xiao Chu; Bing-Bing Liu; Rui Gao; Zheng-Yu Zhang; Yan-Qing Duan; Salam Nimaichand; Wei Chen; Wen-Jun Li (Antonie van Leeuwenhoek, 2015)

A MicroRNA Profile in Fmr1 Knockout Mice Reveals MicroRNA Expression Alterations with Possible Roles in Fragile X Syndrome - Ting Liu; Rui-Ping Wan; Ling-Jia Tang; Shu-Jing Liu; Hai-Jun Li; Qi-Hua Zhao; Wei-Ping Liao; Xiao-Fang Sun; Yong-Hong Yi; Yue-Sheng Long (Molecular Neurobiology, 2015)

Ribosomal Protein L3 Mutations are Associated with cfr-Mediated Linezolid Resistance in Clinical Isolates of Staphylococcus cohnii - Hongtao Xu; Rui Tian; Yanming Li; Dongke Chen; Yalin Liu; Yunjian Hu; Fei Xiao (Current Microbiology, 2015)

Gene transcript profiles of the TIA biosynthetic pathway in response to ethylene and copper reveal their interactive role in modulating TIA biosynthesis in Catharanthus roseus - Ya-Jie Pan; Jia Liu; Xiao-Rui Guo; Yuan-Gang Zu; Zhong-Hua Tang (Protoplasma, 2015)

Retinoic acid promotes primary fetal alveolar epithelial type II cell proliferation and differentiation to alveolar epithelial type I cells - Rui-wei Gao; Xiang-yong Kong; Xiao-xi Zhu; Guo-qing Zhu; Jin-shuai Ma; Xiu-xiang Liu (In Vitro Cellular & Developmental Biology - Animal, 2015)

Screening of Inherited Metabolic Disorders in Infants with Infantile Spasms - Xiao-Ming Liu; Rui Li; Sheng-Zhi Chen; Yan Sang; Jiao Chen; Cong-Hai Fan (Cell Biochemistry and Biophysics, 2015)

Genome-Wide Identification, Expression, and Activity Analysis of Alkaline/Neutral Invertase Gene Family from Cassava (Manihot esculenta Crantz) - Yuan Yao; Meng-Ting Geng; Xiao-Hui Wu; Jiao Liu; Rui-Mei Li; Xin-Wen Hu; Jian-Chun Guo (Plant Molecular Biology Reporter, 2015)

Matching methods of classic hail echo cores of weather radar - Xue-tao Yu; Xiao-ping Rui; Shuang-xi Fu; Wei Liu (Natural Hazards, 2015)

Identification of a new maize inflorescence meristem mutant and association analysis using SLAF-seq method - Chao Xia; Li-li Chen; Ting-zhao Rong; Rui Li; Yong Xiang; Peng Wang; Chun-hua Liu; Xiao-qiu Dong; Bing Liu; Dan Zhao; Ru-jun Wei; Hai Lan (Euphytica, 2015)

Historic water consumptions and future management strategies for Haihe River basin of Northern China - Xiao-jun Wang; Jian-yun Zhang; Zhi-feng Yang; Shamsuddin Shahid; Rui-min He; Xing-hui Xia; Hong-wei Liu (Mitigation and Adaptation Strategies for Global Change, 2015)

Historical development and future perspectives of Environmental Specimen Bank in China: a mini review - Fang Qiu; Xiang-Zhou Meng; Yan-Ling Qiu; Qing-Hui Huang; Ying Liu; Ling-Ling Wu; Qian-Fen Xiao; Ya-Jie Sun; Rui Wang; Yi-Hui Zhou; Zhen-Yang Yu; Da-Qiang Yin; et al. (Environmental Science and Pollution Research, 2015)

Effect of auxin, cytokinin and nitrogen on anthocyanin biosynthesis in callus cultures of red-fleshed apple (Malus sieversii f.niedzwetzkyana) - Xiao-Hao Ji; Yan-Ting Wang; Rui Zhang; Shu-Jing Wu; Meng-Meng An; Min Li; Chuan-Zeng Wang; Xiao-Liu Chen; Yan-Min Zhang; Xue-Sen Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Enzyme Responses to Phytoremediation of PAH-Contaminated Soil Using Echinacea purpurea (L.) - Rui Liu; Lixing Zhao; Caixia Jin; Nan Xiao; R. N. Jadeja; Ting Sun (Water, Air, & Soil Pollution, 2014)

Snail regulated by PKC/GSK-3β pathway is crucial for EGF-induced epithelial-mesenchymal transition (EMT) of cancer cells - Zong-cai Liu; Xiao-hui Chen; Hai-xing Song; Hong-sheng Wang; Ge Zhang; Hao Wang; Dan-yang Chen; Rui Fang; Hao Liu; Shao-hui Cai; Jun Du (Cell and Tissue Research, 2014)

Toxic effects of sodium fluoride on cell proliferation and apoptosis of Leydig cells from young mice - Guo hua Song; Rui Li Wang; Zhao Yang Chen; Bin Zhang; Hai Long Wang; Mao Lin Liu; Ji Ping Gao; Xiao Yan Yan (Journal of Physiology and Biochemistry, 2014)

Simultaneous Determination of Calycosin-7-O-β-d-Glucoside, Ononin, Calycosin, Formononetin, Astragaloside IV, and Astragaloside II in Rat Plasma After Oral Administration of Radix Astragali Extraction for Their Pharmacokinetic Studies by Ultra-Pressure Liquid Chromatography with Tandem Mass Spectrometry - Xiao-hua Liu; Jian-bang Zhao; Long Guo; Ying-lai Yang; Fang Hu; Rui-juan Zhu; Shi-lan Feng (Cell Biochemistry and Biophysics, 2014)

A Clinical Study of Patients with Coronary Heart Disease Complicated with Hypertriglyceridemic Waist Phenotype - Rui-feng Yang; Zhi Lin; Xiao-yong Liu; Ge Zhang (Cell Biochemistry and Biophysics, 2014)

Ergosteroid derivatives from an algicolous strain of Aspergillus ustus - Xiang-Hong Liu; Feng-Ping Miao; Xiao-Rui Liang; Nai-Yun Ji (Natural Product Research, 2014)

Dynamic stability analysis of wedge in rock slope based on kinetic vector method - Weida Ni; Huiming Tang; Xiao Liu; Rui Yong; Zongxing Zou (Journal of Earth Science, 2014)

Characterization and expression profiles of MaACS and MaACO genes from mulberry (Morus alba L.) - Chang-ying Liu; Rui-hua Lü; Jun Li; Ai-chun Zhao; Xi-ling Wang; Umuhoza Diane; Xiao-hong Wang; Chuan-hong Wang; Ya-sheng Yu; Shu-mei Han; Cheng Lu; Mao-de Yu (Journal of Zhejiang University-SCIENCE B, 2014)

Zircon geochronology constraints on the age and nature of ‘Precambrian metamorphic rocks’ in the Xing’an block of Northeast China - Wei Sun; Xiao-Guo Chi; Zhi Zhao; Shi-Yu Pan; Jian-Feng Liu; Rui Zhang; Jing-Yu Quan (International Geology Review, 2014)

Genome-Wide Identification, Classification, Expression Profiling, and SSR Marker Development of the MADS-Box Gene Family in Citrus - Xiao-Jin Hou; Sheng-Rui Liu; Muhammad Rehman Gul Khan; Chun-Gen Hu; Jin-Zhi Zhang (Plant Molecular Biology Reporter, 2014)

Effects of bromide and iodide ions on the formation of disinfection by-products during ozonation and subsequent chlorination of water containing biological source matters - Xiao-song Zha; Yan Liu; Xiang Liu; Qiang Zhang; Rui-hua Dai; Ling-wen Ying; Jin Wu; Jing-ting Wang; Luming Ma (Environmental Science and Pollution Research, 2014)

Climate change and water resources management in Tuwei river basin of Northwest China - Wang Xiao-jun; Zhang Jian-yun; Wang Jian-hua; He Rui-min; Amgad ElMahdi; Liu Jin-hua; Wang Xin-gong; David King; Shamsuddin Shahid (Mitigation and Adaptation Strategies for Global Change, 2014)

New isoflavones with cytotoxic activity from the rhizomes of Iris germanica L. - Guo-Yong Xie; Xiao-Ying Qin; Rui Liu; Qi Wang; Bin-Bin Lin; Guo-Kai Wang; Guang-Kai Xu; Rui Wen; Min-Jian Qin (Natural Product Research, 2013)

Surfactin-Induced Apoptosis Through ROS–ERS–Ca2+-ERK Pathways in HepG2 Cells - Chun-ling Wang; Chuan Liu; Li-li Niu; Li-rui Wang; Li-hua Hou; Xiao-hong Cao (Cell Biochemistry and Biophysics, 2013)

Constructing genetic linkage maps for Pinus elliottii var. elliottii and Pinus caribaea var. hondurensis using SRAP, SSR, EST and ISSR markers - Hui-xiao Yang; Rui Luo; Fen-cheng Zhao; Tian-yi Liu; Chun-xin Liu; Shao-wei Huang (Trees, 2013)

Niche Divergence Among Sex and Age Classes in Black-and-White Snub-nosed Monkeys (Rhinopithecus bieti) - Yi Wan; Rui-Chang Quan; Guo-Peng Ren; Lin Wang; Yong-Cheng Long; Xiao-Hu Liu; Jian-Guo Zhu (International Journal of Primatology, 2013)

Valproic acid reduces autophagy and promotes functional recovery after spinal cord injury in rats - Hai-Hu Hao; Li Wang; Zhi-Jian Guo; Lang Bai; Rui-Ping Zhang; Wei-Bing Shuang; Yi-Jia Jia; Jie Wang; Xiao-Yu Li; Qiang Liu (Neuroscience Bulletin, 2013)

High resource capture and use efficiency and prolonged growth season contribute to invasiveness of Eupatorium adenophorum - Wei-Bin Wang; Rui-Fang Wang; Yan-Bao Lei; Chao Liu; Li-Hong Han; Xiao-Dong Shi; Yu-Long Feng (Plant Ecology, 2013)

WHAMM is required for meiotic spindle migration and asymmetric cytokinesis in mouse oocytes - Xin Huang; Lu Ding; Rui Pan; Peng-Fei Ma; Pan-Pan Cheng; Chun-Hui Zhang; Yu-Ting Shen; Lin Xu; Yu Liu; Xiao-Qin He; Zhong-Quan Qi; Hai-Long Wang (Histochemistry and Cell Biology, 2013)

Pollen morphology and ontogeny of Maianthemum bifolium (L.) F.W. Schmidt in China - Bing-Xiao Chen; Chun-Hai Zhao; Yun-Yun Zhao; Xiao-Rui Liu; Jia-Xi Liu (Plant Systematics and Evolution, 2013)

A stabilized least-squares imaging condition with structure constraints - Guo-Chang Liu; Xiao-Hong Chen; Jian-Yong Song; Zhen-Hua Rui (Applied Geophysics, 2012)

Microsporogenesis and development of the male gametophyte in Allium senescens L. (Liliaceae) in China - Jiao Zhang; Xiao-Rui Liu; Fei-Xiong Zhang; Jia-Xi Liu (Plant Systematics and Evolution, 2012)

Pollen development of Cardiocrinum giganteum (Wall.) Makina in China - Hong-Na Chen; Chun-Hai Zhao; Xiao-Rui Liu; Jia-Xi Liu (Plant Systematics and Evolution, 2012)

Isolation and Characterization of the Cold-Induced Phyllostachys edulis AP2/ERF Family Transcription Factor, peDREB1 - Lei Liu; Xiao-Lu Cao; Rui Bai; Na Yao; Lu-Bin Li; Cong-Fen He (Plant Molecular Biology Reporter, 2012)

Synthesis of 2-R1-2-(4-(2-fluoroethoxy)benzamido)acetate as potential PET imaging agents - Yong He; Jingli Xu; Hang Liu; Man Feng; Xiao Wang; Rui Ding; Chuanmin Qi; Yurong Chen; Fang Li; Zhao-Hui Zhu; Yong-Hong Dang; Ming Wang; et al. (Medicinal Chemistry Research, 2012)

Characterization of the expression profile of calpain-3 (CAPN3) gene in chicken - Zeng-Rong Zhang; Qing Zhu; Yong-Gang Yao; Xiao-Song Jiang; Hua-Rui Du; Yi-Ping Liu (Molecular Biology Reports, 2012)

Preparation and bioevaluation of 99mTc nitrido radiopharmaceuticals with pyrazolo[1,5-a]pyrimidine as tumor imaging agents - Rui Ding; Yong He; Jingli Xu; Hang Liu; Xiao Wang; Man Feng; Chuanmin Qi; Junbo Zhang; Cheng Peng (Medicinal Chemistry Research, 2012)

Gel microbead cultivation with a subenrichment procedure can yield better bacterial cultivability from a seawater sample than standard plating method - Shiqi Ji; Rui Zhao; Qi Yin; Yuan Zhao; Chenguang Liu; Tian Xiao; Xiaohua Zhang (Journal of Ocean University of China, 2012)

Characterization of the expression profiles of calpastatin (CAST) gene in chicken - Zeng-Rong Zhang; Xiao-Song Jiang; Hua-Rui Du; Qing Zhu; Xiao-Cheng Li; Chao-Wu Yang; Yi-Ping Liu (Molecular Biology Reports, 2012)

Clinical Study of Autologous Cytokine-Induced Killer Cells for the Treatment of Elderly Patients with Diffuse Large B-Cell Lymphoma - Xue-chun Lu; Bo Yang; Rui-li Yu; Xiao-hua Chi; Shuai Tuo; Chao-wei Tuo; Hong-li Zhu; Yao Wang; Chao-guang Jiang; Xiao-bing Fu; Yang Yang; Yang Liu; et al. (Cell Biochemistry and Biophysics, 2012)

Synthesis and Characterization of Triphenylethylene Derivatives with Aggregation-Induced Emission Characteristics - Xiao-Fang Li; Zhen-Guo Chi; Bing-Jia Xu; Hai-Yin Li; Xi-Qi Zhang; Wei Zhou; Yi Zhang; Si-Wei Liu; Jia-Rui Xu (Journal of Fluorescence, 2011)

The Electrostatic Interactions Between Nano-TiO2 and Trypsin Inhibit the Enzyme Activity and Change the Secondary Structure of Trypsin - Wen-Rui Wang; Rong-Rong Zhu; Rong Xiao; Hui Liu; Shi-Long Wang (Biological Trace Element Research, 2011)

Expression of a novel gene FAM43B repressing cell proliferation is regulated by DNA methylation in hepatocellular carcinoma cell lines - Xiao Xu; Rui-Fang Liu; Bing-Bing Wan; Wen-Ming Xing; Jian Huang; Ze-Guang Han (Molecular and Cellular Biochemistry, 2011)

Pollen morphology of Hosta Tratt. in China and its taxonomic significance - Jia-Xi Liu; Chun-Hai Zhao; Xiao-Rui Liu; Yi-Zhen Xi; Yu-Long Zhang (Plant Systematics and Evolution, 2011)

The cardioprotective effect of fluvastatin on ischemic injury via down-regulation of toll-like receptor 4 - Jun Yang; Xiao-Dong Zhang; Jian Yang; Jia-Wang Ding; Zhao-Qi Liu; Shu-Guo Li; Rui Yang (Molecular Biology Reports, 2011)

Water resources planning and management based on system dynamics: a case study of Yulin city - Xiao-jun Wang; Jian-yun Zhang; Jiu-fu Liu; Guo-qing Wang; Rui-min He; Amgad Elmahdi; Sondoss Elsawah (Environment, Development and Sustainability, 2011)

Synthesis and Properties of Diphenylcarbazole Triphenylethylene Derivatives with Aggregation-Induced Emission, Blue Light Emission and High Thermal Stability - Bing-jia Xu; Zhen-guo Chi; Xiao-fang Li; Hai-yin Li; Wei Zhou; Xi-qi Zhang; Cheng-cheng Wang; Yi Zhang; Si-wei Liu; Jia-rui Xu (Journal of Fluorescence, 2011)

Comparison of Responsive Behaviors of Two Cinnamic Acid Derivatives Containing Carbazolyl Triphenylethylene - Xi-qi Zhang; Zhen-guo Chi; Bing-jia Xu; Hai-yin Li; Wei Zhou; Xiao-fang Li; Yi Zhang; Si-wei Liu; Jia-rui Xu (Journal of Fluorescence, 2011)

Chemical constituents of Gentiana macrophylla Pall. - Zhi-Bo Jiang; Hong-Li Liu; Xiao-Qing Liu; Ji-Ning Shang; Jia-Rui Zhao; Cheng-Shan Yuan (Natural Product Research, 2010)

MicroRNA-17 post-transcriptionally regulates polycystic kidney disease-2 gene and promotes cell proliferation - Huan Sun; Qing-Wei Li; Xiao-Yan Lv; Jian-Zhong Ai; Qiu-Tan Yang; Jing-Jing Duan; Guo-Hui Bian; Yan Xiao; Yi-Dong Wang; Zheng Zhang; Yu-Hang Liu; Rui-Zhi Tan; et al. (Molecular Biology Reports, 2010)

Down-regulation of Pkd2 by siRNAs suppresses cell–cell adhesion in the mouse melanoma cells - Guo-Hui Bian; Ge Cao; Xiao-Yan Lv; Qing-Wei Li; Huan Sun; Yan Xiao; Jian-Zhong Ai; Qui-Tan Yang; Jing-Jing Duan; Yi-Dong Wang; Zheng Zhang; Rui-Zhi Tan; et al. (Molecular Biology Reports, 2010)

Angiotensin II upregulates Toll-like receptor 4 and enhances lipopolysaccharide-induced CD40 expression in rat peritoneal mesothelial cells - Jun Wu; Xiao Yang; Yun-Fang Zhang; Shu-Feng Zhou; Rui Zhang; Xiu-Qing Dong; Jin-Jin Fan; Mei Liu; Xue-Qing Yu (Inflammation Research, 2009)

Development and characterization of new microsatellite loci from Chinese mitten crab (Eriocheir sinensis) - Rui X. Mao; Ying Y. Zhao; Fu J. Liu; Zhi Y. Jia; Ning Hou; Yu M. Chang; Cui Y. Lu; Li Q. Liang; Xiao W. Sun (Conservation Genetics, 2009)

Relationships Among Genetic Makeup, Active Ingredient Content, and Place of Origin of the Medicinal Plant Gastrodia Tuber - Jun Tao; Zhi-yong Luo; Chikira Ismail Msangi; Xiao-shun Shu; Li Wen; Shui-ping Liu; Chang-quan Zhou; Rui-xin Liu; Wei-xin Hu (Biochemical Genetics, 2009)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Rapid Quantitative Detection of Vibrio parahaemolyticus in Seafood by MPN-PCR - Xiaoyan Luan; Jixiang Chen; Yu Liu; Yun Li; Juntao Jia; Rui Liu; Xiao-Hua Zhang (Current Microbiology, 2008)

Adenovirus-mediated PDCD5 gene transfer sensitizes K562 cells to apoptosis induced by idarubicin in vitro and in vivo - Guo-Rui Ruan; Hong-Shan Zhao; Yan Chang; Jin-Lan Li; Ya-Zhen Qin; Yan-Rong Liu; Shan-Shan Chen; Xiao-Jun Huang (Apoptosis, 2008)

Regulation of skeletal muscle differentiation in fibroblasts by exogenous MyoD gene in vitro and in vivo - Rui-feng Qin; Tian-qiu Mao; Xiao-ming Gu; Kai-jing Hu; Yan-pu Liu; Jin-wu Chen; Xin Nie (Molecular and Cellular Biochemistry, 2007)

Role of iNOS-derived reactive nitrogen species and resultant nitrative stress in leukocytes-induced cardiomyocyte apoptosis after myocardial ischemia/reperfusion - Xiao-Liang Wang; Hui-Rong Liu; Lin Tao; Feng Liang; Li Yan; Rong-Rui Zhao; Bernard L. Lopez; Theodore A. Christopher; Xin-Liang Ma (Apoptosis, 2007)

Inhibition of Japanese Encephalitis Virus NS1 Protein Expression in Cell by Small Interfering RNAs - Xueqin Liu; Shengbo Cao; Rui Zhou; Gaoyuan Xu; Shaobo Xiao; Ying Yang; Minxuan Sun; Yaoming Li; Huanchun Chen (Virus Genes, 2006)